Battery, electronic equipment and vehicle

By introducing magnesium and nickel into the positive electrode active material of the secondary battery and adding conductive material to the surface area outside its (00l) plane, the problem of taking into account the high capacity and safety of the secondary battery is solved, and a high capacity and high safety battery is achieved.

CN119856298APending Publication Date: 2025-04-18SEMICON ENERGY LAB CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380063723.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-09-04
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

It is difficult to take into account the high capacity and safety of existing secondary batteries, especially in the positive electrode active material with layered rock salt crystal structures. The two-dimensional movement of the diffusion path of lithium ions leads to an increase in capacity but is prone to thermal runaway.

Method used

A positive electrode active material containing cobalt, oxygen, magnesium and nickel is used, wherein the distribution of magnesium and nickel has overlapping portions, and a conductive material is added to the surface area outside the (001) surface of the positive electrode active material to improve the safety and capacity of the battery.

Benefits of technology

A secondary battery with high capacity and high safety is realized. By suppressing oxygen release and crystal structure collapse, thermal runaway is avoided, and the stability and circulation characteristics of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856298A_ABST
    Figure CN119856298A_ABST
Patent Text Reader

Abstract

Provided is a secondary battery having high capacity and high safety. The battery includes a positive electrode including a positive electrode active material and a conductive material, the positive electrode active material including cobalt, oxygen, magnesium, and nickel, the positive electrode active material having a median diameter of 1 [mu] m or more and 12 [mu] m or less, and the distribution of magnesium has a portion overlapping the distribution of nickel in an EDX-ray analysis in the depth direction of a region having a surface other than the (00l) plane of the positive electrode active material. The conductive material is bonded to a part of a surface other than the (00l) surface of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to a battery, specifically, to a secondary battery. In addition, the present invention is not limited to the above-mentioned fields, and relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, an electronic device, a vehicle, and a method for manufacturing the same. The semiconductor device, display device, light-emitting device, power storage device, lighting device, electronic device, and vehicle can use the secondary battery of the present invention as a required power source. For example, the electronic device includes an information terminal device equipped with a secondary battery, etc. Furthermore, the power storage device includes a fixed power storage device, etc. Background Art

[0002] In recent years, the demand for high-output, high-capacity secondary batteries has increased dramatically, and they have become a necessity in modern society as a reusable energy source.

[0003] It is said that it is difficult to ensure high capacity and safety of secondary batteries at the same time. For example, in a positive electrode active material having a layered rock salt type crystal structure, because the diffusion path of lithium ions moves two-dimensionally in the crystal structure, high capacity is expected. However, it is believed that in a positive electrode active material having a layered rock salt type crystal structure, when too many lithium ions are detached during charging, thermal runaway is easily caused due to the collapse of the crystal structure, so there are problems in safety. In addition, it is known that lithium ion secondary batteries enter thermal runaway through several states (Non-Patent Document 1).

[0004] As a positive electrode active material having a layered rock salt type crystal structure, lithium cobalt oxide (LiCoO 2 ) and other lithium-ion secondary batteries. Lithium cobalt oxide has a layered rock salt crystal structure in which lithium ions can move two-dimensionally in the CoO 6 The interlayers are composed of octahedrons, so the cycle characteristics are also excellent. However, lithium cobalt oxide undergoes phase changes accompanying charging and discharging. For example, during charging, when lithium ions are detached to a certain extent, the phase change of lithium cobalt oxide from hexagonal to monoclinic occurs. Therefore, in order to utilize lithium cobalt oxide with excellent cycle characteristics, the amount of lithium ions detached is limited. In order to solve these problems, Patent Document 1 discloses a structure in which an additive element is added to lithium cobalt oxide to attempt to increase the capacity.

[0005] As a method for analyzing the crystal structure of a positive electrode active material, there is XRD (X-ray Diffraction). By using the ICSD (Inorganic Crystal Structure Database) introduced in Non-Patent Document 2, XRD data can be analyzed. For example, the lattice constant of lithium cobaltate described in Non-Patent Document 3 can be referred to using the ICSD. In addition, for analysis using the Rietveld method, for example, the analysis program RIETAN-FP (refer to Non-Patent Document 4) can be used. Furthermore, as crystal structure drawing software, VESTA (Non-Patent Document 5) can be used.

[0006] Since ancient times, fluorides such as fluorite (calcium fluoride) have been used as fluxes in ironmaking and the like, and their physical properties have been studied (for example, refer to Non-Patent Document 6). [Prior Art Documents] [Patent Documents]

[0007] [Patent Document 1] WO2020 / 026078 [Non-Patent Documents]

[0008] [Non-Patent Document 1] Nobuo Eda, Learning from Data, 2-4 Mechanisms of Heat Generation, Charge and Discharge Technology of Lithium-Ion Batteries, Published by Nippon CQ Publishing Co., Ltd. on April 4, 2020, pp. 68-72 [Non-Patent Document 2] Belsky, A. et al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., (2002) B58 364-369. [Non-Patent Document 3] Akimoto, J.; Gotoh, Y.; Oosawa, Y. “Synthesis and structure refinement of LiCoO 2 single crystals” Journal of Solid State Chemistry (1998) 141, p. 298-302. [Non-Patent Document 4] F. Izumi and K. Momma, Solid State Phenom., 130, 15-20 (2007) [Non-patent document 5] K. Momma and F. Izumi, J. Appl. Cryst. (2011). 44, 1272-1276 [Non-patent document 6] WE Counts, R. Roy, and E. F. Osborn, "Fluoride Model Systems: II, The Binary Systems CaF 2 -BeF 2 ,MgF 2 -BeF 2 , and LiF-MgF 2 ”, Journal of the AmericanCeramic Society, 36[1]12-17(1953). Summary of the invention Technical problem to be solved by the invention

[0009] When an internal short circuit occurs in a secondary battery, the layered rock salt type positive electrode active material, lithium cobalt oxide (sometimes referred to as LiCoO 2 Therefore, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material and a secondary battery with high capacity and high safety.

[0010] Note that the description of these objects does not prevent the existence of other objects. Note that one embodiment of the present invention does not necessarily achieve all of the above objects. Note that objects other than the above objects can be extracted from the description of the specification, drawings, and claims. Solutions to technical problems

[0011] One embodiment of the present invention is a battery comprising: a positive electrode comprising a positive electrode active material and a conductive material, wherein the positive electrode active material comprises cobalt, oxygen, magnesium and nickel, the median particle size of the positive electrode active material is greater than or equal to 1 μm and less than or equal to 12 μm, in an EDX line analysis in the depth direction of a region of the positive electrode active material having a surface other than a (001) surface, the distribution of magnesium has a portion overlapping with the distribution of nickel, and the conductive material is attached to a portion of the surface other than the (001) surface of the positive electrode active material.

[0012] Another embodiment of the present invention is a battery, comprising: a positive electrode comprising a positive electrode active material and a conductive material, wherein the positive electrode active material comprises cobalt, oxygen, magnesium and nickel, the median particle size of the positive electrode active material is greater than 1 μm and less than 12 μm, in an EDX line analysis in the depth direction of a region of the positive electrode active material having a surface other than the (001) surface, the concentration of magnesium is greater than 0.3 atomic% and less than 7 atomic%, and the conductive material is attached to a portion of the surface other than the (001) surface of the positive electrode active material.

[0013] Another embodiment of the present invention is a battery, comprising: a positive electrode comprising a positive electrode active material and a conductive material, wherein the positive electrode active material comprises cobalt, oxygen, magnesium, nickel and aluminum, the median particle size of the positive electrode active material is greater than 1 μm and less than 12 μm, in an EDX line analysis in the depth direction of a region of the positive electrode active material having a surface other than the (001) surface, the distribution of magnesium has a portion overlapping with the distribution of nickel and the peak of the magnesium concentration is closer to the surface side of the positive electrode active material than the peak of the aluminum concentration, and the conductive material is attached to a portion of the surface other than the (001) surface of the positive electrode active material.

[0014] Another embodiment of the present invention is a battery, comprising: a positive electrode comprising a positive electrode active material and a conductive material, wherein the positive electrode active material comprises cobalt, oxygen, magnesium, nickel and aluminum, the median particle size of the positive electrode active material is greater than 1 μm and less than 12 μm, in an EDX line analysis in the depth direction of a region of the positive electrode active material having a surface other than the (001) surface, the concentration of magnesium is greater than 0.3 atomic% and less than 7 atomic%, the concentration of aluminum is greater than 0.1 atomic% and less than 3 atomic%, and the conductive material is attached to a portion of the surface other than the (001) surface of the positive electrode active material.

[0015] In the present invention, the volume resistivity of the powder of the positive electrode active material is preferably 1.5×10 8 Ω·cm or more.

[0016] In the present invention, the conductive material preferably includes carbon fiber, graphene, or a graphene compound.

[0017] In the present invention, the carbon fibers preferably include carbon nanotubes.

[0018] In the present invention, the carbon nanotubes are preferably in a tangled shape. Effects of the Invention

[0019] According to one embodiment of the present invention, a battery with high safety can be provided. According to one embodiment of the present invention, a battery with high capacity and high safety can be provided.

[0020] Note that the description of these effects does not prevent the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of the above effects. Note that effects other than the above can be known and extracted from the description of the specification, drawings, claims, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a cross-sectional view illustrating a secondary battery. Figure 2A and Figure 2B It is a cross-sectional view illustrating a positive electrode active material. FIG. 3A to FIG. 3D It is a plan view of a positive electrode including a positive electrode active material and a conductive material. Figure 4 It shows that LiF and MgF 2 Diagram of the eutectic point. Figure 5 It is a graph showing the results of DSC measurement of fluorine compounds and mixtures. FIG. 6A to FIG. 6C It is a diagram illustrating the distribution of added elements. Fig. 7A and Figure 7B It is a diagram illustrating the distribution of added elements. Figure 8 It is a diagram illustrating the crystal structure of the positive electrode active material. Fig. 9 It is a figure which shows an XRD pattern. Fig.10 It is a figure which shows an XRD pattern. Fig.11A and Fig. 11B It is a figure which shows an XRD pattern. Fig. 12A and Fig. 12B is a diagram illustrating a needle prick test. Fig.13A and Fig. 13B It is a figure explaining the secondary battery in the needle penetration test. Fig.14 This is a graph showing temperature changes in a secondary battery in which an internal short circuit occurs. Fig.15 It is a graph showing the temperature change of the secondary battery in thermal runaway. FIG. 16A to FIG. 16D It is a diagram for explaining a method for producing a positive electrode active material. Fig.17 It is a diagram for explaining a method for producing a positive electrode active material. 18A to 18C It is a diagram for explaining a method for producing a positive electrode active material. FIG. 19A to FIG. 19D It is a cross-sectional view illustrating a positive electrode. Fig. 20A This is an exploded perspective view of a coin-type secondary battery. Fig. 20B is a perspective view of a coin-type secondary battery. Fig. 20C It is a cross-sectional stereogram. Fig.21A An example of a cylindrical secondary battery is shown. Fig. 21B An example of a cylindrical secondary battery is shown. Fig. 21C A plurality of examples of cylindrical secondary batteries are shown. Fig.21D An example of a power storage system including a plurality of cylindrical secondary batteries is shown. Fig.22A and Fig. 22B is a diagram illustrating an example of a secondary battery, Fig. 22C It is a diagram showing the internal state of a secondary battery. FIG. 23A to FIG. 23C It is a diagram for explaining an example of a secondary battery. Fig.24A and Fig. 24B This is an appearance diagram of a secondary battery. FIG. 25A to FIG. 25C It is a diagram for explaining a method for manufacturing a secondary battery. Fig.26A An example of the structure of a battery pack is shown. Fig.26B An example of the structure of a battery pack is shown. Fig.26C A structural example of a battery pack is shown. Fig.27A is a perspective view showing a battery pack according to one embodiment of the present invention. Fig.27B is the block diagram of the battery pack, Fig.27C is a block diagram of a vehicle including a battery pack. FIG. 28A to FIG. 28D It is a diagram illustrating an example of a transport vehicle. Fig.28E This is a diagram illustrating an example of an artificial satellite. Fig.29A and Fig.29B It is a diagram for explaining a building in which a secondary battery according to one embodiment of the present invention is installed. Fig. 30A is a diagram showing an electric bicycle, Fig. 30B is a diagram showing a secondary battery of an electric bicycle, Fig. 30C It is a figure explaining a small motorcycle. FIG. 31A to FIG. 31D It is a diagram for explaining an example of an electronic device. Fig.32A Showing an example of a wearable device, Fig.32B showing a perspective view of a watch type device, Fig.32C It is a diagram illustrating the side view of a wristwatch-type device. Fig.33 It is a graph showing the particle size distribution of Sample 1 and the like. Fig.34A and Fig.34B It is a graph showing the STEM-EDX analysis of Sample 1 and the like. FIG. 35A to FIG. 35C It is a graph showing the STEM-EDX analysis of Sample 1 and the like. FIG. 36A to FIG. 36C It is a graph showing the STEM-EDX analysis of Sample 1 and the like. Fig.37A and Fig.37B It is a graph showing the STEM-EDX analysis of Sample 1 and the like. Fig.38A and Fig.38B It is a graph showing the STEM-EDX analysis of Sample 1 and the like. Fig.39A and Fig.39B It is a graph showing the STEM-EDX analysis of Sample 1 and the like. FIG. 40A to FIG. 40C It is a graph showing the STEM-EDX analysis of Sample 1 and the like. FIG. 41A to FIG. 41C It is a graph showing the STEM-EDX analysis of Sample 1 and the like. Fig.42 is a SEM image of the positive electrode. Fig.43 is a SEM image of the positive electrode. FIG. 44A to FIG. 44C It is a graph which shows the discharge capacity of a charge-discharge cycle test. FIG. 45A to FIG. 45C It is a graph which shows the discharge capacity of a charge-discharge cycle test. Fig.46 is a graph showing the measurement results of the discharge capacity at different rates. Fig.47A and Fig.47B It is a graph which shows the discharge capacity of a charge-discharge cycle test. Fig.48A and Fig.48B It is a graph which shows the discharge capacity of a charge-discharge cycle test. FIG. 49A to FIG. 49C This is a graph showing XRD during charging. Modes for Carrying Out the Invention

[0022] Hereinafter, examples of embodiments of the present invention will be described using drawings and the like. Note that the present invention should not be interpreted as being limited to the following examples of embodiments. The embodiments of the invention may be changed within the scope of the spirit of the present invention.

[0023] In this specification, etc., the space group is represented by the short notation of the international symbol (or Hermann-Mauguin symbol). In addition, the Miller index is used to represent the crystal plane and the crystal orientation. In crystallography, the space group, crystal plane and crystal orientation are represented by a superscript bar to the number. However, in this specification, etc., due to the symbol limitation in the patent application, - (minus sign) is sometimes attached to the number to represent the space group, crystal plane and crystal orientation, instead of attaching a superscript bar to the number. In addition, "[]" is used to represent the individual orientation of the orientation in the crystal, "<>" is used to represent the collective orientation of all equivalent orientations, "()" is used to represent the individual face of the crystal face, and "{}" is used to represent the collective face with equivalent symmetry. In addition, in general, in order to facilitate the understanding of the structure, the trigonal system represented by the space group R-3m is represented by a compound hexagonal lattice of the hexagonal lattice. In this specification, etc., unless otherwise specified, the space group R-3m is also represented by a compound hexagonal lattice. Sometimes, (hkil) is used as the Miller index in addition to (hkl). Here, i is -(h+k).

[0024] In addition, in this specification, etc., the particles are not limited to spherical (circular cross-sectional shape), and the cross-sectional shape of each particle can also be elliptical, rectangular, trapezoidal, triangular, a quadrilateral with curved corners, an asymmetric shape, etc., and each particle can also be amorphous.

[0025] In addition, the theoretical capacity of the positive electrode active material refers to the amount of electricity when all the lithium that can be inserted and removed in the positive electrode active material is removed. 2 The theoretical capacity of LiNiO is 274 mAh / g (unit weight of positive electrode active material, the same below). 2 The theoretical capacity of LiMn is 274mAh / g. 2 O 4 The theoretical capacity is 148 mAh / g.

[0026] In addition, x in the composition formula, such as Li x MO 2 The x in the positive electrode active material represents the amount of lithium that can be inserted and removed. M represents a transition metal. In this specification, M is the sum of cobalt, nickel, and manganese unless otherwise specified. In the positive electrode active material of a lithium-ion secondary battery, x = (theoretical capacity - charging capacity) / theoretical capacity can be established. For example, when LiMO 2 When a lithium-ion secondary battery used as a positive electrode active material is charged to a positive electrode active material unit weight of 219.2 mAh / g, it can be said that the positive electrode active material is Li 0.2 MO 2 Or we can say x = 0.2. x MO2 A smaller x in [it] means, for example, the case where 0.1 < x ≤ 0.24.

[0027] Li that is appropriately synthesized before being used for the positive electrode x MO 2 When it roughly satisfies the stoichiometric ratio, this Li x MO 2 is LiMO 2 and x = 1. Additionally, Li in the lithium ion secondary battery at the end of discharge x MO 2 can also be said to be LiMO 2 and x = 1. Here, the end of discharge means, for example, a state where the voltage becomes 3.0 V or 2.5 V or less at a current of 100 mA / g or less.

[0028] The charge capacity and / or discharge capacity used to calculate x in Li x MO 2 is preferably measured under conditions where there is no influence of decomposition of short circuit and / or electrolyte, or the influence of decomposition of short circuit and / or electrolyte is small. For example, data of a lithium ion secondary battery in which a capacity change regarded as a short circuit occurs cannot be used for the calculation of x.

[0029] In addition, the space group of the positive electrode active material, etc. is identified by XRD, electron diffraction, neutron diffraction, etc. Therefore, in this specification, etc., belonging to a certain space group or being a space group means being identified as a certain space group.

[0030] Furthermore, when the arrangement of anions is roughly close to cubic close packing, it can be regarded as cubic close packing. The anion arrangement of cubic close packing refers to the following state: anions of the second layer are arranged in the voids of the anions in the first layer, and anions of the third layer are arranged directly above the voids of the anions in the second layer rather than directly above the anions in the first layer. Therefore, the anions do not necessarily have to be strictly cubic lattice. At the same time, in fact, crystals all have defects, so the analysis results can also not be based on theory. For example, in the FFT (Fast Fourier Transform) diagram of an electron diffraction pattern or a TEM (Transmission Electron Microscope) image, etc., spots may also appear at positions slightly different from the theoretical positions. For example, when the azimuth deviation difference from the theoretical position is 5 degrees or less or 2.5 degrees or less, it can be said to have a cubic close packing structure.

[0031] The distribution of a certain element refers to a region where the element is continuously detected within a range where the element is not regarded as noise in a certain continuous analysis method.

[0032] In this specification, etc., the surface portion of the positive electrode active material refers to an area within 20nm or an area within 30nm in a direction perpendicular or substantially perpendicular to the surface from the surface to the inside. The surface portion is synonymous with the vicinity of the surface and the area near the surface. Perpendicular or substantially perpendicular to specifically refers to an angle formed with the surface of more than 80° and less than 100°. In addition, a region deeper than the surface portion of the positive electrode active material is referred to as the interior. The interior is synonymous with the bulk or the core.

[0033] Note that in this specification, etc., the surface of the positive electrode active material does not include carbonates, hydroxyls, etc. chemically adsorbed after the positive electrode active material is manufactured. In addition, it does not include electrolytes, adhesives, conductive materials, or compounds derived from them attached to the surface of the positive electrode active material. Therefore, when quantifying the elements contained in the positive electrode active material, the following correction can also be performed, that is, removing carbon, hydrogen, excess oxygen, excess fluorine, etc. that may be detected by surface analysis.

[0034] In this specification, etc., the positive electrode active material is sometimes described as a composite oxide, a positive electrode material, a positive electrode material for a secondary battery, a positive electrode material for a lithium ion secondary battery, etc. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a compound. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composition. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composite.

[0035] In addition, when describing the characteristics of each particle of the positive electrode active material in the following embodiments, it is not necessary for all particles to have the characteristics. For example, as long as 50% or more, preferably 70% or more, and more preferably 90% or more of the three or more positive electrode active material particles selected irregularly have the characteristics, it can be said that the characteristics of the positive electrode active material and the secondary battery including the positive electrode active material are fully improved.

[0036] Generally, as the charge voltage of a secondary battery increases, the voltage applied to the positive electrode also increases. In the positive electrode active material of one embodiment of the present invention, the positive electrode active material in a charged state is stable, so that a decrease in discharge capacity due to repeated charge and discharge can be suppressed.

[0037] In addition, the internal short circuit or external short circuit of the secondary battery can cause heat and fire in addition to causing defects in the charging operation and / or discharging operation of the secondary battery. In order to achieve a safe secondary battery, it is preferred to suppress the internal short circuit or external short circuit also at a high charging voltage. The positive electrode active material of one embodiment of the present invention can also suppress the internal short circuit or external short circuit at a high charging voltage. Therefore, a secondary battery that simultaneously achieves a large discharge capacity and high safety can be manufactured. The internal short circuit of a secondary battery refers to the phenomenon that the positive and negative electrodes are in contact inside the battery. In addition, the external short circuit of a secondary battery is assumed to be used incorrectly, and refers to the phenomenon that the positive and negative electrodes are in contact outside the battery.

[0038] In this specification, etc., ignition in the needle penetration test refers to the phenomenon that an open flame is observed on the outside of the outer packaging within 1 minute after the needle is inserted or thermal runaway of the secondary battery occurs. For example, when thermal decomposition products of the positive electrode and / or the negative electrode are observed at a distance of more than 2 cm from the part of the needle after the needle penetration test, this situation is called thermal runaway. Thermal decomposition products of the positive electrode and / or the negative electrode include, for example, aluminum oxide formed by oxidation of aluminum of the positive electrode current collector and copper oxide formed by oxidation of copper of the negative electrode current collector.

[0039] For example, when layered rock salt type LiMO is used as the positive electrode active material 2 (M is mainly Co, and may also be Co and Ni), theoretically, the ratio of the number of atoms of M to the number of atoms of O (hereinafter referred to as A O / A M ) is 2. On the other hand, in the case of thermal runaway of LiMO 2 When oxygen is released, A O / A M Therefore, for example, the following refers to the occurrence of thermal runaway: After the needle puncture test, the energy dispersive X-ray spectrometry (EDX: Energy Dispersive X-ray Spectroscopy) analysis of the A at a distance of more than 2 cm from the needle point indicates that thermal runaway has occurred. O / A M On the contrary, the A in the EDX analysis at a distance of more than 2 cm from the needle is less than 1.3. O / A M When the voltage is 1.3 or more, it can be said that thermal runaway has not occurred. When the battery voltage decreases but also increases after the needle penetration test, it can also be said that thermal runaway has not occurred.

[0040] On the other hand, even if open flames, sparks and / or smoke are confirmed in the needle penetration test, they only occur in the needle portion, that is, the fire does not spread, and thermal runaway of the secondary battery does not occur, and this is not called a fire. For example, when the above-mentioned fire does not occur even when the secondary battery is subjected to the needle penetration test, the secondary battery can be said to be a fire-proof secondary battery.

[0041] Note that, unless otherwise specified, the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) included in the secondary battery in the state before degradation are described. In addition, the following situation is not referred to as degradation: the situation where the discharge capacity is reduced due to aging treatment and burn-in treatment in the stage of manufacturing the secondary battery. For example, the following situation can be referred to as the state before degradation: the discharge capacity of a secondary battery composed of a single cell or a battery pack is more than 97% of the rated capacity. When using secondary batteries for portable devices, the rated capacity is based on JIS C8711:2019. When using secondary batteries other than the above, it is not limited to the above-mentioned JIS specifications, but is based on various JIS, IEC specifications, etc. for electric vehicle propulsion and industrial use.

[0042] In this specification, etc., the state before deterioration of the material included in the secondary battery is sometimes referred to as an initial article or an initial state, and the state after deterioration (a state in which the discharge capacity is less than 97% of the rated capacity of the secondary battery) is sometimes referred to as an article in use or a state in use or a used article or a used state.

[0043] In this specification, etc., a lithium ion secondary battery refers to a battery using lithium ions as carrier ions, but the carrier ions of the present invention are not limited to lithium ions. For example, alkali metal ions or alkaline earth metal ions can be used as carrier ions of the present invention, and specifically sodium ions can be used. At this time, lithium ions can be referred to as sodium ions to understand the present invention. In addition, when there is no restriction on the carrier ions, it is sometimes referred to as a secondary battery.

[0044] In this specification, etc., the (001) plane and the (003) plane are sometimes collectively referred to as the (001) plane. Note that in this specification, etc., the (001) plane is sometimes referred to as the C plane, the basal plane, etc. In addition, lithium has a two-dimensional diffusion path in lithium cobalt oxide. That is, it can be said that the diffusion path of lithium exists along the plane. In this specification, etc., sometimes the plane other than the plane where the diffusion path of lithium is exposed, that is, the plane where lithium is embedded and released (specifically, the (001) plane) is referred to as the end face.

[0045] In this specification, when the surface concavo-convex information is quantified based on the measurement data on a cross section of the active material, it can be said that the surface smoothness of the active material is a state with a surface roughness of at least 10 nm or less. In this specification, a cross section is, for example, a cross section obtained when observing using a STEM (Scanning Transmission Electron Microscope) image.

[0046] In this specification, etc., secondary particles refer to particles formed by the aggregation of primary particles. In this specification, etc., primary particles refer to particles that do not appear to have grain boundaries. In this specification, etc., single particles refer to particles that do not appear to have grain boundaries. In this specification, etc., single crystals refer to crystals in a state where there are no grain boundaries inside the particles, and polycrystalline refers to crystals in a state where there are grain boundaries inside the particles. Polycrystalline can also be referred to as an aggregate of multiple grains, and a grain boundary can also be referred to as an interface between two or more grains. In a polycrystalline, the directions of the grains are preferably consistent.

[0047] In this specification and the like, the median diameter (D50) may be simply referred to as the median diameter.

[0048] In this specification, "A and / or B" may be described, which is an example of description including "only A", "only B" or "A and B".

[0049] (Implementation Method 1) In this embodiment, a structure of a secondary battery having high capacity and high safety will be described.

[0050] <Secondary Battery> A secondary battery of one embodiment of the present invention includes a positive electrode, a negative electrode, and an electrolyte. An electrolyte that is liquid at room temperature is called an electrolyte. The secondary battery including the electrolyte includes a separator between the positive electrode and the negative electrode. In addition, the positive electrode, the negative electrode, the electrolyte, etc. are contained in an outer packaging body.

[0051] Figure 1 An example of the structure of a secondary battery 10 is shown. The secondary battery 10 includes a positive electrode 12, a negative electrode 11, and a separator 13 between the positive electrode 12 and the negative electrode 11. The positive electrode 12 includes a positive electrode collector 31 and a positive electrode active material layer 32 coated on the positive electrode collector 31. The positive electrode active material layer 32 contains a positive electrode active material. The positive electrode active material is preferably composed of primary particles, secondary particles or single particles. The negative electrode 11 includes a negative electrode collector 21 and a negative electrode active material layer 22 coated on the negative electrode collector 21. The negative electrode active material layer 22 contains a negative electrode active material. In addition, the separator 13 can also be omitted.

[0052] <Positive Electrode Active Material> In order to maintain charge neutrality during the insertion and extraction of lithium ions, the positive electrode active material of the lithium ion secondary battery preferably contains a transition metal that can be oxidized and reduced. Preferably, the positive electrode active material of one embodiment of the present invention mainly uses cobalt as a transition metal for redox reaction. In addition to cobalt, at least one or two or more selected from nickel and manganese can also be used. When cobalt accounts for more than 75 atomic%, preferably more than 90 atomic%, and more preferably more than 95 atomic% of the transition metal contained in the positive electrode active material, it is relatively easy to synthesize, easy to handle, and has many advantages such as good cycle characteristics, so it is preferred. This cobalt is called the main component of the positive electrode active material or the main component of the transition metal of the positive electrode active material.

[0053] Lithium cobalt oxide is preferably used as the positive electrode active material. Lithium cobalt oxide can also be expressed as a composite oxide containing lithium, cobalt and oxygen. Note that the composition of lithium cobalt oxide as the positive electrode active material is not strictly limited to Li:Co:O=1:1:2.

[0054] <Add Elements> The positive electrode active material preferably contains an additive element. Examples of the additive element include magnesium. (Mg), fluorine (F), nickel (Ni), aluminum (Al), and titanium (Ti), zirconium (Zr), vanadium (V), iron (Fe), manganese (Mn), chromium (Cr), niobium (Nb), arsenic (As), zinc (Zn), silicon (Si), sulfur (S), phosphorus (P), boron (B), bromine (Br) and beryllium (Be), etc.

[0055] As the additive element, it is not necessary to contain magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine or beryllium.

[0056] For example, by manufacturing a positive electrode active material that does not substantially contain manganese, the above advantages such as easier synthesis, easy handling, good cycle characteristics, etc. can be improved. The weight of manganese contained in the positive electrode active material is preferably less than 600 ppm, more preferably less than 100 ppm.

[0057] Figure 2A and Figure 2B An example of the structure of a positive electrode active material 100 according to one embodiment of the present invention is shown. Figure 2A and Figure 2B The (00l) plane in the layered rock salt crystal structure is attached. Figure 2A Arrows indicating insertion and extraction of lithium are attached to the surfaces other than the (001) surface.

[0058] like Figure 2AAs shown, the positive electrode active material 100 preferably includes an inner portion 100b and a first region 100s. The first region 100s preferably exists along the periphery of the positive electrode active material 100. In addition, the first region 100s is preferably located in the above-mentioned surface layer. The first region 100s is a region containing an additional element in addition to the elements contained in the positive electrode active material 100. In other words, the region where the additional element exists can be referred to as the first region 100s.

[0059] Magnesium is typically used as an additive element contained in the first region 100s. Magnesium has a high bonding force with oxygen, so the release of oxygen near magnesium can be suppressed. The first region 100s is a region that can suppress the release of oxygen. This first region 100s can be called a shell region. Oxygen release is suppressed, thereby improving the safety of the secondary battery.

[0060] The first region 100s is a region containing an additive element and in which oxygen release is suppressed, and its resistance is higher than that of the inner region 100b. That is, the resistance of the positive electrode active material including the first region 100s is sometimes higher than that of the positive electrode active material not including the first region 100s. The positive electrode active material not including the first region 100s can also be said to be a positive electrode active material not including magnesium.

[0061] Furthermore, when a secondary battery having a positive electrode active material 100 including the first region 100s is subjected to a needle penetration test, the first region 100s can slow down the speed of the current flowing into the positive electrode active material 100. In view of the effect of slowing down the speed of the current flowing into the positive electrode active material 100, the first region 100s is more preferably located in the surface layer. Note that the first region 100s may not be included in the entire surface layer.

[0062] As described above, it can be said that the safety of the secondary battery including the positive electrode active material including the first region 100 s is improved.

[0063] As the additive element contained in the first region 100s, an element other than magnesium may be used, but in order to exert the above-mentioned effect, it is preferable to use an element having a high bonding strength with at least oxygen. In addition to magnesium, aluminum or nickel may be cited. In order to further exert the above-mentioned effect, as the additive element contained in the first region 100s, aluminum and / or nickel may be included in addition to magnesium.

[0064] The surface layer of the positive electrode active material 100 includes a region having a (001) plane and a region having a plane other than the (001) plane. Figure 2AThe surface where the lithium ions diffuse, that is, the surface other than the (001) surface, is added. In other words, sometimes the distribution of the added elements in the surface of the region with the (001) surface and the region with the surface other than the (001) surface is different. For example, magnesium is more easily diffused in the region with the surface other than the (001) surface than in the region with the (001) surface. Therefore, Figure 2A As shown, the thickness of the first region 100s containing magnesium in the region having the (001) plane is sometimes thinner than the thickness in the region having a plane other than the (001) plane. Note that the thickness of the first region 100s can also be referred to as the distance in the depth direction from the surface of the positive electrode active material 100.

[0065] As described later, the positive electrode active material 100 containing an additive element such as magnesium can suppress the collapse of the crystal structure even when charged at a high voltage. Therefore, the charging voltage of the secondary battery containing the positive electrode active material 100 can be increased, thereby achieving a higher capacity.

[0066] Figure 2B The positive electrode active material 100 shown in the figure is an example of a structure including the cracks 102. This positive electrode active material 100 also exhibits the above-mentioned Figure 2A The effect shown.

[0067] The crack 102 can also be referred to as an area where the crystal plane deviates or an area where the crystal plane is split, and in many cases is generated along the (001) plane. A new surface is exposed in this crack 102. The first region 100s does not exist on the new surface. On the above-mentioned new surface, the effect of magnesium and the like in suppressing oxygen release cannot be expected, so it is preferred to make the crack 102 as small as possible in the positive electrode active material 100. For example, when observing the positive electrode active material 100 by surface SEM or cross-sectional SEM, the number of cracks 102 that can be observed in one positive electrode active material is preferably 0 or more and 5 or less.

[0068] The crack 102 is sometimes caused by the pressurization after the positive electrode slurry is applied to the positive electrode collector. Therefore, in the manufacturing process of the positive electrode of the present invention, the pressure of the press is preferably set to a linear pressure of 500 kN / m or less, more preferably a linear pressure of 300 kN / m or less, and further preferably a linear pressure of 250 kN / m or less. In addition, it is preferred to heat the roller when applying pressure with the press. Since the binder in the positive electrode slurry is melted by heating, the positive electrode active materials can be firmly combined with each other, the positive electrode active materials and the conductive material, the positive electrode active materials and the positive electrode collector, etc.

[0069] <Electrode Density> The electrode density of the positive electrode is preferably 3.0 g / cm 3 Above and 4.0g / cm 3 Below, more preferably 3.0g / cm3 Above and 3.5g / cm 3 When the above-mentioned line voltage is satisfied, the above-mentioned electrode density range is achieved. It is considered that a positive electrode having such an electrode density and a secondary battery including the positive electrode are less likely to cause thermal runaway.

[0070] <Surface smoothness of positive electrode active material> like Figure 2A As shown, it is preferable that the surface of the positive electrode active material 100 is smooth as a whole. In other words, it is preferable that the surface of the positive electrode active material 100 is smooth as a whole. It can be said that such a positive electrode active material 100 has no corners or curves.

[0071] And, if Figure 2A and Figure 2B As shown, there are preferably no or very few microscopic particles attached to the surface of the positive electrode active material 100. In this specification, microscopic particles refer to metal oxide particles of 0.001 μm or more and 0.1 μm or less. Microscopic particles are sometimes fragments of the positive electrode active material and / or unreacted additive element sources.

[0072] The particle size of the extremely small particles is the Feret diameter or the projected circle equivalent diameter measured from the surface SEM (Scanning Electron Microscope) image. For example, when the extremely small particles in the surface SEM image of the positive electrode are 10 / cm 2 Below, preferably 5 / cm 2 When the concentration is less than 0.05, it can be said that there are no extremely fine particles or the number of extremely fine particles is very small.

[0073] <Heating by Flux> As will be described later, in the manufacturing process of the positive electrode active material 100, it is preferred to add a material used as a flux together with the additive element source for heating. Due to the flux, solidification begins after the surface of the composite oxide and the additive element source are fully melted. Therefore, even if extremely small particles are attached to the surface of the composite oxide, they are melted through these processes, so there are no extremely small particles or very few extremely small particles remaining on the surface. That is, it can be said that there are no extremely small particles or very few extremely small particles on the surface of the positive electrode active material 100, which means that a material used as a flux is added to heat in the manufacturing process of the positive electrode active material 100.

[0074] <Initial Heating> like Figure 2AAs shown in FIG. 1 , the positive electrode active material 100 after initial heating is smooth and glossy as a whole. Initial heating refers to the heating of the composite oxide during the manufacturing process of the positive electrode active material. Due to the initial heating, the distortion and crystal defects in the positive electrode active material are also reduced.

[0075] <Crystallinity> The positive electrode active material 100 preferably has high crystallinity, and is more preferably a single crystal or a polycrystalline. After the above-mentioned initial heating, the crystallinity of the positive electrode active material 100 is improved, so it is preferred. In particular, when the positive electrode active material 100 has a single crystal, even if the volume of the positive electrode active material 100 changes due to charging and discharging, cracks are not easy to occur, so it is preferred. In addition, when the positive electrode active material 100 is a single crystal, the secondary battery using the positive electrode active material 100 is considered to be less likely to catch fire, so safety can be improved.

[0076] <Grain Boundary> The grain boundary refers to, for example, a portion where the particles of the positive electrode active material 100 are bonded together; a portion where the crystal orientation changes inside the positive electrode active material 100, such as a portion where bright lines and dark lines are repeatedly discontinuous in a STEM image, a portion containing multiple crystal defects, a portion with a disordered crystal structure, etc. In addition, a crystal defect refers to a defect observable by a cross-sectional TEM (transmission electron microscope), a cross-sectional STEM image, etc., that is, a structure where other atoms enter the lattice, a void, etc. The grain boundary can be said to be one of the surface defects. In addition, the vicinity of the grain boundary refers to the area from the grain boundary to within 10 nm. In addition to the distribution as described above, at least a portion of the added elements of the positive electrode active material 100 is unevenly distributed at the grain boundary and its vicinity.

[0077] In this specification, etc., "non-uniformly distributed" means that the concentration of an element in an arbitrary region is different from that in other regions. "Non-uniformly distributed" is synonymous with "segregation", "precipitation", "non-uniform", "deviation" and "mixture of high-concentration regions and low-concentration regions".

[0078] For example, the magnesium concentration at the grain boundary and its vicinity of the positive electrode active material 100 is preferably higher than that in other regions of the interior 100b. In addition, the fluorine concentration at the grain boundary and its vicinity is preferably higher than that in other regions of the interior 100b. In addition, the nickel concentration at the grain boundary and its vicinity is also preferably higher than that in other regions of the interior 100b. In addition, the aluminum concentration at the grain boundary and its vicinity is preferably higher than that in other regions of the interior 100b.

[0079] Grain boundaries are a type of surface defect. Therefore, like the surface, they tend to be unstable and are prone to changes in crystal structure. Therefore, the higher the concentration of the additive element A at the grain boundary and its vicinity, the more effectively the changes in crystal structure can be suppressed.

[0080] In addition, when the concentrations of magnesium and fluorine are high at the grain boundary and its vicinity, even when cracks are generated along the grain boundary of the positive electrode active material 100 of one embodiment of the present invention, the concentrations of magnesium and fluorine are high near the surface generated by the cracks. Therefore, the corrosion resistance of the positive electrode active material to hydrofluoric acid can also be improved after the cracks are generated.

[0081] <Median Particle Size of Positive Electrode Active Material> The median particle size of the positive electrode active material of the present invention is preferably small. The range of the median particle size is described. When the positive electrode active material is too small, it is sometimes difficult to carry out coating when manufacturing the positive electrode. In addition, when the positive electrode active material is too small, the surface area is too large, so the surface of the positive electrode active material may over-react with the electrolyte. In addition, when the positive electrode active material is too small, it is sometimes necessary to mix a large amount of conductive material, which may lead to a decrease in capacity. In this regard, the median particle size of the positive electrode active material is preferably greater than 1 μm. In addition, as the median particle size of the positive electrode active material, even the smallest particle is preferably greater than 100 nm. It is not easy to produce deviation areas in the positive electrode active material with a small median particle size, so it is preferred. In addition, the positive electrode active material with a small median particle size is not easy to crack even after the pressing process, so it is preferred.

[0082] On the other hand, when most of the active materials are too small, there are concerns that the density of the positive electrode active material layer decreases, the side reactions with the electrolyte increase, etc. In view of this, the median particle size of the positive electrode active material is preferably 12 μm or less, more preferably 10 μm or less, and further preferably 8 μm or less.

[0083] The median particle size of the positive electrode active material is 1 μm to 12 μm, preferably 1 μm to 10 μm. Alternatively, the median particle size of the positive electrode active material is 100 nm to 12 μm, preferably 100 nm to 10 μm.

[0084] The median particle size can be measured, for example, by observation using SEM or TEM or by a particle size distribution analyzer using a laser diffraction and scattering method. When measured by a particle size distribution analyzer using a laser diffraction and scattering method, the median particle size refers to the particle size when the cumulative amount accounts for 50% in the cumulative curve of the particle size distribution measurement result. In addition, as a method for measuring the median particle size by analysis using SEM or TEM, for example, more than 20 particles are measured and a cumulative particle amount curve is prepared, and the particle size when the cumulative amount accounts for 50% is defined as the median particle size.

[0085] <Conductive Materials> The conductive material is also called a conductive agent or a conductive auxiliary agent, and a carbon material is used. By covering, laminating or attaching the conductive material to the active material, multiple active materials can be electrically connected to each other, thereby improving the conductivity of the positive electrode. Note that laminating or attaching not only refers to the physical close contact between the active material and the conductive material, but also refers to the concept including the following situations: when a covalent bond occurs; when bonded by van der Waals force; when the conductive material covers a part of the surface of the active material; when the conductive material is embedded in the surface unevenness of the active material; when they are electrically connected without contact with each other, etc. Specifically, laminating the active material and the conductive material means that the contact between the two can be confirmed using a surface SEM image or a cross-sectional SEM image. At this time, there is no restriction on the type and strength of the force that attracts each other. The binder can also be located at the interface between the two.

[0086] As the conductive material of the positive electrode active material with a small median particle size, carbon black, Ketjen black (registered trademark), acetylene black (hereinafter sometimes referred to as AB), fullerene, graphene, graphene compounds, carbon fiber, etc. can be used. By using a particle-shaped conductive material such as carbon black, Ketjen black or AB as the conductive material of the positive electrode active material with a small median particle size, sufficient charge and discharge characteristics can be obtained.

[0087] In addition, when a rope-shaped or fibrous conductive material is used as a conductive material for a positive electrode active material with a small median particle size, an efficient conductive path can be supplied even if the amount added is small, thereby obtaining sufficient charge and discharge characteristics. In addition, a long-range conductive path can be ensured. In this specification, etc., a rope-shaped or fibrous conductive material is sometimes simply referred to as a carbon fiber, specifically, VGCF (registered trademark), carbon fiber or carbon nanotube (hereinafter sometimes referred to as CNT). CNT includes a single-layer CNT and a multilayer CNT. This is because the major axis or fiber length of the carbon fiber is large, so it can span multiple positive electrode active materials, in other words, it can be configured along multiple positive electrode active materials. The carbon fibers configured in this way look like the positive electrode active materials are bundled together. By adopting such carbon fibers, for example, a conductive path between a current collector and a positive electrode active material that is not adjacent to the current collector but is located far away can be realized. Therefore, the carbon fibers can be charged and discharged quickly. Furthermore, since the carbon fibers that bundle the positive electrode active materials together can suppress cracks, ruptures or deviations of the positive electrode active materials, a secondary battery with improved safety can be provided.

[0088] Figure 3A 1 shows a plan view of a positive electrode 12 including a positive electrode active material 100 and a conductive material 41. This plan view can be observed using a surface SEM image or the like. Figure 3AAn example of a structure using CNT as the conductive material 41 is shown. The conductive material 41 is in a tangled state, located between a plurality of positive electrode active materials 100 and attached to at least one positive electrode active material 100. The tangled state can also be said to include a state in which one or more CNTs are tangled together, a state in which one or more CNTs are aggregated, or a state in which one or more CNTs are in a block. The above-mentioned affixing state can also be said to be a state in which the conductive material 41 is arranged in a manner covering a plurality of positive electrode active materials 100, along a plurality of positive electrode active materials 100, entangled around a plurality of positive electrode active materials 100, or surrounded by a plurality of positive electrode active materials 100. In addition, the state in which the conductive material 41 is attached to the positive electrode active material 100 can also be said to be a state in which the conductive material 41 bundles the positive electrode active material 100.

[0089] Figure 3B The particle size ratio is shown Figure 3A The positive electrode 12 is a positive electrode 100a with a small positive electrode active material 100a, that is, a positive electrode 12 with a small median particle size. Multiple positive electrode active materials 100a sometimes agglomerate. The conductive material 41a is in a winding shape and is arranged in a manner that spans across multiple positive electrode active materials 100a. The situation of sticking can also be said to be a situation where the conductive material 41a is arranged in a manner that covers multiple positive electrode active materials 100a, along multiple positive electrode active materials 100a, around multiple positive electrode active materials 100a, or surrounds multiple positive electrode active materials 100a. In addition, the situation where the conductive material 41a is attached to the positive electrode active material 100a can also be said to be a situation where the conductive material 41a bundles the positive electrode active material 100a.

[0090] Figure 3C Shown including Figure 3A The positive electrode active material 100 having a large particle size, that is, a large median particle size and Figure 3B The positive electrode 12 is a positive electrode active material 100a having a small particle size, that is, a small median particle size. A plurality of positive electrode active materials 100a are sometimes aggregated. The conductive material 41 is wound and arranged at least in a manner of being attached to the positive electrode active material 100. The conductive material 41a is wound and arranged in a manner of being attached across a plurality of positive electrode active materials 100a.

[0091] exist Figure 3D In the enlarged view of FIG, the conductive material 41b attached to the surface other than the (001) surface of the positive electrode active material 100 is shown. It can be considered that it is easier to attach the conductive material 41b to the surface other than the (001) surface than to the (001) surface. Since the surface other than the (001) surface becomes the starting point of cracking, the positive electrode active material 100 can be suppressed from cracking by reinforcing it with the conductive material 41b attached to the surface other than the (001) surface.

[0092] Such conductive material 41 , conductive material 41 a , and conductive material 41 b can support rapid charging because they ensure a long-distance conductive path, and can suppress cracks, breakage, or deviation of the positive electrode active material 100 , thereby improving safety.

[0093] In addition, the conductive material 41 is a material with a lower resistance than the positive electrode active material 100. On the other hand, when the concentration of magnesium or the like in the first region 100s increases, it is possible to become a positive electrode active material 100 with high insulation. In other words, although safety is improved, the discharge capacity may be reduced. Therefore, by adopting a structure in which the conductive material 41 is attached to the surface of the positive electrode active material 100, it is easy to embed and release lithium even if the concentration of added elements such as magnesium increases, so it can work as a secondary battery.

[0094] Among carbon fibers, VGCF has a specific surface area of ​​100 m 2 / g or less, preferably 60m 2 / g or more, more preferably 20m 2 In carbon fiber, the specific surface area of ​​CNT is preferably 500m 2 / g or more, more preferably 650m 2 / g or more, more preferably 800m 2 As an example, the specific surface area is set to a value measured by the BET method.

[0095] In carbon fiber, the major axis or fiber length of VGCF is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 20 μm or less. The major axis or fiber length of CNT in carbon fiber is preferably 100 μm or more and 600 μm or less, more preferably 200 μm or more and 500 μm or less. In addition, when the above-mentioned major axis or fiber length is greater than the median particle size of the positive electrode active material, the carbon fiber can be arranged on multiple positive electrode active materials, so it is not limited to the above-mentioned numerical value. Furthermore, since the carbon fiber is in a entangled state, the major axis or fiber length of a carbon fiber is not very important, and the major axis when it is in a entangled state is also important as a conductive material.

[0096] Furthermore, the average diameter of the carbon fiber is preferably 1 nm or more and 180 nm or less, more preferably 2 nm or more and 150 nm or less. Because the average diameter of VGCF and the like is large, it can satisfy 100 nm or more and 180 nm or less, preferably 130 nm or more and 160 nm or less. The larger the average diameter, the more highly dispersible it can be. Because the average diameter of CNT and the like is small, it can satisfy 1 nm or more and 100 nm or less, preferably 1 nm or more and 50 nm or less, more preferably 3 nm or more and 5 nm or less. Note that it is sufficient to satisfy the above average diameter as a carbon fiber rather than as an aggregate. Carbon fibers having the above length and average diameter are easy to form aggregates and are more likely to be entangled. In particular, CNTs and the like having a small average diameter are easy to be entangled. While the entangled carbon fibers function as a conductive path for the positive active material with a small median particle size, cracks, ruptures or deviations in the positive active material can be suppressed, thereby suppressing the changes in multiple positive active materials caused by the charge and discharge cycle.

[0097] As a conductive material, graphene or graphene compounds can also be used instead of carbon fibers. Graphene or graphene compounds can be said to be sheet-like conductive materials, so like fibrous conductive materials, they can suppress the generation of cracks, ruptures or deviations in the positive electrode active material while playing the function of a conductive path for a positive electrode active material with a small median particle size, thereby suppressing the effect of changes in multiple positive electrode active materials caused by charge and discharge cycles.

[0098] The graphene compound in this specification etc. includes graphene, multilayer graphene, multigraphene (multigraphene), graphene oxide, multilayer graphene oxide, multigraphene oxide, reduced graphene oxide, reduced multilayer graphene oxide, reduced multigraphene oxide, graphene quantum dots, etc. Graphene compound refers to a compound containing carbon and having a two-dimensional structure formed using a carbon six-membered ring in a shape such as a flat plate or a sheet. In addition, the two-dimensional structure formed by the six-membered ring composed of carbon atoms can be referred to as a carbon sheet. Graphene compound may also have a functional group. In addition, the graphene compound preferably has a curved shape.

[0099] The content of the conductive material in the total amount of the active material layer is preferably 0.1wt% to 10wt%, more preferably 1wt% to 5wt%. When CNT is used as the conductive material, the content of CNT in the total amount of the active material layer is preferably 0.3wt% to 10wt%, more preferably 0.3wt% to 5wt%.

[0100] <Add element details> <Magnesium> Magnesium, one of the added elements, is divalent. In the layered rock salt type crystal structure, magnesium ions are more stable in the lithium position than in the cobalt position in the layered rock salt type crystal structure, and thus easily enter the lithium position. When magnesium is present at the lithium position in the surface layer at an appropriate concentration, the layered rock salt type crystal structure can be easily maintained. This is because magnesium present at the lithium position is used as CoO 2 In addition, in the presence of magnesium, such as in Li x CoO 2 When x is 0.24 or less, the oxygen around magnesium can be suppressed from being released. In addition, it can be expected that the density of the positive electrode active material 100 is improved when magnesium is present. In addition, when the magnesium concentration of the surface layer is high, it can be expected that the corrosion resistance to hydrofluoric acid generated by the decomposition of the electrolyte can be improved.

[0101] If magnesium has an appropriate concentration, it has no negative effect on the insertion and removal of lithium accompanying charge and discharge, so the above advantages can be obtained. However, excess magnesium may have a negative effect on the insertion and removal of lithium. In addition, the effect of contributing to the stabilization of the crystal structure is sometimes reduced. This is because magnesium not only enters the lithium position but also the cobalt position. In addition, there is also the following concern: excessive magnesium compounds (for example, oxides or fluorides, etc.) that are not substituted at the lithium position or the cobalt position are segregated on the surface of the positive electrode active material and become the resistance component of the secondary battery. In addition, the increase in the magnesium concentration of the positive electrode active material sometimes reduces the discharge capacity of the positive electrode active material. This is because the excess magnesium enters the lithium position and the amount of lithium contributing to charge and discharge is reduced.

[0102] Therefore, it is preferred that an appropriate amount of magnesium is included in the positive electrode active material 100 as a whole. For example, the atomic number ratio of magnesium is preferably greater than 0.001 times and less than 0.1 times the atomic number ratio of cobalt, more preferably greater than 0.01 times and less than 0.04 times, and further preferably about 0.02 times. Here, the amount of magnesium in the positive electrode active material 100 as a whole can be, for example, a value obtained by analyzing all elements of the positive electrode active material 100 using GD-MS, ICP-MS, etc., or a value based on the coordination value of the raw materials in the manufacturing process of the positive electrode active material 100.

[0103] <Aluminum> Aluminum, one of the added elements, may exist in the cobalt position in the layered rock salt type crystal structure. Aluminum is a typical trivalent element and its valence does not change, so the lithium around aluminum is not easy to move during charge and discharge. Therefore, aluminum and the lithium around it are used as pillars to suppress changes in the crystal structure. In addition, aluminum has the effect of suppressing the dissolution of surrounding cobalt and improving continuous charging tolerance. In addition, the Al-O bond is stronger than the Co-O bond, so the oxygen around aluminum can be suppressed from detaching. Through the above effects, thermal stability is improved. Therefore, when aluminum is included as an added element, the safety when used in a secondary battery can be improved. In addition, a positive electrode active material 100 can be achieved that is not prone to crystal structure collapse even after repeated charge and discharge.

[0104] On the other hand, when the amount of aluminum is too large, there is a possibility that the insertion and extraction of lithium may be adversely affected.

[0105] Therefore, it is preferred that an appropriate amount of aluminum is included in the positive electrode active material 100 as a whole. For example, the atomic number ratio of aluminum in the positive electrode active material 100 as a whole is preferably 0.05% or more and 4% or less of the atomic number ratio of cobalt, more preferably 0.1% or more and 2% or less, and further preferably 0.3% or more and 1.5% or less. Alternatively, it is preferably 0.05% or more and 2% or less. Alternatively, it is preferably 0.1% or more and 4% or less. The amount in the positive electrode active material 100 as a whole shown here can be, for example, a value obtained by elemental analysis of the positive electrode active material 100 as a whole using GD-MS, ICP-MS, etc., or a value obtained by mixing raw materials in the manufacturing process of the positive electrode active material 100.

[0106] <Nickel> Nickel, which is one of the added elements, may be present at the cobalt site or the lithium site. When nickel is present at the cobalt site, the redox potential is lower than that of cobalt, and the discharge capacity is increased, which is preferable.

[0107] In addition, when nickel is present at the lithium position, the deviation of the layered structure composed of octahedrons of cobalt and oxygen is suppressed. In addition, the volume change caused by charging and discharging is also suppressed. In addition, the elastic modulus is increased, that is, it becomes hard. This is because the nickel present at the lithium position is also used as CoO 2 Therefore, it is expected that the crystal structure will be more stable when charging is performed at a high temperature of 45°C or higher, which is preferable.

[0108] On the other hand, when the amount of nickel is too large, the influence of distortion due to the Jan-Teller effect increases, which is not preferable. In addition, when the amount of nickel is too large, it may have a negative impact on the insertion and extraction of lithium.

[0109] Therefore, it is preferred that an appropriate amount of nickel is included in the positive electrode active material 100 as a whole. For example, the atomic number ratio of nickel contained in the positive electrode active material 100 is preferably greater than 0% of the atomic number ratio of cobalt and is less than 7.5%, more preferably greater than 0.05% and less than 4%, further preferably greater than 0.1% and less than 2%, and further preferably greater than 0.2% and less than 1%. Alternatively, it is preferably greater than 0% and less than 4%. Alternatively, it is preferably greater than 0% and less than 2%. Alternatively, it is preferably greater than 0.05% and less than 7.5%. Alternatively, it is preferably greater than 0.05% and less than 2%. Alternatively, it is preferably greater than 0.1% and less than 7.5%. Alternatively, it is preferably greater than 0.1% and less than 4%. The amount of nickel shown here can be, for example, a value obtained by elemental analysis of the positive electrode active material as a whole using GD-MS, ICP-MS, etc., or a value obtained by mixing raw materials in the manufacturing process of the positive electrode active material.

[0110] <Fluorine> Fluorine, one of the added elements, is a monovalent anion, and when part of the oxygen in the surface portion is replaced by fluorine, the lithium separation energy is reduced. This is because the valence change of the cobalt ion accompanying the lithium separation varies depending on the presence or absence of fluorine, for example, from trivalent to tetravalent in the absence of fluorine, and from divalent to trivalent in the presence of fluorine, and the redox potential is different. Therefore, when part of the oxygen in the surface portion of the positive electrode active material 100 is replaced by fluorine, it can be said that the separation and insertion of lithium ions near fluorine occur smoothly. Therefore, when used in a secondary battery, the charge and discharge characteristics, high current characteristics, etc. can be improved. In addition, by having fluorine in the surface portion of the surface including the portion in contact with the electrolyte, the corrosion resistance to hydrofluoric acid can be effectively improved.

[0111] Here, when the melting point of fluorine compounds such as lithium fluoride (sometimes also referred to as fluorides) is lower than the melting points of other additive element sources, the fluorine compounds can be used as fluxes (also referred to as solvents) to lower the melting points of other additive element sources. 2 When Figure 4 (Cited and modified from Non-Patent Document 6, Figure 5 ) as shown, LiF and MgF 2 The eutectic point P of is around 742°C (T1), so in the heating step after mixing and adding the elements, the heating temperature is preferably 742°C or higher.

[0112] Here, use Figure 5 The results of differential scanning calorimetry (DSC measurement) performed on fluorinated compounds and mixtures are described. Figure 5 This is a graph of heat flow relative to temperature. The mixture is a mixture of lithium cobalt oxide and fluoride. LiF and MgF are used as fluoride.2 More specifically, as the mixture, LiCoO 2 :LiF:MgF 2 =100:0.33:1 (molar ratio) and mixed. Figure 5 The fluorides in the 2 Specifically, as the fluoride, LiF:MgF 2 =1:3 (molar ratio) and mixed.

[0113] like Figure 5 As shown in FIG. 1 , an absorption peak is observed in the fluoride at around 735°C. In addition, an endothermic peak is observed in the mixture at around 830°C. Therefore, the heating temperature after mixing and adding the elements is preferably 742°C or higher, more preferably 830°C or higher. In addition, the temperature may be between 800°C and 900°C. Figure 4 T2) or above.

[0114] <Titanium> It is known that titanium oxide, one of the added elements, has super hydrophilicity. Therefore, by manufacturing the positive electrode active material 100 containing titanium oxide in the surface layer, it sometimes has good wettability to a solvent with high polarity. When manufacturing a secondary battery, the positive electrode active material 100 has good contact with the interface of the electrolyte with high polarity, and sometimes the increase of internal resistance can be suppressed.

[0115] <Distribution of added elements> like FIG. 6A to FIG. 6C As shown, the detection intensity of at least magnesium and nickel in the surface part of the added elements is preferably greater than the detection intensity of the inner part 100b. Furthermore, it is preferred that a detection intensity peak with a narrow width is present in a region closer to the surface in the surface part. For example, it is preferred that a detection intensity peak is present in a region within 3nm from the surface or the reference point. In addition, the distributions of magnesium and nickel are preferably overlapped. It is also possible to have detection intensity peaks of magnesium and nickel at the same depth, and the peak of magnesium may be closer to the surface side, such as Figure 6B The nickel peak shown may also be closer to the surface side. The depth difference between the nickel detection intensity peak and the magnesium detection intensity peak is preferably within 3nm, more preferably within 1nm. In addition, the detection intensity of the inner part 100b of nickel is sometimes very small or undetectable compared to the surface part.

[0116] Although not shown in the figure, the detection intensity of the surface portion of fluorine is preferably greater than the detection intensity of the internal portion, as with magnesium or nickel. It is preferred that a detection intensity peak is present in an area closer to the surface in the surface portion. For example, it is preferred that a detection intensity peak is present in an area within 3 nm from the surface or a reference point. Similarly, the detection intensity of the surface portion of titanium, silicon, phosphorus, boron and / or calcium is preferably greater than the detection intensity of the internal portion. In addition, it is preferred that a detection intensity peak is present in an area closer to the surface in the surface portion. For example, it is preferred that a detection intensity peak is present in an area within 3 nm from the surface or a reference point.

[0117] Among the added elements, at least aluminum preferably has a detection intensity peak closer to the interior than magnesium. Fig. 6A The distributions of magnesium and aluminum shown can overlap, e.g. Figure 6C The distributions of magnesium and aluminum shown in the figure may have almost no overlap. The detection intensity peak of aluminum may exist in the surface part or in a region deeper than the surface part. For example, it is preferred that there is a peak in a region with a depth of 5 nm or more and 30 nm or less from the surface or reference point to the inside.

[0118] In addition, the distribution of aluminum is sometimes not normally distributed. For example, in the case of Al When the distribution of aluminum is segmented, the tail length sometimes differs between the surface side and the inner side. More specifically, if Figure 7B As shown in the figure, when the maximum value (Max Al )1 / 5 of the height (1 / 5Max Al ) is divided into two, the inner peak width W c Sometimes the peak width W is greater than the peak width W on the surface side. s big.

[0119] Thus, it is considered that aluminum diffuses deeper into the interior than magnesium because the diffusion rate of aluminum is greater than that of magnesium. On the other hand, it is inferred that the aluminum detection intensity is low in the area closest to the surface because aluminum exists more stably in the area other than the area where magnesium or the like is solid-dissolved at a high concentration than in the area where magnesium or the like is solid-dissolved at a high concentration.

[0120] In more detail, compared with the layered rock salt type LiAlO 2 In contrast, in the layered rock salt type or cubic rock salt type region of space group R-3m, where magnesium is dissolved in a high concentration, the distance between cations and oxygen is longer, so aluminum is difficult to exist stably. 3+ Become Co 2+ To make up for Li + Substituted with Mg 2+ However, Al can only take a trivalent state, so it is considered difficult for Al and magnesium to coexist in a rock salt type or layered rock salt type structure.

[0121] Although not shown in the figure, manganese preferably has a peak with detection intensity closer to the inside than magnesium.

[0122] Note that it is not necessary that the added element has the same concentration gradient or distribution throughout the entire surface layer of the positive electrode active material 100. As an example of the depth direction of the (001) surface of lithium cobalt oxide of the positive electrode active material 100, Fig. 7A An example of distribution of added elements is shown.

[0123] The distribution of the added elements in the region with a surface having a (001) orientation may also be different from that in the region with other surfaces. For example, the detection intensity of one or more of the selected added elements in the region having the (001) surface may also be lower than that in the surface other than the (001) surface. Specifically, the detection intensity of nickel may also be low. Alternatively, the detection intensity peaks of one or more of the selected added elements in the region having a surface having a (001) orientation may also be shallower from the surface than that in the region having a surface other than the (001) surface. Specifically, the detection intensity peaks of magnesium and aluminum in the region having a surface other than the (001) surface are shallower from the surface.

[0124] In the layered rock salt type crystal structure belonging to R-3m, the cations are arranged parallel to the (00l) plane. This can be said to be caused by CoO 2 The layers and lithium layers are parallel to the (00l) plane and are alternately stacked. Therefore, the diffusion path of lithium ions is also parallel to the (00l) plane. On the other hand, CoO 2 The layer is relatively stable, so it is relatively stable when the surface of the positive electrode active material 100 is oriented in the (001) direction. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) surface.

[0125] Furthermore, the diffusion path of lithium ions is exposed on the surfaces other than the (001) surface. The surfaces and surface portions other than the (001) surface are important areas for maintaining the diffusion path of lithium ions and are the areas where lithium ions are first separated, so they tend to be unstable. Therefore, in order to maintain the overall crystal structure of the positive electrode active material 100, it is very important to strengthen the surfaces and surface portions other than the (001) surface.

[0126] Therefore, in the positive electrode active material 100, the distribution of the additional element in the region having a plane other than the (001) plane is preferably FIG. 6A to FIG. 6C Among the additive elements, nickel is preferably detected in a region having a surface other than the (001) surface. On the other hand, the concentration of the additive element in the region having the (001) surface may be as low as described above.

[0127] For example, the half width of the distribution of magnesium in the region having the (001) plane is preferably 10 nm or more and 200 nm or less, more preferably 50 nm or more and 150 nm or less, and further preferably 80 nm or more and 120 nm or less. In addition, the half width of the distribution of magnesium in the region having the (001) plane is preferably more than 200 nm and 500 nm or less, more preferably more than 200 nm and 300 nm or less, and further preferably 230 nm or more and 270 nm or less.

[0128] The half width of nickel distribution in the region having the (001) plane is preferably 30 nm to 150 nm, more preferably 50 nm to 130 nm, and even more preferably 70 nm to 110 nm.

[0129] In the following embodiment, when producing high purity LiCoO 2 In the manufacturing method of mixing the additive element and then heating, the additive element diffuses mainly through the diffusion path of lithium ions. Therefore, the distribution of the additive element in the region having a plane other than the (001) plane is likely to be within a preferred range.

[0130] <Crystal Structure> <Li x CoO 2 When x is 1> exist Figure 8 Li x CoO 2 The crystal structure of lithium cobalt oxide with x=1 in FIG. Li x CoO 2 When x=1, it is a discharge state. In the discharge state, the positive electrode active material 100 preferably has a layered rock salt type crystal structure belonging to the space group R-3m. The inner part 100b that occupies most of the volume of the positive electrode active material 100 preferably has a layered rock salt type crystal structure. In the layered rock salt type crystal structure, lithium occupies an octahedral site and includes three CoO 2 layer, so this crystal structure is sometimes called O3 type crystal structure (denoted as O3 in the figure). Note that CoO 2 The layer refers to a structure in which an octahedral structure in which cobalt is coordinated to six oxygens is continuous on one plane in a state of edge sharing. This structure is sometimes referred to as a layer composed of octahedrons of cobalt and oxygen.

[0131] The surface layer portion of the positive electrode active material 100 preferably strengthens the layered structure composed of octahedrons of transition metal M and oxygen in the interior 100b even when lithium is detached from the positive electrode active material 100 due to charging, so as to prevent the collapse of the layered structure. Alternatively, the surface layer portion is preferably used as a barrier film for the positive electrode active material 100. Alternatively, the surface layer portion of the outer peripheral portion of the positive electrode active material 100 preferably strengthens the positive electrode active material 100. Here, strengthening means suppressing the structural changes in the surface layer portion and the interior 100b of the positive electrode active material 100 such as the detachment of oxygen and / or suppressing the oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.

[0132] Thus, the surface layer portion may also have a crystal structure different from that of the interior 100b. For example, at least a part of the surface layer portion of the positive electrode active material 100 may have a rock salt-type crystal structure. Alternatively, the surface layer portion may also have both a layered rock salt-type crystal structure and a rock salt-type crystal structure.

[0133] <Li x CoO 2 in a state where x is small> The positive electrode active material 100 is different from the conventional positive electrode active material in that it has a crystal structure in a state where x in x CoO 2 is small. Note that here, x being small means 0.1 < x ≤ 0.24, and as an example, x = 0.12 or x = 0.2 is sometimes used. The conventional positive electrode active material refers to lithium cobaltate that does not contain additive elements.

[0134] Conventional lithium cobaltate has a crystal structure belonging to the space group R-3m when x is around 0.12. It can also be said that this structure is a structure in which a CoO 2 structure such as a trigonal crystal O1 type structure and a LiCoO 2 structure such as belonging to R-3m (O3) are alternately stacked. Thus, this crystal structure is sometimes referred to as an H1-3 type crystal structure. In fact, the number of cobalt atoms in the unit cell of the H1-3 type crystal structure is twice that of other structures. However, in this specification such as Figure 8 etc., for the sake of easy comparison with other crystal structures, the c-axis of the H1-3 type structure is 1 / 2 of the unit cell.

[0135] As an example of an H1-3 type crystal structure, the coordinates of cobalt and oxygen in the unit cell can be represented by Co (0, 0, 0.42150 ± 0.00016), O1 (0, 0, 0.27671 ± 0.00045), and O2 (0, 0011535 ± 0.00045). O1 and O2 are both oxygen atoms. For example, by performing a Rietveld analysis of an XRD pattern, it can be determined which unit cell is used to represent the crystal structure of the positive electrode active material. At this time, a unit cell with a small GOF (goodness of fit) value can be used.

[0136] Thus, when charging and discharging are repeated with x being less than 0.24, the existing lithium cobalt oxide repeatedly changes dynamically between the H1-3 type crystal structure and the R-3m O3 structure in the discharge state (i.e., non-equilibrium phase transition), which has a negative impact on the stability of the crystal structure.

[0137] Therefore, when charging and discharging are repeated until x becomes less than 0.24, the crystal structure of the existing lithium cobalt oxide collapses. The collapse of the crystal structure will cause the deterioration of the cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably, and the insertion and extraction of lithium become difficult.

[0138] On the other hand, when the conventional lithium cobalt oxide has an H1-3 type crystal structure, that is, when x is less than 0.24, for example, about 0.2, Figure 8 The positive electrode active material 100 shown has a crystal structure different from the above structure. The positive electrode active material 100 when x=0.2 has a crystal structure belonging to the space group R-3m of the trigonal system. CoO 2 The symmetry of the layer is the same as that of O3. Therefore, this crystal structure is called O3' type crystal structure. Because this crystal structure belongs to the space group R-3m, Figure 8 R-3m O3' is attached in. In addition, this crystal structure is not a spinel structure, but sometimes a pattern similar to the spinel structure appears in the XRD pattern, and this crystal structure is sometimes called a pseudo-spinel structure.

[0139] The coordinates of cobalt and oxygen in the unit cell of the O3' type crystal structure can be represented by Co(0, 0, 0.5) and O(0, 0, x) respectively, and are within the range of 0.20≤x≤0.25. In addition, the lattice constant of the unit cell is as follows: the a-axis is preferably 2.797≤a≤2.837(×10 -1 nm), more preferably 2.807≤a≤2.827(×10 -1 nm), typically a=2.817(×10 -1 The c-axis is preferably 13.681≤c≤13.881(×10 -1nm), more preferably 13.751≤c≤13.811, typically c=13.781(×10 -1 nm).

[0140] In addition, when x=0.15, the positive electrode active material 100 of one embodiment of the present invention has a monoclinic crystal structure belonging to the space group P2 / m. In the unit cell of this structure, there is one CoO 2 layer. In addition, the amount of lithium present in the positive electrode active material 100 at this time is about 15 atomic% in the discharge state. Therefore, this crystal structure is called a monoclinic O1(15) type crystal structure. Figure 8 The crystal structure is represented by P2 / m monoclinic O1(15).

[0141] In the monoclinic O1(15) crystal structure, the coordinates of cobalt and oxygen in the unit cell can be expressed as follows: Co1(0.5,0,0.5), Co2(0,0.5,0.5), O1(X(O1), 0, Z(O1)), 0.23≤X(O1)≤0.24, 0.61≤Z(O1)≤0.65, O2(X(O2), 0.5, Z(O2)), 0.75≤X(O2)≤0.78, 0.68≤Z(O2)≤0.71. In addition, the lattice constants of the unit cell are as follows: a=4.880±0.05(×10 -1 nm), b=2.817±0.05(×10 -1 nm), c=4.839±0.05(×10 -1 nm), α=90°、 β=109.6±0.1°、 γ=90°.

[0142] This crystal structure can also express the lattice constant when it belongs to the space group R-3m while allowing a certain error. The coordinates of cobalt and oxygen in the unit cell can be expressed as follows: Co(0,0,0.5), O(0, 0, Z(O)), 0.21≤Z(O)≤0.23. In addition, the lattice constant of the unit cell is as follows: a=2.817±0.02(×10 -1 nm), c=13.68±0.1(×10 -1 nm).

[0143] In each of the O3' type crystal structure and the monoclinic O1(15) type crystal structure, ions of cobalt, nickel, magnesium, etc. occupy six oxygen sites. In addition, light elements such as lithium and magnesium may occupy four oxygen sites.

[0144] like Figure 8 The dashed lines in the figure show the CoO structure between the R-3m O3-type crystal structure, the O3'-type structure and the monoclinic O1(15)-type crystal structure under discharge. 2 The layers barely deviate.

[0145] The difference in volume of the same number of cobalt atoms between the R-3m O3 type crystal structure and the O3' type crystal structure in the discharged state is 2.5% or less, more specifically 2.2% or less, and typically 1.8%.

[0146] In addition, the difference in volume of the same number of cobalt atoms between the R-3m O3 type crystal structure and the monoclinic O1(15) type crystal structure in the discharged state is 3.3% or less, more specifically 3.0% or less, and typically 2.5%.

[0147] Thus, in the positive electrode active material 100 of one embodiment of the present invention, Li x CoO 2 When x is smaller, that is, when more lithium is released, the change in the crystal structure is suppressed compared with the existing positive active material. In addition, the change in volume when compared with the same number of cobalt atoms is also suppressed. Therefore, the crystal structure of the positive active material 100 is not easy to collapse even if x is repeatedly charged and discharged below 0.24. Therefore, the decrease in the discharge capacity of the positive active material 100 caused by the charge and discharge cycle is suppressed. In addition, a larger amount of lithium can be stably embedded and released than the existing positive active material, so the discharge capacity per unit weight and unit volume of the positive active material 100 is larger. Therefore, by using the positive active material 100, a secondary battery with a higher discharge capacity per unit weight and unit volume can be manufactured.

[0148] In addition, it was confirmed that the positive electrode active material 100 x CoO 2 When x in θ is 0.15 or more and 0.24 or less, it may have an O3' type crystal structure. And it is considered that it also has an O3' type crystal structure when x exceeds 0.24 and is 0.27 or less.

[0149] However, in addition to Li x CoO2 In addition to x in Li, it is also affected by the number of charge and discharge cycles, charge and discharge current, temperature, electrolyte, etc., so it is not limited to the above range of x. x CoO 2 When x exceeds 0.1 and is equal to or less than 0.24, the interior 100b of the positive electrode active material 100 does not need to be entirely of the O3' type crystal structure. Alternatively, it may have other crystal structures or may be partially amorphous.

[0150] In addition, in order to achieve Li x CoO 2 In the case where x is small, it is generally necessary to charge with a high charging voltage. x CoO 2 The state in which x is smaller is called a state of charging at a high charging voltage. For example, when CC / CV charging is performed at a voltage of 4.6V or more based on the potential of lithium metal in an environment of 25°C, an H1-3 type crystal structure is presented in the existing positive electrode active material. Therefore, it can be said that a charging voltage of 4.6V or more based on the potential of lithium metal is a high charging voltage. In addition, in this specification, unless otherwise specified, the charging voltage is expressed based on the potential of lithium metal.

[0151] The positive electrode active material 100 sometimes has H1-3 type crystals only when the charging voltage is further increased. In addition, as described above, the crystal structure is affected by the number of charge and discharge cycles, the charge and discharge current, the electrolyte, etc., so when the charging voltage is lower, for example, even at 25°C and the charging voltage is 4.5V or more and less than 4.6V, the positive electrode active material 100 of one embodiment of the present invention sometimes has an O3' type crystal structure.

[0152] In addition, for example, when graphite is used as the negative electrode active material of the secondary battery, the voltage drop of the secondary battery is equivalent to the potential of the graphite. The potential of graphite is about 0.05V to 0.2V based on the potential of lithium metal. Therefore, in the secondary battery using graphite as the negative electrode active material, the same crystal structure is obtained at the voltage obtained by subtracting the potential of graphite from the above voltage.

[0153] In addition, Figure 8 In the O3' type, lithium exists at all lithium sites with equal probability, but the present invention is not limited to this. It can also exist in a concentrated manner at a part of the lithium sites. For example, it can also have a monoclinic O1 (Li 0.5 CoO 2 The distribution of lithium can be analyzed, for example, by neutron diffraction.

[0154] In addition, although the O3' type crystal structure contains lithium irregularly between the layers, it can also have the same 2 The crystal structure is similar to that of CdCl 2 The crystal structure of the type is similar to that of the nickel oxide, which is charged to become Li 0.06 NiO 2 However, it is known that pure lithium cobalt oxide or layered rock salt-type positive electrode active materials containing a large amount of cobalt generally do not have CdCl 2 Type crystal structure.

[0155] <Analysis Method> In order to determine whether a positive electrode active material is in Li x CoO 2 The positive electrode active material 100 of one embodiment of the present invention, which has an O3'-type crystal structure when x is small, can contain Li x CoO 2 The positive electrode of the positive electrode active material having a smaller x in the graph is determined by analysis using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), or the like.

[0156] In particular, XRD is preferred because of the following advantages: the symmetry of transition metals such as cobalt contained in the positive electrode active material can be analyzed with high resolution; the height of crystallinity and the orientation of crystallinity can be compared; the periodic distortion of the lattice and the grain size can be analyzed; sufficient accuracy can be obtained when directly measuring the positive electrode obtained by disassembling a secondary battery, etc. Through XRD, especially powder XRD, a diffraction peak reflecting the crystal structure of the interior 100b of the positive electrode active material 100 that occupies most of the volume of the positive electrode active material 100 can be obtained.

[0157] When analyzing the crystal size by powder XRD, it is preferable to perform the measurement without affecting the orientation due to pressure, etc. For example, it is preferable to take out the positive electrode active material from the positive electrode obtained by disassembling the secondary battery as a powder sample for measurement.

[0158] Note that sometimes the positive electrode active material in a state where x is small changes its crystal structure when exposed to air. For example, sometimes it changes from an O3' type crystal structure to an H1-3 type crystal structure. Therefore, all samples used in analyzing the crystal structure are preferably handled in an inert atmosphere such as an argon atmosphere.

[0159] < <xrd>> As long as there is appropriate adjustment and calibration, there is no limitation on the apparatus and conditions for XRD measurement. For example, the following apparatus can be used for measurement under the following conditions. XRD device: D8 ADVANCE manufactured by Bruker AXS X-ray source: Cu(CuKα 1 ray) Output: 40kV, 40mA Emission angle: Div. Slit, 0.5° Detector: LynxEye Scanning mode: 2θ / θ continuous scanning Measuring range (2θ): 15° to 90° Step width (2θ): set to 0.01° Counting time: 1 second / step Sample stage rotation: 15rpm As a standard sample for adjustment and calibration, for example, a standard sintered alumina plate SRM 1976 of NIST (National Institute of Standards and Technology) or the like can be used.

[0160] When the sample to be measured is a powder, the sample can be mounted by placing it in a glass sample holder, or by sprinkling the sample on a silicon non-reflective plate coated with grease, etc. When the sample to be measured is a positive electrode, the positive electrode active material layer can be mounted according to the measurement surface required by the device by attaching the positive electrode to the substrate with double-sided tape.

[0161] The monochromatization of characteristic X-rays can be performed using a filter or the like, or using XRD data analysis software after obtaining the XRD pattern. For example, DEFFRAC.EVA (XRD data analysis software manufactured by Bruker) can be used to remove the CuKα 2 The peak of the ray is extracted only through CuKα 1 In addition, the software can also be used to remove background, etc.

[0162] In this specification, etc., when the 2θ value of a certain diffraction peak is mentioned, it means the 2θ value of the peak top of the diffraction peak that appears in the XRD pattern after fitting the calculation model. There is no particular limitation on the crystal structure analysis software used for fitting, for example, TOPASver.3 (crystal structure analysis software manufactured by Bruker) can be used.

[0163] Fig. 9 The XRD patterns of the O3 type crystal structure, the O3' type crystal structure, and the monoclinic O1(15) type crystal structure when CuKα1 is used as the radiation source are shown. Fig.10 The CuKα calculated from the model of the H1-3 type crystal structure is shown. 1 The ideal powder XRD pattern obtained by X-ray and the CuKα 1 The ideal XRD pattern obtained by X-ray. Fig.11A and Fig. 11B All of the above XRD patterns are shown. Note that in the drawings, the range of 2θ is 18° or more and 21° or less, and the range of 2θ is 42° or more and 46° or less. LiCoO 2 (O3) and CoO 2 The pattern (O1) was made by using the crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) using Reflex Powder Diffraction, one of the modules of Materials Studio (BIOVIA). At this time, the range of 2θ was set to 15° to 75°, Step size = 0.01, and wavelength λ = 1.54×10 -10 The patterns of the O3′ type crystal structure and the monoclinic O1(15) type crystal structure were prepared by inferring the crystal structure from the XRD pattern of the positive electrode active material 100 and fitting it using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker).

[0164] like Fig. 9 , Fig.11A and Fig. 11B As shown, in the O3' type crystal structure, at 2θ of 19.25±0.12° (19.13° or more and less than 19.37°) and at 2θ of 45.47±0.10° A diffraction peak appears at (45.37° or more and less than 45.57°).

[0165] In addition, in the monoclinic O1(15) type crystal structure, at 2θ of 19.47±0.10° Diffraction peaks appear at (19.37° or more and 19.57° or less) and at 2θ of 45.62±0.05° (45.57° or more and 45.67° or less).

[0166] However, if Fig.10 , Fig.11A and Fig. 11B As shown, in the H1-3 type crystal structure and the trigonal crystal O1, the peak does not appear at the above position. x CoO 2 The presence of peaks at 19.13° to less than 19.37° and / or 19.37° to 19.57° and at 45.37° to less than 45.57° and / or 45.57° to 45.67° in a state where x is small is characteristic of the positive electrode active material 100 .

[0167] This also indicates that: the position of the XRD diffraction peak appearing in the crystal structure when x=1 is close to the position of the XRD diffraction peak appearing in the crystal structure when x≤0.24; more specifically, regarding the peaks in the main diffraction peaks of the crystal structure when x=1 and the crystal structure when x≤0.24, the 2θ difference between the peaks appearing at 42° or more and 46° or less is less than 0.7°, preferably less than 0.5°.

[0168] In addition, the positive electrode active material 100 is in Li x CoO 2 When x is small, it has an O3' type crystal structure and / or a monoclinic O1(15) type crystal structure, but it is not necessary for all particles to have the O3' type crystal structure and / or the monoclinic O1(15) type crystal structure. It can have other crystal structures and can also be partially amorphous. Note that when performing Rietveld analysis on the XRD pattern, the O3' type crystal structure and / or the monoclinic O1(15) type crystal structure preferably accounts for more than 50%, more preferably more than 60%, and further preferably more than 66%. When the O3' type crystal structure and / or the monoclinic O1(15) type crystal structure accounts for more than 50%, more preferably more than 60%, and further preferably more than 66%, a positive electrode active material with sufficiently excellent cycle characteristics can be achieved.

[0169] Furthermore, even after 100 or more charge-discharge cycles from the start of measurement, the O3' type crystal structure and / or the monoclinic O1(15) type crystal structure in the Rietveld analysis preferably accounts for 35% or more, more preferably 40% or more, and further preferably 43% or more.

[0170] In addition, when the Rietveld analysis is similarly performed, the H1-3 type crystal structure and the O1 type crystal structure preferably account for 50% or less. Alternatively, the crystal structure more preferably accounts for 34% or less. Alternatively, the structure is more preferably not substantially observed.

[0171] In addition, the sharpness of the diffraction peak in the XRD pattern indicates the height of crystallinity. Therefore, each diffraction peak after charging is preferably sharp, that is, the half width (e.g., half maximum full width) is preferably narrow. The half width of the peak of the same crystalline phase varies according to the measurement conditions of XRD and / or the value of 2θ. When the above-mentioned measurement conditions are adopted, for example, the half maximum full width of the peak observed at 2θ of 43° or more and 46° or less is preferably 0.2° or less, more preferably 0.15° or less, and further preferably 0.12° or less. Note that it is not necessary for all peaks to meet the above conditions. As long as a part of the peaks meet the above conditions, it can be said that the crystallinity of its crystalline phase is higher. The above-mentioned higher crystallinity fully contributes to the stabilization of the crystal structure after charging.

[0172] In addition, the grain size of the O3′ type crystal structure and the monoclinic O1(15) type crystal structure of the positive electrode active material 100 is reduced to only the LiCoO 2 Therefore, even under the same XRD measurement conditions as the positive electrode before charge and discharge, it is possible to x CoO 2 When x in is small, obvious peaks of O3' type crystal structure and / or monoclinic O1(15) type crystal structure are confirmed. 2 A portion of the crystal structure may have a structure similar to the O3' type crystal structure and / or the monoclinic O1(15) type crystal structure, the grain size may become smaller, and the peak may become wider and smaller.

[0173] <Grain size> The grain size can be obtained from, for example, the following Scherrer formula.

[0174] [Formula 1]

[0175] In addition, when calculating the crystallite size, all diffraction peaks detected in the range of 2θ being 15° or more and 90° or less may be used. It is preferred that the crystallite size of each diffraction peak be calculated and then corrected and calculated as an average value of the crystallite size.

[0176] The XRD diffraction pattern used when calculating the grain size is preferably obtained in a state where there is only a positive electrode active material, but it can also be obtained in a state where the positive electrode also includes a current collector, a binder, and a conductive material in addition to the positive electrode active material. Note that in the positive electrode state, the particles of the positive electrode active material may be affected by the pressurization in the manufacturing process and oriented in a manner where the crystal planes of the particles of the positive electrode active material are consistent in one direction. When the degree of orientation is large, it may not be possible to accurately calculate the grain size, so it is more preferable to obtain the XRD diffraction pattern by the following method: remove the positive electrode active material layer from the positive electrode, use a solvent to remove the binder in the positive electrode active material layer to a certain extent, and fill it into a sample holder, etc. In addition, there is also the following method: apply grease on a silicon non-reflective plate to attach a powder sample of the positive electrode active material to the silicon non-reflective plate.

[0177] In the calculation of grain size, for example, the following can be used: ADVANCE, using CuKα as X-ray source 1 , 2θ is greater than 15° and less than 90°, increment is 0.005, and the detector is LYNXEYE XE-T; and ICSD coll.code.172909 is the literature value of lithium cobalt oxide. This literature value can be used for correction. DIFFRAC.TOPAS ver.6 can be used as a crystal structure analysis software for analysis, for example, the following settings can be used. It is preferred to use the LVol-IB value of the grain size as the grain size. Note that when the calculated Preferred Orientation is less than 0.8, it is sometimes not suitable for calculating the grain size because the sample is too oriented.

[0178] <Charging method> As charging for determining whether the composite oxide is the positive electrode active material 100 of one embodiment of the present invention, for example, a coin battery (CR2032 type, 20 mm in diameter, 3.2 mm in height) of a lithium counter electrode can be manufactured and charged.

[0179] More specifically, as the positive electrode, a positive electrode obtained by applying a slurry obtained by mixing a positive electrode active material, a conductive material, and a binder to a positive electrode current collector of an aluminum foil can be used.

[0180] Lithium metal can be used as the counter electrode. Note that the potential of the positive electrode when a material other than lithium metal is used as the counter electrode is different from that of the secondary battery. Unless otherwise specified, the voltage and potential in this specification and the like refer to the potential of the positive electrode.

[0181] As the electrolyte in the electrolyte solution, 1 mol / L lithium hexafluorophosphate (LiPF 6 ), an electrolyte prepared by adding 2 wt % of vinylene carbonate (VC) to a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7 was used as the electrolyte.

[0182] As the separator, a polypropylene porous film having a thickness of 25 μm can be used.

[0183] The positive electrode can and the negative electrode can may be formed of stainless steel (SUS).

[0184] The coin-type battery manufactured under the above conditions is charged to any voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V). There is no restriction on the charging method as long as it can be charged to any voltage in sufficient time. For example, when charging with CCCV, the current in CC charging can be set to be greater than 20mA / g and less than 100mA / g. CV charging can be performed until it is greater than 2mA / g and less than 10mA / g. In order to observe the phase change of the positive electrode active material, it is preferred to charge with the above-mentioned smaller current value. The temperature is set to 25°C or 45°C. After charging in this manner, the coin-type battery is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, thereby obtaining a positive electrode active material of any charging capacity. When various analyses are performed later, in order to prevent reaction with external components, it is preferably sealed under an argon atmosphere. For example, XRD can be performed in a sealed container sealed in an argon atmosphere. In addition, it is preferred to take out the positive electrode and analyze it immediately after charging is completed. Specifically, it is preferred to analyze it within 1 hour after charging is completed, and more preferably within 30 minutes after charging is completed.

[0185] In addition, when analyzing the crystal structure of the charged state after multiple charge and discharge, the multiple charge and discharge conditions may also be different from the above-mentioned charging conditions. For example, charging can be performed at a current value of 20 mA / g or more and 100 mA / g or less to any voltage (for example, 4.6 V, 4.65 V, 4.7 V, 4.75 V or 4.8 V), and then constant voltage charging is performed until the current value reaches 2 mA / g or more and 10 mA / g or less, and discharging can be performed at a constant current of 20 mA / g or more and 100 mA / g or less to 2.5 V.

[0186] When analyzing the crystal structure in a discharged state after multiple charge and discharge, for example, constant current discharge to 2.5 V may be performed at a current value of 20 mA / g or more and 100 mA / g or less.

[0187] <Powder resistance measurement> The powder volume resistivity of the positive electrode active material 100 will be described below.

[0188] The powder volume resistivity of the positive electrode active material 100 is preferably 1.0×10 3 Ω·cm or more, more preferably 4.0×10 3 Ω·cm or more. In the positive electrode active material 100, the added element is distributed in the first region 100s at a preferred concentration, so the above value is achieved. In other words, the volume resistivity can be used as an indicator indicating that the first region 100s can be well formed. The positive electrode active material 100 having the above volume resistivity has a stable crystal structure even at a high voltage, and it can be said that the crystal structure of the positive electrode active material is stable in the charged state.

[0189] However, when a thicker high resistance region exists from the surface to the inside of the positive electrode active material 100, the battery reaction may be blocked. Therefore, it is more preferred that only the thinner region near the surface such as the first region 100s actually has high resistance. The first region 100s preferably exists in a region within 20nm from the surface to the inside in a direction perpendicular or substantially perpendicular to the surface, preferably within 10nm, more preferably within 5nm, etc., that is, thinner. Therefore, the first region 100s is sometimes thinner than the surface portion.

[0190] In addition, when the volume resistivity is too high, the charge-discharge cycle characteristics may be insufficient. Therefore, the powder volume resistivity of the positive electrode active material 100 is preferably 1×10 12 Note that when CNT is used as the conductive material, the powder volume resistivity of the positive electrode active material 100 can be 1×10 13 Since the CNT can fully ensure the conductive path, even with the above volume resistivity, good charge and discharge cycle characteristics can be achieved.

[0191] A battery including the positive electrode active material 100 having such a volume resistivity can be a secondary battery that is less likely to catch fire in an internal short circuit test such as a needle penetration test, and can also exhibit good characteristics in a charge and discharge cycle test under high voltage conditions.

[0192] A method for measuring the powder volume resistivity of the positive electrode active material 100 according to one embodiment of the present invention will be described.

[0193] The measurement of the bulk volume resistivity preferably includes a first mechanism having terminals for resistance measurement and a second mechanism for applying pressure to a powder sample (the sample) to be measured. The second mechanism preferably includes a cylinder for placing the powder sample and a piston that can move up and down within the cylinder. The piston is connected to a spring or the like to apply pressure to the sample within the cylinder. The first mechanism preferably includes a measurement electrode that contacts the bottom surface of the cylinder. As such a measurement device including terminals for resistance measurement and a mechanism for applying pressure to the powder to be measured, for example, MCP-PD51 manufactured by Mitsubishi Chemical Analytech Co., Ltd. can be used. As the resistance meter, Loresta-GP or Hiresta-UP can be used. Loresta-GP can be used in the measurement of low-resistance samples by the four-probe method, and Hiresta-UP can be used in the measurement of high-resistance samples by the two-probe method. Note that as the measurement environment, a stable environment such as a drying chamber is preferably adopted, but a general laboratory environment can also be adopted. As the drying chamber environment, for example, an environment with a temperature of 20°C or higher and 25°C or lower and a dew point of -40°C or lower is preferred. As a general laboratory environment, it can also be an environment with a temperature of 15°C or higher and 30°C or lower and a humidity of 30% or higher and 70% or lower.

[0194] Describe the measurement of the bulk volume resistivity using the above measurement device. In the measurement of the bulk volume resistivity, the resistance of the powder and the thickness of the powder are measured while the powder is under pressure. The powder can be pressurized under various conditions. For example, the resistance and thickness of the powder are measured under each pressure condition of 13 MPa, 25 MPa, 38 MPa, 51 MPa, and 64 MPa. The bulk volume resistivity can be calculated based on the measured values of the resistance and thickness of the powder.

[0195] Describe the calculation method of the volume resistivity. When measuring by the two-probe method using Hiresta-UP, the volume resistivity is obtained by multiplying the resistance of the powder by the area of the electrode applying pressure to the powder and then dividing by the thickness of the powder. Additionally, when measuring by the four-probe method using Loresta-GP, the volume resistivity is obtained by multiplying the resistance of the powder by the correction factor and then dividing by the thickness of the powder. The correction factor is a value that varies according to the sample shape, size, and measurement position and can be obtained using the operation software built into Loresta-GP.

[0196] <X-ray Photoelectron Spectroscopy (XPS)> When analyzing inorganic oxides and using monochromated aluminum Kα rays as the X-ray source, XPS can analyze the depth range of about 2nm to 8nm (generally less than 5nm) from the surface, so the concentration of each element in about half of the depth direction of the surface can be quantitatively analyzed. In addition, by performing narrow scan analysis, the bonding state of the elements can be analyzed.

[0197] In the positive electrode active material 100 of one embodiment of the present invention, the concentration of one or more selected from the added elements in the surface part or the first region 100s is preferably higher than that in the interior 100b. This means that the concentration of one or more selected from the added elements in the surface part or the first region 100s is preferably higher than the average concentration of the positive electrode active material 100 as a whole. Therefore, for example, it can be said that the concentration of one or more added elements measured by XPS or the like is preferably higher than the average concentration of the added elements of the positive electrode active material 100 as a whole measured by ICP-MS or GD-MS or the like. The average concentration of the overall added element includes the average value of the added element concentration of the surface part and the added element concentration of the interior. For example, the magnesium concentration measured by XPS or the like is preferably higher than the average magnesium concentration of the positive electrode active material 100 as a whole. In addition, the nickel concentration measured by XPS or the like is preferably higher than the average nickel concentration of the positive electrode active material 100 as a whole. In addition, the aluminum concentration measured by XPS or the like is preferably higher than the average aluminum concentration of the positive electrode active material 100 as a whole. In addition, the fluorine concentration measured by XPS or the like is preferably higher than the average fluorine concentration of the positive electrode active material 100 as a whole.

[0198] For example, when the positive electrode active material 100 is analyzed by XPS, the ratio of the atomic number ratio of cobalt to the atomic number ratio of magnesium (this ratio may also be expressed as an existence ratio, expressed as A Mg / A Co ) is preferably greater than 0, specifically, preferably 0.8 to 1.4, more preferably 0.9 to 1.3, and even more preferably 1.0 to 1.2. For example, the ratio of the number of atoms of cobalt to the number of atoms of nickel (A Ni / A Co ) is preferably greater than 0, preferably greater than 0.07 and less than 0.15, more preferably greater than 0.08 and less than 0.13, and further preferably greater than 0.09 and less than 0.11. For example, the ratio of the number of atoms of cobalt to the number of atoms of fluorine (A F / A Co ) is preferably greater than 0, preferably greater than 0.5 and less than 1.0, more preferably greater than 0.6 and less than 0.9, and further preferably greater than 0.7 and less than 0.8. In addition, it is preferred that the above ratio is within the above range in multiple parts, for example, three or more parts, of the positive electrode active material 100.

[0199] <edx> The concentration of the added element in the positive electrode active material 100 can be analyzed by exposing the cross section of the positive electrode active material 100 by, for example, FIB (Focused Ion Beam) or the like and analyzing the cross section by energy dispersive X-ray spectroscopy (EDX), EPMA (electron probe microanalysis), etc. In many cases, the EDX analysis device is included in the SEM device or the STEM device, which are respectively referred to as SEM-EDX measurement or STEM-EDX measurement.

[0200] In EDX measurement, the method of measuring and evaluating while irradiating an electron beam and performing linear scanning is called line analysis. In addition, the method of measuring while irradiating an electron beam and scanning a point or an arbitrary area is called point analysis. Point analysis can be measured with an area larger than line analysis as the object, so it is preferred when quantifying trace elements in a certain area. In any of the above analyses, the concentration of each element can be calculated as a quantitative value. In addition, the energy spectrum of each element can be obtained in any of the above measurements. When the concentration of each element is small, it is preferably combined with the energy spectrum for evaluation.

[0201] The method for obtaining the quantitative value of an element measured by STEM-EDX is described below. First, a positive electrode active material that has been processed by FIB is prepared as a sample, and a cross-sectional STEM image is obtained using a STEM device. When a certain area is subjected to STEM-EDX line analysis with reference to the cross-sectional STEM image, a graph can be obtained in which the horizontal axis represents the distance (nm) and the vertical axis represents the detection amount (detection intensity or count) or the quantitative value (atomic%) of the characteristic X-ray. The quantitative value is obtained based on the detection intensity. When obtaining the quantitative value of an element, a graph of the quantitative value (atomic%) is used on the vertical axis. In addition, when quantifying the concentration of an element according to the surface and interior of the positive electrode active material, it is necessary to specify reference points such as the surface position. At this time, the average value M of the detection intensity inside cobalt is taken as AVE The average value of the detection intensity with background M BG The point where 50% of the sum of the detected intensities or the average value of the detected intensities of the oxygen inside AVE The average value of the background BG The point where the sum is 50% is called the above-mentioned reference point or surface. The surface layer and the interior can be specified based on the reference point or the distance from the surface. Note that when the reference point obtained from the above-mentioned cobalt is different from the reference point obtained from oxygen, it can be considered that it is affected by metal oxides, carbonates, etc. containing oxygen attached to the surface. Therefore, the reference point obtained from the above-mentioned cobalt can be used.

[0202] The average value of the cobalt background above M BG For example, it can be obtained by averaging in a range of 2 nm or more, preferably 3 nm or more, in a region corresponding to the outer side of the active material other than the vicinity of the portion where the detection intensity of cobalt starts to increase. AVE The detection intensity of cobalt and oxygen can be averaged and obtained in a region where the detection intensity of cobalt and oxygen is saturated and stable, for example, in a region of 30 nm or more, preferably 50 nm or more in the depth direction from the reference point or the surface. The average value of the background of oxygen O BG and the average value of the internal detection intensity of oxygen O AVE It can also be found in the same way.

[0203] As long as it is an element with sufficient concentration, the peak or distribution of the element is confirmed in the STEM-EDX line analysis results. On the other hand, the peak and distribution of the element are sometimes not observed in the element with trace concentration. In the element confirmed to be distributed with sufficient concentration, the value of the quantitative value (atomic%) of the vertical axis is the quantitative value of the element, and by reading the quantitative value (atomic%) of the vertical axis, the concentration range of the element can be specified. In addition, it is preferred to use STEM-EDX point analysis to compositely determine the quantitative value of the element that cannot be confirmed to be distributed due to trace concentration. Specifically, it is preferred to obtain an energy spectrum by STEM-EDX point analysis, and composite determination is performed by combining the presence of the spectral lines of the element.

[0204] For example, the case of obtaining the quantitative value of nickel, one of the added elements, is described. Here, nickel is a trace element in the surface part and / or the interior, and no clear distribution of nickel can be confirmed by STEM-EDX line analysis. At this time, refer to the energy spectrum obtained by STEM-EDX point analysis of the surface part and / or the interior. In the energy spectrum, when the energy peak of nickel is confirmed, the value of the quantitative value (atomic%) of the vertical axis is the quantitative value of nickel. In other words, the vertical axis of the chart can be read to specify the nickel concentration range. On the other hand, when the spectrum line of nickel is not confirmed, the quantitative value (atomic%) of the vertical axis can be an example of the upper limit value of the nickel concentration.

[0205] The quantitative value of each element can be obtained through the above steps.

[0206] In addition, the distribution in STEM-EDX line analysis is different from the peak. The peak in STEM-EDX line analysis refers to the maximum value of the detection intensity or concentration in the distribution of each element or the maximum value of the characteristic X-ray of each element.

[0207] For example, when EDX line analysis is performed on a positive electrode active material 100 containing magnesium as an additive element, the peak of the magnesium concentration in the surface portion preferably appears in the range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably in the range of 1nm to a depth, and further preferably in the range of 0.5nm to a depth. In addition, the magnesium concentration is preferably reduced to less than 60% of the peak at a point 1nm deep from the peak. In addition, it is preferred that the point 2nm deep from the peak is reduced to less than 30% of the peak. In addition, due to the influence of spatial resolution in EDX line analysis, the position of the peak of the magnesium concentration is sometimes negative when the depth to the inside is positive based on the surface. The quantitative value of magnesium is preferably greater than 0atomic%, preferably greater than 0.3atomic% and less than 7atomic%, and more preferably greater than 0.3atomic% and less than 5atomic%. As shown in the following examples, the quantitative value is sometimes different depending on the crystal surface.

[0208] In addition, when performing EDX line analysis, the fluorine concentration peak of the surface portion preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. In addition, the fluorine concentration peak is preferably slightly closer to the surface side than the magnesium concentration peak, and the resistance to hydrofluoric acid is improved at this time, so it is preferred. For example, the fluorine concentration peak is preferably closer to the surface side by more than 0.5nm than the magnesium concentration peak, and more preferably closer to the surface side by more than 1.5nm than the magnesium concentration peak.

[0209] In addition, in the positive electrode active material 100 containing nickel as an added element, the nickel concentration peak of the surface portion preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. Alternatively, preferably within ±1nm from the surface. In addition, in the positive electrode active material 100 containing magnesium and nickel, the distribution of nickel preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction between the nickel concentration peak and the magnesium concentration peak is preferably within 10nm, more preferably within 3nm, and further preferably within 1nm. The quantitative value of nickel is preferably greater than 0atomic%, preferably greater than 0.3atomic% and less than 3atomic%, and more preferably greater than 0.3atomic% and less than 2atomic%. As shown in the following embodiments, the quantitative value sometimes differs depending on the crystal surface.

[0210] In addition, when the positive electrode active material 100 includes aluminum as an added element, when performing EDX line analysis, the concentration peaks of magnesium, nickel or fluorine are closer to the surface than the aluminum concentration peaks of the surface layer. For example, the aluminum concentration peak preferably appears in the range of a depth of more than 0.5nm and less than 50nm from the surface of the positive electrode active material 100 to the center, and more preferably appears in the range of a depth of more than 3nm and less than 30nm. The quantitative value of aluminum is preferably greater than 0 atomic%, preferably more than 0.1 atomic% and less than 3 atomic%, and more preferably more than 0.1 atomic% and less than 2 atomic%. As shown in the following examples, the quantitative value is sometimes different depending on the crystal surface.

[0211] In addition, when EDX line analysis, surface analysis, or point analysis is performed on the positive electrode active material 100, the ratio of the atomic number ratio of magnesium to the atomic number ratio of cobalt at the peak position of magnesium (A Mg / A Co ) is preferably greater than 0 in the region including the end face, specifically, preferably greater than 0.8 and less than 1.4, more preferably greater than 0.9 and less than 1.3, and further preferably greater than 1.0 and less than 1.2. It is considered that the atomic number ratio of Mg in the region including the basal plane is smaller than that in the region including the end face. In addition, the ratio of the atomic number ratio of cobalt to the atomic number ratio of nickel at the peak position (A Ni / A Co ) is preferably greater than 0, more preferably greater than 0, more preferably greater than 0.07 and less than 0.15, further preferably greater than 0.08 and less than 0.13, further preferably greater than 0.09 and less than 0.11 in the region including the end face. It is considered that the atomic number ratio of Mg in the region including the basal plane is smaller than that in the region including the end face. In addition, the ratio of the atomic number ratio of cobalt to the atomic number ratio of fluorine (A F / A Co ) is preferably greater than 0 in the region including the end face, preferably greater than 0.5 and less than 1.0, more preferably greater than 0.6 and less than 0.9, and further preferably greater than 0.7 and less than 0.8. In addition, it is preferred that the above ratio is within the above range in multiple parts, for example, three or more parts, of the positive electrode active material 100.

[0212] For example, when the added element is magnesium, when the positive electrode active material 100 is subjected to line analysis or surface analysis, the ratio of the atomic number ratio of cobalt to the atomic number ratio of magnesium near the grain boundary (A Mg / A Co ) is preferably greater than 0.020 and less than 0.50. More preferably, it is greater than 0.025 and less than 0.30. Further preferably, it is greater than 0.030 and less than 0.20. Alternatively, it is preferably greater than 0.020 and less than 0.30. Alternatively, it is preferably greater than 0.020 and less than 0.20. Alternatively, it is preferably greater than 0.025 and less than 0.50. Alternatively, it is preferably greater than 0.025 and less than 0.20. Alternatively, it is preferably greater than 0.030 and less than 0.50. Alternatively, it is preferably greater than 0.030 and less than 0.30. In addition, it is preferred that the above ratio is within the above range in multiple parts of the positive electrode active material 100, for example, more than three parts.

[0213] <Pre-analysis processing> Before various analyses, the samples of the positive electrode active material and the positive electrode active material layer may be washed to remove the electrolyte, binder, conductive material or compounds derived therefrom attached to the surface of the positive electrode active material. At this time, lithium is sometimes dissolved in the solvent used for washing, but the added element is not easily dissolved, so it has no effect on the quantitative value of the added element.

[0214] <Needle prick test> The needle penetration test is a test in which a secondary battery is fully charged and a steel needle having a specified diameter selected from 2 mm to 10 mm is used to penetrate the secondary battery at a certain rate. The needle penetration speed may be, for example, 1 mm / s to 20 mm / s. In this embodiment, the needle penetration test apparatus is first described. Fig. 12A A side view of the needle penetration test device 1000 is shown, Fig. 12B A perspective view of a needle penetration test device 1000 is shown.

[0215] Fig. 12A The puncture test device 1000 shown includes a stage 1001, a driving unit 1002, a steel needle 1003, a voltage measuring instrument 1015, a temperature measuring instrument 1016, and a control unit 1018. The driving unit 1002 includes a driving mechanism 1012 for moving the steel needle 1003 in the direction of the arrow in the figure, and the driving mechanism 1012 is used to move the steel needle 1003 in a manner of penetrating a secondary battery 1004 disposed on the stage 1001. At this time, the secondary battery 1004 is in a fully charged state (equal to the States Of Charge (state of charge): SOC100%), and this action is called a puncture action. Note that, Fig. 12A The dotted line in the figure represents the recessed portion of the stage 1001 provided to accommodate the steel needle 1003 after penetration during the acupuncture operation.

[0216] The voltage measuring instrument 1015 transmits information about the voltage of the secondary battery during the needle operation to the control unit 1018. In addition, the temperature measuring instrument 1016 transmits information about the temperature during the needle operation to the control unit 1018. The control unit 1018 can transmit a control signal to the driving unit 1002 when controlling the operation conditions of the steel needle 1003.

[0217] Fig. 12B It is a stereoscopic view illustrating the vicinity of the upper portion of the stage 1001 of the puncture test device 1000. The secondary battery 1004 set on the stage 1001 is electrically connected to the wiring 1005a and the wiring 1005b. Note that the wiring 1005a and the wiring 1005b are included in the voltage measuring instrument 1015, and the wiring 1005a and the wiring 1005b are electrically connected to the positive electrode side tab and the negative electrode side tab of the secondary battery 1004, respectively, so that the voltage of the secondary battery 1004 can be measured. When the temperature sensor 1006 is used as the temperature measuring instrument 1016, the temperature sensor 1006 is set in a manner that contacts the surface of the outer packaging body of the secondary battery 1004. The temperature sensor can also be configured in two or more. For example, when one temperature sensor cannot be used due to expansion of the outer packaging body, other temperature sensors can be used. In configuring two or more temperature sensors, it is preferred to confirm that the temperature difference is within ±5°C, preferably within ±2°C, and then start the puncture action. Note that, Fig. 12B The dotted ellipse in the figure indicates the position where the steel needle 1003 penetrates the secondary battery 1004 during acupuncture. The temperature sensor is preferably set within 5 cm, preferably within 2 cm, from the area where the steel needle 1003 penetrates. When two or more temperature sensors are set, it is preferred that both temperature sensors are set within 5 cm, preferably within 2 cm, from the area where the steel needle 1003 penetrates.

[0218] <Secondary battery in needle penetration test> Next, use Fig.13A and Fig. 13B The state of the secondary battery in the needle penetration test is described again. The needle penetration test is a test in which the secondary battery 1004 is in a fully charged state and is penetrated at a certain rate by a steel needle 1003 satisfying a prescribed diameter selected from 2 mm to 10 mm. Fig.13A 1 is a cross-sectional view showing a state where a secondary battery 1004 is pierced by a steel needle 1003. The secondary battery 1004 has a structure in which a positive electrode 503, a separator 508, a negative electrode 506, and an electrolyte 530 are contained in an outer packaging body 531. The positive electrode 503 includes a positive electrode collector 501 and a positive electrode active material layer 502 formed on both surfaces of the positive electrode collector 501, and the negative electrode 506 includes a negative electrode collector 511 and a negative electrode active material layer 512 formed on both surfaces of the negative electrode collector 511. In addition, Fig. 13B An enlarged view of the vicinity of the steel needle 1003 and the positive electrode current collector 501 is shown, and the positive electrode active material 100 and the conductive material 553 in the positive electrode active material layer 502 are also shown. A carbon material is preferably used as the conductive material 553. The median particle size of the positive electrode active material 100 is 12 μm or less, preferably 10.5 μm or less, and more preferably 8 μm or less, so it can be considered that the positive electrode active material 100 is not easy to break in the needle penetration test, and the secondary battery is not easy to catch fire.

[0219] like Fig.13A and Fig. 13B As shown, when the secondary battery 1004 is pierced by the steel needle 1003, specifically, when the steel needle 1003 penetrates the positive electrode 503 and the negative electrode 506, an internal short circuit occurs. As a result, the potential of the steel needle 1003 becomes equal to the potential of the negative electrode 506, and the electron (e - ) flows to the positive electrode 503 through the steel needle 1003 as shown by the arrow, generating Joule heat in the internal short circuit portion and its vicinity. In addition, the carrier ions separated from the negative electrode 506 due to the internal short circuit are typically lithium ions (Li + ) is released into the electrolyte as shown by the white arrow. Here, when the anions in the electrolyte 530 are insufficient, when the lithium ions are released from the negative electrode 506 into the electrolyte 530, the electrolyte 530 is not electrically neutral, so the electrolyte 530 begins to decompose in order to maintain electrical neutrality. This is one of the electrochemical reactions, and is called a reduction reaction of the electrolyte caused by the negative electrode.

[0220] When the temperature of the secondary battery 1004 rises due to Joule heat, when lithium cobalt oxide is used as the positive electrode active material, the lithium cobalt oxide undergoes a phase change (i.e., a structural change) from an H1-3 type crystal structure to an O1 type crystal structure, and sometimes generates heat. Note that H1-3 and O1 will be described later.

[0221] And, if Fig.13A and Fig. 13B As shown, due to the electrons (e - ) In the charged lithium cobalt oxide, tetravalent Co is reduced to trivalent or divalent, and the lithium cobalt oxide releases oxygen due to the reduction reaction, and the electrolyte 530 is decomposed by the oxidation reaction caused by the oxygen. This is one of the electrochemical reactions, which is called the oxidation reaction of the electrolyte caused by the positive electrode. The flow rate of the current to the positive electrode active material 100, etc. is slightly different depending on the insulation of the positive electrode active material, and it is also considered that the flow rate of the current has an impact on the above-mentioned electrochemical reaction.

[0222] As described above, when an internal short circuit of a secondary battery occurs, the temperature is considered to be Fig.14 changes as shown in the graph. Fig.14 This is a graph that modifies a portion of the graph shown on page 70 [Figure 2-12] of Non-Patent Document 1, and is a graph of the temperature (specifically, internal temperature) of a secondary battery relative to time. When an internal short circuit occurs at (P0), the temperature of the secondary battery rises over time. As shown in (P1), when the temperature of the secondary battery rises to around 100°C due to the heat generated by Joule heat, it exceeds the reference temperature (Ts) of the secondary battery. As a result, in (P2), the negative electrode (when graphite is used, the negative electrode is C 6 In (P3), the positive electrode causes the electrolyte to oxidize and generate heat, and in (P4), the electrolyte causes heat to be generated by thermal decomposition. Then, the secondary battery causes thermal runaway and causes fire or smoke.

[0223] In addition, it is considered that: in order to prevent the generation of smoke, heat, etc. during the puncture test, it is preferred to suppress the temperature rise of the secondary battery and have stable characteristics of the negative electrode, the positive electrode and / or the electrolyte at high temperatures. Specifically, the positive electrode active material 100 preferably has a stable structure that does not release oxygen even when exposed to high temperatures. Alternatively, the positive electrode active material 100 preferably has a structure in which the speed of the current flowing to the positive electrode active material is stable. The positive electrode active material 100 of one embodiment of the present invention can have both the above-mentioned stable structure and a structure that stabilizes the speed of the current, which will be described later.

[0224] <Thermal runaway of secondary batteries> Regarding the principle of thermal runaway of secondary batteries, Fig.15 The figure shows a modified diagram of a part of the graph shown in [Fig. 2-11] on page 69 of Non-Patent Document 1. When the temperature (specifically, the internal temperature) of the secondary battery described above increases during charging, for example, the secondary battery goes through several states and causes thermal runaway. Fig.15 This is a graph of the temperature of a secondary battery relative to time. For example, when the temperature of a secondary battery reaches 100°C or thereabouts, (1) the SEI (Solid Electrolyte Interphase) of the negative electrode is destroyed and heat is generated. In addition, when the temperature of a secondary battery exceeds 100°C, (2) the negative electrode (when graphite is used, the negative electrode is C 6 Li) causes reduction and heat generation of the electrolyte, and (3) oxidation and heat generation of the electrolyte caused by the positive electrode. Furthermore, when the temperature of the secondary battery reaches 180°C or thereabouts, (4) thermal decomposition of the electrolyte occurs, and (5) oxygen release and thermal decomposition from the positive electrode occur (this thermal decomposition includes structural changes in the positive electrode active material). Then, when the temperature of the secondary battery exceeds 200°C, (6) decomposition of the negative electrode occurs, and finally (7) the positive and negative electrodes come into direct contact. After such a state, especially after the state of (5), the state of (6) or the state of (7), the secondary battery causes thermal runaway.

[0225] It is considered that in order to prevent thermal runaway, it is preferable to suppress the temperature rise of the secondary battery and to have stable characteristics of the negative electrode, the positive electrode and / or the electrolyte at high temperatures.

[0226] The content of this embodiment mode can be freely combined with the content of other embodiment modes.

[0227] (Implementation Method 2) In this embodiment, a method for producing a positive electrode active material having a median particle size of 12 μm or less will be described with reference to FIGS. 16 to 18 .

[0228] <Example 1 of Method for Producing Positive Electrode Active Material> Reference FIG. 16A to FIG. 16D An example of a method for producing a positive electrode active material that can be used in one embodiment of the present invention (Example 1 of a method for producing a positive electrode active material) is described. Note that in <Example 1 of a method for producing a positive electrode active material>, the additional elements described as additional element X, additional element Y, and additional element Z in Embodiment 1 are collectively referred to as additional element A.

[0229] <Step S10> First, as step S10, lithium cobalt oxide used as a starting material is prepared. The median particle size of the lithium cobalt oxide is preferably less than 10 μm, and more preferably less than 8 μm. Commercially available lithium cobalt oxide can be used as the lithium cobalt oxide having a median particle size of less than 10 μm. As a typical example of commercially available lithium cobalt oxide, lithium cobalt oxide manufactured by Nippon Chemical Industry Co., Ltd. (trade name "CELLSEED C-5H") can be cited. In addition, in this specification, etc., CELLSEED C-5H is simply referred to as "C-5H". The median particle size of C-5H is approximately 7 μm.

[0230] Lithium cobalt oxide with a median particle size of less than 10 μm can be used Fig. 16B The lithium cobalt oxide produced in steps S11 to S14 is shown. The production method of steps S11 to S14 is described.

[0231] <Step S11> exist Fig. 16B In step S11 shown, as starting materials of lithium and transition metal, a lithium source (referred to as Li source in the drawing) and a cobalt source (referred to as Co source in the drawing) are prepared, respectively.

[0232] As the lithium source, a compound containing lithium is preferably used, for example, lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. The purity of the lithium source is preferably high, for example, a material with a purity of 99.99% or more is preferably used.

[0233] As the cobalt source, a compound containing cobalt is preferably used, for example, cobalt tetraoxide, cobalt hydroxide, etc. The purity of the cobalt source is preferably high, for example, it is preferred to use a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and further preferably 5N (99.999%) or more. By using a high-purity material, impurities in the positive electrode active material can be controlled. As a result, the capacity of the secondary battery is improved and the reliability of the secondary battery is improved.

[0234] <Step S12> Then, in Fig. 16B In step S12 shown, the lithium source and the cobalt source are crushed and mixed to produce a mixed material. The crushing and mixing can be performed by a dry method or a wet method. When the crushing and mixing are performed by a wet method, the powder can be ground smaller, so in order to obtain lithium cobalt oxide with a median particle size of less than 10 μm as a starting material, the wet method is preferred. When the crushing and mixing are performed by a wet method, a solvent is prepared. As a solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is preferred to use a non-protonic solvent that is not easy to react with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. Preferably, the dehydrated acetone with a moisture content suppressed to less than 10 ppm and a purity of 99.5% or more is mixed with a lithium source and a transition metal source for crushing and mixing. By using dehydrated acetone of the above purity, impurities that may be mixed in can be reduced.

[0235] As a method for pulverizing and mixing, a ball mill or a sand mill can be used. When a ball mill is used, aluminum oxide balls or zirconium oxide balls are preferably used as pulverizing media. Zirconia balls are preferred because they have less impurities. In addition, when a ball mill or a sand mill is used, the peripheral speed is preferably set to 100 mm / s or more and 2000 mm / s or less in order to suppress contamination from the pulverizing media.

[0236] <Step S13> Then, in Fig. 16B In step S13 shown, the mixed material is heated.

[0237] Although it varies depending on the achieved temperature, the heating rate in the heating step of the heat treatment is preferably 80°C / h or more and 250°C / h or less. For example, when the temperature in the temperature holding step is 1000°C, the heating rate is preferably 200°C / h.

[0238] The heating rate in the treatment chamber of the heat treatment device is preferably within the above range. Note that sometimes the heating rate set in the heat treatment device is inconsistent with the heating rate in the treatment chamber. For example, the heating rate in the treatment chamber is sometimes lower than the set heating rate. The set heating rate can be adjusted in such a way that the heating rate in the treatment chamber is within the above range. Note that when the temperature in the treatment chamber cannot be measured, the set heating rate of the heat treatment device can be set within the above range. In the case where the temperature of the object to be processed can be measured, it is more preferred that the heating rate of the object to be processed is within the above range.

[0239] The temperature of the temperature holding step is preferably 800°C or more and 1100°C or less, more preferably 900°C or more and 1000°C or less, and further preferably about 950°C. When the temperature is too low, there is a concern that the decomposition and melting of the lithium source and the cobalt source are insufficient. On the other hand, when the temperature is too high, defects may occur due to the following reasons: lithium evaporates from the lithium source; and / or cobalt is excessively reduced; etc. For example, cobalt changes from trivalent to divalent, causing oxygen defects, etc.

[0240] The temperature in the treatment chamber of the heat treatment device is preferably within the above range. Note that sometimes the temperature set in the heat treatment device is inconsistent with the temperature in the treatment chamber. For example, sometimes the temperature in the treatment chamber is lower than the set temperature. The set temperature can be adjusted in a manner such that the temperature in the treatment chamber is within the above range. Note that when the temperature in the treatment chamber cannot be measured, the set temperature of the heat treatment device can be set within the above range. In the case where the temperature of the object to be processed can be measured, it is more preferred that the temperature of the object to be processed is within the above range.

[0241] After the heating process and at the beginning of the temperature keeping process, the temperature in the processing chamber is sometimes higher than the set temperature (also called overshoot). In the event of overshoot, it is also preferred to adjust the heating rate so that the temperature in the processing chamber is within the temperature range of the above-mentioned temperature keeping process. It is also possible to set multiple heating processes with different heating rates. For example, a first heating process and a second heating process after the first heating process are set, and the heating rate of the second heating process is lower than the heating rate of the first heating process. In this way, the occurrence of overshoot can be suppressed. In addition, in the case of temporarily leaving the temperature range of the above-mentioned temperature keeping process due to overshoot, the period is preferably short.

[0242] When the temperature holding step is too short, lithium cobalt oxide may not be synthesized, and when the temperature holding step is too long, productivity decreases. For example, the time is preferably from 1 hour to 100 hours, and more preferably from 2 hours to 20 hours.

[0243] Note that the temperature-raising process, the temperature-maintaining process and the cooling process may also be distinguished inaccurately. In the heat treatment, the length of the period of the above-mentioned temperature range is the above-mentioned time range. Therefore, in this specification, etc., sometimes the temperature of the above-mentioned temperature-maintaining process is recorded as the temperature of the heat treatment or the heating temperature, and the time of the temperature-maintaining process is recorded as the time of the heat treatment or the heating time.

[0244] The atmosphere of the heating process and the temperature holding process preferably contains oxygen. As the oxygen-containing atmosphere, for example, an oxygen atmosphere, a dry air atmosphere, an atmospheric atmosphere, an atmosphere of a mixture of oxygen and other gases (for example, one or more selected from nitrogen and noble gases) can be cited. As the noble gas, for example, argon can be cited. In addition, as the atmosphere, nitrogen, a noble gas, or a mixture of two or more selected from nitrogen and noble gases can also be used.

[0245] The atmosphere in the heating process and the temperature keeping process preferably contains less water. The dew point of the atmosphere is preferably -50°C or less, and more preferably -80°C or less. Dry air may be used appropriately in the heating process and the temperature keeping process. 4 ,CO,CO 2 , and H 2 The impurity concentration of the above materials is set to 5 ppb (parts per billion) or less, which can sometimes suppress the impurities that may be mixed into the material.

[0246] There is a method for continuously introducing gas into a treatment chamber for heat treatment. It can be said that in this method, the gas flows through the treatment chamber. In this case, the flow rate of the gas is set to, for example, 0.1 L / min or more and 0.7 L / min or less per 1 L volume of the treatment chamber. When the volume of the treatment chamber is 40 L, it is preferably 10 L / min or thereabouts. As the gas, for example, oxygen gas, dry air, nitrogen gas, noble gas, and a mixture of two or more gases selected from these gases can be used.

[0247] A method of preventing the gas from entering and exiting the processing chamber after replacing the atmosphere in the processing chamber with a desired gas may also be adopted. For example, the atmosphere in the processing chamber may be replaced with a gas containing oxygen to prevent the gas from entering and exiting the processing chamber. In addition, the gas may be introduced after the processing chamber is depressurized. Specifically, for example, after the processing chamber is depressurized until the differential pressure gauge shows -970 hPa, the gas may be introduced until the pressure reaches 50 hPa.

[0248] After the temperature maintenance process, the object to be processed is cooled in the cooling process. The time of the cooling process can be, for example, more than 15 minutes and less than 50 hours. The cooling process can also be natural cooling. Note that it is not necessarily necessary to cool to room temperature, but only to a temperature allowed by the next step.

[0249] The atmosphere of the cooling process preferably contains oxygen. As the oxygen-containing atmosphere, for example, an oxygen atmosphere, a dry air atmosphere, an atmospheric atmosphere, an atmosphere of mixed oxygen and other gases (for example, one or more selected from nitrogen and noble gases) can be cited. In addition, as the atmosphere, nitrogen, noble gases, or a mixture of two or more selected from nitrogen and noble gases can also be used.

[0250] In the cooling process, gas may also be introduced into the processing chamber. In addition, in the cooling process, gas may continue to be introduced into the processing chamber. As the gas, oxygen gas, dry air, nitrogen gas, noble gas, and a mixture of two or more gases selected from these gases may be used.

[0251] In the cooling process, the temperature in the processing chamber can be gradually lowered from the temperature in the temperature holding process by controlling the temperature in the processing chamber using a heater, etc. In addition, in the cooling process, the temperature can be heated to a temperature lower than the temperature in the temperature holding process and higher than the room temperature.

[0252] In the cooling step, cooling may be performed at room temperature without heating using a heater or the like.

[0253] The gas used in the cooling process may also be heated to a temperature higher than room temperature. In addition, the gas used in the cooling process may also be cooled to a temperature lower than room temperature. Alternatively, a cooling solvent such as cooling water may be used to cool one or both of the heat treatment device and the treatment chamber. For example, cooling water may be circulated around the periphery of the treatment chamber for cooling.

[0254] In the heat treatment, the temperature raising step, the temperature holding step, and the cooling step may be performed in the same treatment chamber, or may be performed in different treatment chambers.

[0255] When a rotary kiln is used for the heating treatment, the heating step, the temperature maintaining step, and the cooling step may be continuously performed in the rotary kiln. Alternatively, the cooling step or a part of the cooling step may be performed outside the rotary kiln.

[0256] The case of using a roller kiln is described. The roller kiln preferably has at least three areas, for example, an area for performing a heating process (hereinafter referred to as a heating zone), an area for performing a temperature maintenance process (hereinafter referred to as a temperature maintenance zone), and an area for performing a cooling process (hereinafter referred to as a cooling zone). The mixed material prepared in step S12 is placed in a heating container such as a sagger, and is moved to the heating zone, the temperature maintenance zone, and the cooling zone of the roller kiln in sequence.

[0257] The container used for heating is preferably an alumina crucible or an alumina sagger. The alumina crucible is a material that is almost free of impurities. In this embodiment, an alumina sagger with a purity of 99.9% is used. In addition, heating the crucible or sagger after covering it with a lid can prevent the volatilization of the material, so it is preferred.

[0258] After heating, the material may be ground and screened as needed. When the heated material is recovered, it may be moved from the crucible to the mortar first, and then the heated material may be recovered. In addition, the mortar is preferably made of zirconium oxide or agate. In addition, the same heating conditions as those in step S13 may be used in the heating process described later other than step S13.

[0259] <Step S14> Through the above steps, it is possible to synthesize Fig. 16B The lithium cobalt oxide (LiCoO 2 ). The lithium cobalt oxide (LiCoO 2 ) can be called a composite oxide. In addition, a grinding process and a classification process can be performed after step S13 to adjust the particle size distribution, and then the lithium cobalt oxide (LiCoO) shown in step S14 can be obtained. 2 ).

[0260] As shown in steps S11 to S14, an example of producing the composite oxide by a solid phase method is shown, but the composite oxide may also be produced by a coprecipitation method. Alternatively, the composite oxide may also be produced by a hydrothermal method.

[0261] <Step S15> Then, in Fig.16A In step S15 shown, lithium cobalt oxide, which is a starting material, is heated. The heating in step S15 is the first heating of lithium cobalt oxide, so it is sometimes referred to as initial heating in this specification, etc. In addition, this heating is also performed before step S31 shown below, so it is sometimes referred to as preheating treatment or pretreatment.

[0262] The lithium compounds and the like that unintentionally remain on the surface of the lithium cobalt oxide are detached due to the initial heating. In addition, the effect of improving the internal crystallinity can be expected. In addition, the lithium source and / or the cobalt source prepared in step S11 and the like are sometimes mixed with impurities, but by performing the initial heating, the impurities in the lithium cobalt oxide that is the starting material can be reduced. In addition, the effect of improving the internal crystallinity refers to, for example, the effect of alleviating the skewness, deviation, etc. caused by the difference in shrinkage of the lithium cobalt oxide manufactured in step S14.

[0263] The initial heating has the effect of smoothing the surface of the lithium cobalt oxide and also has the effect of alleviating cracks and crystal defects in the lithium cobalt oxide.

[0264] Note that when performing this initial heating, it is not necessary to separately prepare materials used as a lithium source, an additional element source, or a flux.

[0265] When the heating time of this step is too short, a sufficient effect cannot be obtained, but when the heating time is too long, the productivity decreases. The range of appropriate heating time can be selected from the heating conditions described in step S13 and implemented. In addition, in order to maintain the crystal structure of the composite oxide, the heating temperature of step S15 is preferably lower than the temperature of step S13. In addition, in order to maintain the crystal structure of the composite oxide, the heating time of step S15 is preferably shorter than the heating time of step S13. For example, it is preferred to heat at a temperature of 700°C or more and 1000°C or less (more preferably 800°C or more and 900°C or less) for more than 1 hour and less than 20 hours (more preferably 1 hour or more and less than 5 hours).

[0266] In lithium cobalt oxide, a temperature difference sometimes occurs between the surface and the inside of the lithium cobalt oxide after the heating in step S13. Sometimes the temperature difference causes a shrinkage difference. It can also be considered that the shrinkage difference occurs because the fluidity between the surface and the inside is different according to the temperature difference. Due to the energy related to the shrinkage difference, a difference in internal stress occurs in the lithium cobalt oxide. The difference in internal stress is also called distortion, and this energy is sometimes called distortion energy. It can be considered that the internal stress is removed after the initial heating in step S15, in other words, the distortion energy is uniformized after the initial heating in step S15. When the distortion energy is uniformized, the distortion of the lithium cobalt oxide is alleviated. Therefore, the surface of the lithium cobalt oxide becomes smooth. It can also be said that the surface is improved. In other words, it can be considered that after step S15, the shrinkage difference generated in the lithium cobalt oxide is alleviated, so that the surface of the composite oxide can be smoothed.

[0267] In addition, the shrinkage difference sometimes leads to the generation of small deviations in the lithium cobalt oxide, such as the generation of crystal deviations. In order to reduce the deviation, step S15 is preferably performed. After step S15, the deviation of the composite oxide can be uniformed (relaxing the deviation of crystals etc. generated in the composite oxide or arranging the grains). As a result, the surface of the composite oxide may become smooth.

[0268] By using lithium cobalt oxide having a smooth surface as a positive electrode active material, the safety of the secondary battery is improved, degradation during charge and discharge is reduced, and cracking of the positive electrode active material can be further prevented.

[0269] Note that step S15 is not a structure that must exist in one embodiment of the present invention, so an embodiment in which step S15 is omitted is also included in one embodiment of the present invention.

[0270] <Step S20> Next, refer to Fig. 16C and Fig.16D The details of step S20 of preparing to add element A as an A source will be described.

[0271] <Step S21> Fig. 16C The step S20 shown includes steps S21 to S23. In step S21, an additive element A is prepared. As specific examples of the additive element A, one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus and boron can be used. Fig. 16C An example is shown in which a magnesium source (referred to as Mg source in the drawing) and a fluorine source (referred to as F source in the drawing) are prepared. Note that in step S21, in addition to the added element A, a lithium source may be prepared separately.

[0272] When magnesium is selected as the additive element A, the source of the additive element A can be referred to as a magnesium source. As a magnesium source, magnesium fluoride (MgF 2 ), magnesium oxide (MgO), magnesium hydroxide (Mg(OH) 2 ) or magnesium carbonate (MgCO 3 ) etc. In addition, multiple magnesium sources may also be used.

[0273] When fluorine is selected as the additive element A, the source of the additive element A may be referred to as a fluorine source. As the fluorine source, for example, lithium fluoride (LiF), magnesium fluoride (MgF 2 ), aluminum fluoride (AlF 3 ), titanium fluoride (TiF 4 ), cobalt fluoride (CoF 2 , CoF 3 ), nickel fluoride (NiF 2 ), zirconium fluoride (ZrF 4 ), vanadium fluoride (VF 5 ), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF 2 ), calcium fluoride (CaF 2 ), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF 2 ), cerium fluoride (CeF 3 , CeF 4 ), lanthanum fluoride (LaF 3 ) or sodium aluminum hexafluoride (Na 3 AlF 6 ) etc. Among them, lithium fluoride has a relatively low melting point, namely 848°C, and is easily melted in the heating step described later, so it is preferred. In other words, lithium fluoride can be used as a flux (also called a solubility aid).

[0274] Magnesium fluoride can be used as both a fluorine source and a magnesium source. In addition, lithium fluoride can also be used as a lithium source. As another lithium source used in step S21, lithium carbonate can be cited.

[0275] Alternatively, the fluorine source may be a gas, and fluorine (F 2 ), carbon fluoride, sulfur fluoride or oxygen fluoride (OF 2 , O 2 F 2 , O 3 F 2 , O 4 F 2 , O 5 F 2 , O 6 F 2 , O 2 F) etc. are mixed in the atmosphere. In addition, a plurality of fluorine sources may be used.

[0276] In this embodiment, lithium fluoride (LiF) is prepared as a fluorine source, and magnesium fluoride (MgF) is prepared as a fluorine source and a magnesium source. 2 ). When lithium fluoride and magnesium fluoride are LiF:MgF 2 =65:35 (molar ratio) is the most effective in lowering the melting point. In addition, when the ratio of lithium fluoride is too large, there will be too much lithium, which may lead to deterioration of the cycle characteristics. For this reason, the molar ratio of lithium fluoride to magnesium fluoride is preferably LiF:MgF 2 =x:1 (0≤x≤1.9), more preferably LiF:MgF 2 =x:1 (0.1≤x≤0.5), more preferably LiF:MgF 2 =x:1 (x=near 0.33) Note that, unless otherwise specified in this specification, “near” means a value greater than 0.9 times and less than 1.1 times the value.

[0277] <Step S22> Then, in Fig. 16C In step S22 shown in the figure, the magnesium source and the fluorine source are pulverized and mixed. This step can be carried out by selecting the conditions for pulverization and mixing described in step S12.

[0278] <Step S23> Then, in Fig. 16C In step S23, the pulverized and mixed materials are collected to obtain a source of the additive element A (source A). The source of the additive element A shown in step S23 includes a plurality of starting materials and can also be called a mixture.

[0279] The median particle size of the mixture is preferably 100 nm to 10 μm, more preferably 300 nm to 5 μm. When one material is used as the source of the additive element A, the median particle size is also preferably 100 nm to 10 μm, more preferably 300 nm to 5 μm.

[0280] When the mixture (including the case where there is only one additive element) that has been micronized in step S22 is mixed with lithium cobalt oxide in a subsequent step, the mixture can be easily uniformly attached to the surface of lithium cobalt oxide. When the mixture is uniformly attached to the surface of lithium cobalt oxide, it is easy to uniformly distribute or diffuse the additive element in the surface layer of the composite oxide after heating, which is preferred.

[0281] <Step S21a> use Fig.16D Description and Fig. 16C Different processes. Fig.16D The illustrated step S20 includes steps S21a to S23.

[0282] exist Fig.16D In step S21a shown, four sources of additive elements A are prepared to be added to lithium cobalt oxide. That is, Fig.16D The type of source of added element A and Fig. 16C In addition, a lithium source may be prepared separately in addition to the element A source.

[0283] As four sources of additive elements A, a magnesium source (denoted as Mg source in the figure), a fluorine source (denoted as F source in the figure), a nickel source (denoted as Ni source in the figure) and an aluminum source (denoted as Al source in the figure) are prepared. The magnesium source and the fluorine source can be obtained from Fig. 16C As the nickel source, nickel oxide, nickel hydroxide, etc. can be used. As the aluminum source, aluminum oxide, aluminum hydroxide, etc. can be used.

[0284] <Step S22> and <Step S23> then, Fig.16D The steps S22 and S23 shown in FIG. Fig. 16C The same applies to step S22 and step S23 described in .

[0285] <Step S31> Then, in Fig.16A In step S31, the lithium cobalt oxide and the additive element A source are mixed after step S15 (initial heating). Here, the number of atoms of cobalt in the lithium cobalt oxide after step S15 is A. Co The number of atoms of magnesium in the added element A Mg The ratio is preferably A Co : A Mg =100:y(0.1≤y≤6), more preferably A Co : A Mg =100:y (0.3≤y≤3). The surface of the lithium cobalt oxide after the initial heating is smooth, so the additive element A can be uniformly added. Therefore, it is preferred that the order of adding the additive element A after the initial heating (step S15) is not to perform the initial heating (step S15) after adding the additive element A.

[0286] In addition, when nickel is selected as the additive element A, the mixing in step S31 is preferably performed in such a manner that the number of nickel atoms in the nickel source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide after step S15. In addition, when aluminum is selected as the additive element A, the mixing in step S31 is preferably performed in such a manner that the number of aluminum atoms in the aluminum source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide after step S15.

[0287] In order not to damage the shape of the lithium cobalt oxide particles, the mixing of step S31 is preferably performed under milder conditions than the crushing and mixing of step S12. For example, it is preferred to adopt conditions with fewer rotations or shorter time than the mixing of step S12. In addition, it can be said that the dry method is a milder condition than the wet method. Mixing can be performed using, for example, a ball mill, a sand mill, etc. When a ball mill is used, it is preferred to use, for example, zirconia balls as the medium.

[0288] In the present embodiment, the mixing is performed by a dry method at 150 rpm for 1 hour using a ball mill using zirconia balls having a diameter of 1 mm. The mixing is performed in a dry room having a dew point of -100°C or higher and -10°C or lower.

[0289] <Step S32> Then, in Fig.16A In step S32, the mixed materials are recovered to obtain a mixture 903.

[0290] <Step S33> Then, in Fig.16A In step S33 shown, the mixture 903 is heated. The heating temperature of step S33 is preferably 800°C to 1100°C, more preferably 800°C to 950°C, and further preferably 850°C to 900°C. In addition, the heating time of step S33 can be 1 hour to 100 hours, preferably 1 hour to 10 hours. The lower limit of the heating temperature of step S33 needs to be above the temperature at which the reaction of lithium cobalt oxide and the source of the additive element A progresses. The temperature at which the reaction progresses can be set to the temperature at which mutual diffusion of the elements contained in the source of the additive element A occurs, and can also be lower than the melting point of the above-mentioned materials. Taking the oxide as an example, from the melting point T m 0.757 times (Taman temperature T d ) solid phase diffusion begins to occur, so the heating temperature in step S33 can be set above 500°C.

[0291] For example, in the case where the additive element A source contains LiF and MgF 2 When Figure 4 LiF and MgF 2 The eutectic point of is around 742° C., so the lower limit of the heating temperature in step S33 is preferably set to 742° C. or higher. Of course, when the temperature is set to a temperature at which one or more of the materials selected from the mixture 903 are melted or higher, the reaction is more likely to proceed.

[0292] In addition, in DSC measurements, Figure 5 As shown in Figure 2, it is observed that at around 830°C, LiCoO 2 :LiF:MgF 2 =100:0.33:1 (molar ratio) is the endothermic peak of the mixture 903. Therefore, the lower limit of the heating temperature is more preferably set to 830°C or more.

[0293] A higher heating temperature is preferred because the reaction proceeds more easily, the heating time is shortened, and the productivity is improved.

[0294] The upper limit of the heating temperature is set to be lower than the decomposition temperature of lithium cobalt oxide (melting point is 1130°C). At a temperature near the decomposition temperature, slight decomposition of lithium cobalt oxide may occur. Therefore, the heating temperature is preferably 1000°C or lower, more preferably 950°C or lower, and further preferably 900°C or lower.

[0295] When the mixture 903 is heated, the partial pressure of fluorine or fluoride derived from the fluorine source or the like is preferably controlled within an appropriate range.

[0296] In the manufacturing method described in this embodiment, some materials such as LiF as a fluorine source are sometimes used as a flux. Through the above function, the heating temperature can be reduced to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, above 742°C and below 950°C, and additive elements such as magnesium can be distributed in the surface layer, thereby manufacturing a positive electrode active material with good characteristics.

[0297] However, the specific gravity of LiF in the gas state is lighter than that of oxygen, so it is possible that LiF will volatilize by heating, and when LiF volatilizes, the LiF in the mixture 903 will decrease. In this case, the function of LiF as a flux is reduced. Therefore, it is preferable to heat while suppressing the volatilization of LiF. In addition, even if LiF is not used as a fluorine source, LiCoO 2 The Li on the surface reacts with F as a fluorine source to generate LiF, and the LiF volatilizes. Therefore, even if a fluoride having a higher melting point than LiF is used, volatilization needs to be suppressed in the same manner.

[0298] Therefore, it is preferable to cover the container of the mixture 903 with a lid or the like to heat the mixture 903. By heating in this way, volatilization of LiF in the mixture 903 can be suppressed.

[0299] The heating in this step is preferably performed in a manner that does not cause the mixture 903 to adhere together. When the mixture 903 adheres together during heating, the area of ​​the particles in contact with oxygen in the atmosphere is reduced, and the diffusion path of the added element (such as fluorine) is blocked, so that the added element (such as magnesium and fluorine) may not be easily distributed in the surface layer.

[0300] In addition, when the added element (such as fluorine) is evenly distributed in the surface layer, a smooth and less uneven positive electrode active material can be obtained. Therefore, in order to maintain the smooth state of the surface heated by step S15 or further smoothen it in this process, it is preferred not to make the mixture 903 bonded together.

[0301] <Step S34> Then, in Fig.16A In step S34 shown, the heated material is recovered and ground as needed to obtain a positive electrode active material 100 containing the added element A. At this time, it is preferred that the recovered positive electrode active material 100 is also screened. Through the above process, a positive electrode active material 100 with a median particle size of 12 μm or less (preferably 10.5 μm or less, more preferably 8 μm or less) can be manufactured.

[0302] <Example 2 of the method for producing positive electrode active material> Reference Fig.17 FIG. 18 and FIG. 19 illustrate another example of a method for producing a positive electrode active material (Example 2 of a method for producing a positive electrode active material). In Example 2 of a method for producing a positive electrode active material, the number of times the additional element is added and the mixing method are different from those in Example 1 of a method for producing a positive electrode active material, but other records can refer to the records in Example 1 of a method for producing a positive electrode active material. Note that in <Example 2 of a method for producing a positive electrode active material>, the additional element X described in Implementation Example 1 is represented as additional element A1. In addition, the additional element Y and the additional element Z described in Implementation Example 1 are collectively referred to as additional element A2.

[0303] <Step S10> and <Step S15> exist Fig.17 In, with Fig.16A Similarly, step S10 and step S15 are performed to prepare lithium cobalt oxide that has been initially heated. Note that step S15 is not an essential structure in one embodiment of the present invention, so an embodiment in which step S15 is omitted is also included in one embodiment of the present invention.

[0304] <Step S20a> Next, as shown in step S20a, a first additional element A1 source (referred to as A1 source in the drawings) is prepared. Fig.18A The details of step S20a will be described.

[0305] <Step S21> exist Fig.18A Step S21 shown in the figure is to prepare a first added element A1 source (denoted as A1 source in the figure). As the A1 source, it can be obtained from Fig. 16C The additive element A1 is selected from the additive element A1 described in step S21. For example, one or more selected from magnesium, fluorine and calcium can be used as the additive element A1. Fig.18A An example is shown in which a magnesium source (referred to as Mg source in the drawing) and a fluorine source (referred to as F source in the drawing) are used as the additive element A1.

[0306] exist Fig.18A Steps S21 to S23 shown in FIG. 1 can be performed by Fig. 16C The production is performed under the same conditions as steps S21 to S23 shown in the figure. As a result, the added element A1 source (A1 source) can be obtained in step S23.

[0307] in addition, Fig.17 Steps S31 to S33 shown can be performed with Fig.16A The same conditions are used to manufacture the steps S31 to S33 shown.

[0308] <Step S34a> Next, the material heated in step S33 is recovered to obtain lithium cobalt oxide containing the additive element A1. Here, in order to distinguish it from the lithium cobalt oxide (first composite oxide) after step S15, it is also referred to as a second composite oxide.

[0309] <Step S40> exist Fig.17 In step S40, a second source of the added element A2 (referred to as A2 source in the drawings) is prepared. Fig.18B and Fig.18C Step S40 is described.

[0310] <Step S41> exist Fig.18B Step S40 shown in the figure is to prepare a second source of the added element A2 (denoted as A2 source in the figure). As the A2 source, it can be obtained from Fig. 16C The additive element A2 is selected from the additive element A described in step S20. For example, one or more selected from nickel, titanium, boron, zirconium and aluminum can be suitably used as the additive element A2. Fig.18B An example is shown in which a nickel source and an aluminum source are used as the additional element A2.

[0311] Fig.18B Steps S41 to S43 shown in FIG. Fig. 16C The same conditions as steps S21 to S23 are used to produce the additive element. As a result, a source of the additive element A2 (A2 source) can be obtained in step S43.

[0312] Fig.18C Steps S41 to S43 shown are Fig.18B An example of a deformation of . Fig.18C In step S41, a nickel source (referred to as Ni source in the figure) and an aluminum source (referred to as Al source in the figure) are prepared, and they are crushed independently in step S42a. As a result, a plurality of second additional element A2 sources (referred to as A2 sources in the figure) are prepared in step S43. Fig.18C Step S40 and Fig.18B The difference of step S40 is that the additional element source is pulverized independently in step S42a.

[0313] <Step S51> to <Step S53> then, Fig.17 Steps S51 to S53 shown in FIG. Fig.16A The conditions of step S53 of the heating process are preferably the same as those of step S31 to step S34 shown in FIG. Fig.17 The temperature of step S33 is lower or / and the time is shorter than that shown in the figure. Specifically, the heating temperature is preferably 800°C to 950°C, more preferably 820°C to 870°C, and further preferably 850°C±10°C. The heating time is, for example, preferably 0.5 hours to 8 hours, more preferably 1 hour to 5 hours.

[0314] Note that when nickel is selected as the additive element A2, the mixing in step S51 is preferably performed in such a manner that the number of nickel atoms in the nickel source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide after step S15. In addition, when aluminum is selected as the additive element A2, the mixing in step S51 is preferably performed in such a manner that the number of aluminum atoms in the aluminum source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide after step S15.

[0315] <Step S54> Then, in Fig.17 In step S54 shown, the heated material is recovered to obtain a positive electrode active material 100 containing the added element A1 and the added element A2. The recovered material can also be ground as needed. Through the above process, a positive electrode active material 100 (composite oxide) with a median particle size of 12 μm or less (preferably 10.5 μm or less, more preferably 8 μm or less) can be manufactured.

[0316] In the manufacturing method example 2 described above, as Fig.17 As shown in FIG. 18 , the additive elements are divided into the first additive element A1 and the second additive element A2 and introduced into the lithium cobalt oxide. By introducing the additive elements separately, the distribution of each additive element along the depth direction can be changed. For example, the first additive element can be distributed in a manner that the concentration in the surface portion is higher than that in the interior, and the second additive element can be distributed in a manner that the concentration in the interior portion is higher than that in the surface portion. Fig.16A and Fig.16D The positive electrode active material 100 manufactured by the steps of adding multiple additive elements A sources together has the advantage of being able to be manufactured at low cost. Fig.17 The positive electrode active material 100 manufactured by the steps of Figure 18 is added with multiple sources of additional elements A in multiple steps, so the manufacturing cost is relatively high, but the distribution of each additional element A in the depth direction can be more accurately controlled, so it is preferred.

[0317] (Implementation 3) In this embodiment, components of the secondary battery will be described again.

[0318] <Positive electrode> The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and may further contain at least one of a conductive material and a binder. As the positive electrode active material, the material described in Embodiment 1 may also be used.

[0319] Fig.19A An example of a schematic diagram of a cross section of the positive electrode 12 is shown.

[0320] The positive electrode current collector 31 may be made of, for example, metal foil. Materials that can be used for the positive electrode current collector 31 will be described later. The positive electrode may be formed by applying a slurry on the positive electrode current collector 31 and drying it. Alternatively, pressing may be performed after drying. In the positive electrode, a positive electrode active material layer 32 is formed on the positive electrode current collector 31.

[0321] The slurry refers to a slurry containing a positive electrode active material, a binder and a solvent, preferably a conductive material. The slurry is sometimes referred to as an electrode slurry or an active material slurry. Sometimes, the positive electrode slurry is used when forming a positive electrode active material layer, and sometimes, the negative electrode slurry is used when forming a negative electrode active material layer.

[0322] The positive electrode active material 100 may also be the material described in Embodiment 1 or Embodiment 2. In addition, the positive electrode active material 100 may be two or more materials having different particle sizes as long as the material has little degradation associated with charge and discharge even when a high charging voltage is used. Fig.19A An example in which the shape of the positive electrode active material 100 is spherical is shown.

[0323] And, in Fig.19A In addition to the positive electrode active material 100, the positive electrode active material 100 with a large median particle size is also included. The median particle size of the positive electrode active material 100 is 1.2 times or more and 3 times or less, preferably 1.5 times or more and 2 times or less of the median particle size of the positive electrode active material 100. The content of the positive electrode active material 100 with a large median particle size is preferably 1 times or more and 9 times or less of the content of the positive electrode active material 100, and more preferably 6 times or more and 8 times or less.

[0324] Specific examples of the carbon material that can be used as the conductive material 42 are shown in Embodiment 1. Fig.19A The case where AB is used as the conductive material 42 is shown.

[0325] The binder is mixed in the slurry to fix the positive electrode current collector 31, the positive electrode active material 100, the positive electrode active material 100 and the conductive material 43. The binder is also called a bonding agent. The binder is a polymer material. When a large amount of the binder is included, the ratio of the active material in the positive electrode is reduced and the discharge capacity of the secondary battery is reduced. Therefore, it is preferred to mix the minimum amount of the binder. Therefore, Fig.19A The adhesive is not shown in the figure. In addition, the materials that can be used for the adhesive will be described later.

[0326] The positive electrode active material layer 32 includes voids 51 which are not filled with the positive electrode active material, the conductive material, and the binder. The voids 51 may be filled with an electrolyte solution.

[0327] FIG. 19B to FIG. 19D Show Fig.19A The deformation example of the positive electrode active material layer is shown. FIG. 19B to FIG. 19D The example in which the positive electrode active material 100 has a polygonal shape with rounded corners is shown. FIG. 19B to FIG. 19D The gaps 51 are also included, and sometimes the gaps 51 are filled with electrolyte.

[0328] Furthermore, Fig.19B An example of the positive electrode 12 including the conductive material 42 as the conductive material in addition to the conductive material 43 is shown. Specific examples of the carbon material that can be used as the conductive material 42 and the conductive material 43 are shown in Embodiment 1. Fig.19B The case where AB is used as the conductive material 42 and graphene or a graphene compound is used as the conductive material 43 is shown.

[0329] In the step of obtaining the electrode slurry, the conductive material 42 and the conductive material 43 may be mixed, or the conductive material 42 and the dispersant may be mixed before adding the conductive material 43. Alternatively, the conductive material 43 and the dispersant may be mixed before adding the conductive material 43.

[0330] In the positive electrode 12, the weight of the conductive material 43 is preferably 1.5 to 20 times, more preferably 2 to 9.5 times, that of the conductive material 42. In other words, the weight of AB is preferably 1.5 to 20 times, more preferably 2 to 9.5 times, that of graphene.

[0331] When the mixing ratio of graphene and AB is set within the above range, when adjusting the slurry, the dispersion stability of AB is excellent and it is not easy to generate an aggregation part. In addition, when the mixing ratio of graphene and AB is set within the above range, a high electrode density can be achieved compared with a positive electrode in which only AB is used for a conductive material. By increasing the electrode density, the capacity per unit weight can be increased. Specifically, the density of the positive electrode active material layer measured by weight can be 3.5 g / cc or more.

[0332] In addition, compared with the positive electrode using only graphene as the conductive material, the electrode density is low, but the mixing ratio of graphene and AB is within the above range, thereby enabling correspondingly fast charging. Therefore, this is particularly effective when used for a vehicle-mounted secondary battery.

[0333] Fig.19C An example of the positive electrode 12 using the conductive material 44 instead of the conductive material 43 is shown. Specific examples of carbon materials that can be used as the conductive material 42 and the conductive material 44 are shown in Embodiment 1. Fig.19C The case where AB is used as the conductive material 42 and carbon fibers are used as the conductive material 44 is shown. By using carbon fibers, aggregation of AB can be prevented and dispersibility can be improved.

[0334] Fig.19D An example of a positive electrode 12 including a conductive material 42, a conductive material 43, and a conductive material 44 is shown. Specific examples of carbon materials that can be used as the conductive material 42 to the conductive material 44 are shown in Embodiment 1. Here, an example is shown in which AB is used as the conductive material 42, graphene or a graphene compound is used as the conductive material 43, and carbon fibers are used as the conductive material 44. By using both graphene and carbon fibers, aggregation of AB can be prevented, and dispersibility can be further improved.

[0335] The secondary battery can be manufactured by the following steps: FIG. 19A to FIG. 19D Any positive electrode in the above is stacked with a separator on the positive electrode, and the stacked body in which the negative electrode is stacked on the separator is placed in an outer packaging body (a metal can can also be used instead of the outer packaging body) and the electrolyte is filled in the outer packaging body.

[0336] <Adhesive> As the binder, for example, styrene-butadiene rubber (SBR) is preferably used. rubber), styrene-isoprene-styrene rubber As the adhesive, rubber materials such as acrylonitrile-butadiene rubber, butadiene rubber, and ethylene-propylene-diene copolymer can be used. In addition, fluororubber can also be used as the adhesive.

[0337] In addition, as a binder, for example, a water-soluble polymer is preferably used. As a water-soluble polymer, for example, polysaccharides etc. can also be used. As polysaccharides, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, regenerated cellulose, starch etc. can be used. In addition, it is more preferred to use these water-soluble polymers and the above-mentioned rubber material in combination.

[0338] Alternatively, as an adhesive, it is preferred to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose.

[0339] As the binder, a plurality of the above-mentioned materials may be used in combination.

[0340] For example, materials with particularly good viscosity regulating effects can also be used in combination with other materials. For example, although rubber materials and the like have high cohesive force and high elasticity, it is sometimes difficult to regulate viscosity when mixed in a solvent. In such a case, for example, it is preferably mixed with materials with particularly good viscosity regulating effects. As materials with particularly good viscosity regulating effects, for example, water-soluble polymers can be used. In addition, as water-soluble polymers with particularly good viscosity regulating functions, the above-mentioned polysaccharides can be used, for example, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, and regenerated cellulose, or starch can be used.

[0341] Note that cellulose derivatives such as carboxymethyl cellulose, for example, can be easily used as viscosity modifiers by being converted into salts such as sodium salts and ammonium salts of carboxymethyl cellulose to improve their solubility. Due to the increased solubility, the dispersibility of active materials or other components can be improved when forming a slurry for an electrode. In this specification, etc., cellulose and cellulose derivatives used as binders for electrodes include their salts.

[0342] By dissolving a water-soluble polymer in water to stabilize its viscosity, the active material and other materials used as a binder combination, such as styrene-butadiene rubber, can be stably dispersed in an aqueous solution. Since the water-soluble polymer has a functional group, it is expected to be easily and stably attached to the surface of the active material. Most cellulose derivatives such as carboxymethyl cellulose have functional groups such as hydroxyl groups or carboxyl groups. Since they have functional groups, the polymer is expected to interact with each other and widely cover the surface of the active material.

[0343] When the binder covering or contacting the surface of the active material forms a film, it is also expected to be used as a passivation film to exert an effect of inhibiting the decomposition of the electrolyte. Here, the "passivation film" is a film that has no conductivity or very low conductivity. For example, when the passivation film is formed on the surface of the active material, it inhibits the decomposition of the electrolyte at the battery reaction potential. More preferably, the passivation film can transmit lithium ions while inhibiting the conductivity.

[0344] <Positive Electrode Current Collector> As the current collector, materials with high conductivity such as stainless steel, gold, platinum, aluminum, titanium and other metals and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, molybdenum, etc. that improve heat resistance are added can be used. In addition, metal elements that react with silicon to form silicides can also be used. As metal elements that react with silicon to form silicides, there are zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, nickel, etc. As the current collector, shapes such as foil, plate, sheet, mesh, punched metal mesh, and drawn metal mesh can be appropriately used. The thickness of the current collector is preferably 5 μm or more and 30 μm or less.

[0345] <Negative electrode> The negative electrode includes a negative electrode active material layer and a negative electrode current collector. In addition, the negative electrode active material layer may also include a negative electrode active material and further include a conductive material and a binder.

[0346] <Negative Electrode Active Material> As the negative electrode active material, for example, an alloy material or a carbon material can be used.

[0347] As the negative electrode active material, an element that can perform charge and discharge reactions through alloying / de-alloying reactions with lithium can be used. For example, a material containing at least one selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium and indium can be used. The capacity of such elements is higher than that of carbon, and in particular, the theoretical capacity of silicon is high, which is 4200mAh / g. Therefore, silicon is preferably used for the negative electrode active material. In addition, compounds containing these elements can also be used. For example, SiO, Mg 2 Si、Mg 2 Ge, SnO, SnO 2 Mg 2 Sn、SnS 2 、V 2 Sn 3 、FeSn 2 、CoSn 2 、Ni 3 Sn 2 , Cu 6 Sn 5 、Ag 3 Sn、Ag 3 Sb、Ni 2 MnSb、CeSb 3 、LaSn 3 ,La 3 Co 2 Sn 7 、CoSb 3 , InSb, SbSn, etc. Here, an element capable of performing a charge-discharge reaction by alloying / de-alloying reaction with lithium and a compound containing the element are sometimes referred to as an alloy material.

[0348] In this specification, "SiO" refers to silicon monoxide, for example. Alternatively, SiO may also be represented as SiO x Here, x preferably represents a value of 1 or a value close to 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.

[0349] As the carbon material, graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), carbon fiber (carbon nanotube), graphene, carbon black, or the like can be used.

[0350] As graphite, artificial graphite or natural graphite can be cited. As artificial graphite, for example, mesocarbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. can be cited. Here, spherical graphite with a spherical shape can be used as artificial graphite. For example, MCMB sometimes has a spherical shape, so it is preferred. In addition, MCMB is relatively easy to reduce its surface area, so it is sometimes preferred. As natural graphite, for example, flaky graphite, spheroidized natural graphite, etc. can be cited.

[0351] When lithium ions are intercalated in graphite (when lithium-graphite intercalation compounds are generated), graphite shows a potential as low as that of lithium metal (0.05 V or more and 0.3 V or less vs. Li / Li + ). As a result, lithium-ion batteries using graphite can show high operating voltages. Graphite also has the following advantages: large capacity per unit volume; relatively small volume expansion; relatively cheap; and higher safety than lithium metal, so it is preferred.

[0352] In addition, titanium dioxide (TiO 2 ), lithium titanium oxide (Li 4 Ti 5 O 12 ), lithium-graphite intercalation compound (Li x C 6 ), niobium pentoxide (Nb 2 O 5 ), tungsten dioxide (WO 2 ), molybdenum dioxide (MoO 2 ) and other oxides.

[0353] In addition, as the negative electrode active material, lithium and transition metal nitrides can be used, that is, Li 3 N-type Li 3-x M x N (M = Co, Ni, Cu). For example, Li 2.6 Co 0.4 N shows a large charge and discharge capacity (the unit weight of active material is 900mAh / g, 1890mAh / cm 3 ), so it is preferred.

[0354] When a nitride containing lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, and thus can react with V used as the positive electrode active material. 2 O 5 Cr 3 O 8 Note that when a material containing lithium ions is used as a positive electrode active material, a nitride containing lithium and a transition metal may be used as a negative electrode active material by previously removing the lithium ions contained in the positive electrode active material.

[0355] In addition, materials that cause conversion reactions can also be used as negative electrode active materials. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as negative electrode active materials. 2 O 3 , CuO, Cu 2 O、RuO 2 Cr 2 O 3 Oxides, CoS 0.89 , NiS, CuS and other sulfides, Zn 3 N 2 , Cu 3 N, Ge 3 N 4 Nitride, NiP 2 ,FeP 2 、CoP 3 Phosphides, FeF 3 、BiF 3 Fluorine compounds.

[0356] In addition, as another form of the negative electrode, it can also be a negative electrode that does not contain a negative electrode active material at the end of battery manufacturing. As a negative electrode that does not contain a negative electrode active material, for example, the following negative electrode can be used, which only contains a negative electrode collector at the end of forming the battery manufacturing, and the lithium ions separated from the positive electrode active material due to the charging of the battery are precipitated in the form of lithium metal on the negative electrode collector, thereby forming a negative electrode active material layer. The battery using this negative electrode is sometimes called a negative electrode-free (anode-free) battery, etc.

[0357] When using a negative electrode that does not contain a negative electrode active material, a film for homogenizing the precipitation of lithium may also be included on the negative electrode current collector. As a film for homogenizing the precipitation of lithium, for example, a solid electrolyte with lithium ion conductivity can be used. As a solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, and a polymer solid electrolyte can be used. Among them, the film of the polymer solid electrolyte is relatively easy to form evenly on the negative electrode current collector, so it is suitable for a film for homogenizing the precipitation of lithium. In addition, as a film for homogenizing the precipitation of lithium, for example, a metal film that forms an alloy with lithium can be used. As a metal film that forms an alloy with lithium, for example, a magnesium metal film can be used. Since lithium and magnesium form a solid solution in a wider composition range, it is suitable for a film for uniformly precipitating lithium.

[0358] In addition, when using a negative electrode that does not contain a negative electrode active material, a negative electrode current collector having concave and convex portions can be used. When using a negative electrode current collector having concave and convex portions, the concave portions of the negative electrode current collector are cavities that are easy to precipitate lithium contained in the negative electrode current collector, thereby preventing the shape of lithium from becoming dendritic when it precipitates.

[0359] As the conductive material and the binder which may be contained in the negative electrode active material layer, the same conductive material and the binder which may be contained in the positive electrode active material layer may be used.

[0360] <Negative Electrode Current Collector> As the negative electrode current collector, copper or the like may be used in addition to the same materials as the positive electrode current collector. In addition, as the negative electrode current collector, it is preferable to use a material that does not alloy with carrier ions such as lithium.

[0361] <Electrolytes> As a method, an electrolyte containing an organic solvent and a lithium salt (also referred to as an electrolyte) dissolved in the organic solvent can be used. As the organic solvent of the electrolyte, an aprotic organic solvent is preferably used, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, vinyl chloride carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, ethylene glycol dimethyl ether (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme (methyl diglyme), acetonitrile, benzonitrile, tetrahydrofuran, cyclopentane sulfone, sultone, etc., or two or more of the above can be used in any combination and ratio.

[0362] By using one or more ionic liquids (room temperature molten salts) with flame retardancy and low volatility as organic solvents, even if the internal temperature rises due to internal short circuit or overcharge of the storage device, the rupture and ignition of the storage device can be prevented. The ionic liquid is composed of cations and anions, including organic cations and anions. As organic cations for electrolytes, aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations and quaternary phosphonium cations or aromatic cations such as imidazolium cations and pyridinium cations can be cited. In addition, as anions for electrolytes, monovalent amide anions, monovalent methylated anions, fluorosulfonic acid anions, perfluoroalkyl sulfonic acid anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions or perfluoroalkyl phosphate anions can be cited.

[0363] In addition, as the lithium salt (electrolyte) dissolved in the above solvent, for example, LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiAlCl 4 、LiSCN、LiBr、LiI、Li 2 SO 4 , Li 2 B 10 Cl 10 , Li 2 B 12 Cl 12 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiC(CF 3 SO 2 ) 3 、LiC(C 2 F 5 SO 2 ) 3 、LiN(CF 3 SO 2 ) 2 、LiN(C 4 F 9 SO 2 )(CF 3 SO 2 )、LiN(C 2 F 5 SO 2 ) 2 , Lithium bis(oxalate borate) 2 O 4 ) 2 , referred to as: LiBOB) and other lithium salts, one or more.

[0364] In addition, additives such as vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate borate) (LiBOB) or dinitrile compounds such as succinonitrile and adiponitrile may be added to the electrolyte. For example, the concentration of the additive may be set to be 0.1 wt % or more and 5 wt % or less relative to the solvent in which the electrolyte is dissolved.

[0365] Alternatively, a polymer gel electrolyte in which a polymer is swollen with an electrolyte solution may be used.

[0366] In addition, by using a polymer gel electrolyte, safety against leakage is improved, and the secondary battery can be made thinner and lighter.

[0367] As gelled polymer, silicone gel, acrylic acid gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, fluorine polymer gel etc. can be used. As gelled polymer, for example, polymers with polyoxyalkylene structures such as polyethylene oxide (PEO), PVDF and polyacrylonitrile etc. and copolymers comprising these etc. can be used. For example, PVDF-HFP as a copolymer of PVDF and hexafluoropropylene (HFP) can be used. In addition, the formed polymer can also have a porous shape.

[0368] <Isolated Body> When the electrolyte includes an electrolyte solution, a separator is disposed between the positive electrode and the negative electrode. As the separator, for example, the following materials can be used: fibers containing cellulose such as paper, nonwoven fabrics, glass fibers, ceramics, or synthetic fibers containing nylon (polyamide), vinylon (polyvinyl alcohol-based fibers), polyester, acrylic resin, polyolefin, polyurethane, etc. It is preferred that the separator is processed into a bag shape and disposed so as to surround either the positive electrode or the negative electrode.

[0369] The separator may have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As a fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As a polyamide material, for example, nylon or aromatic polyamide (meta-aramid or para-aramid) may be used.

[0370] By applying ceramic materials, the oxidation resistance can be improved, thereby suppressing the degradation of the separator during high-voltage charging and discharging, thereby improving the reliability of the secondary battery. By applying fluorine materials, it is easy to make the separator close to the electrode, and the output characteristics can be improved. By applying polyamide materials (especially aromatic polyamide), the heat resistance can be improved, thereby improving the safety of the secondary battery.

[0371] For example, a mixture of aluminum oxide and aramid may be applied to both sides of a polypropylene film. Alternatively, a mixture of aluminum oxide and aramid may be applied to the surface of the polypropylene film in contact with the positive electrode and a fluorine-based material may be applied to the surface in contact with the negative electrode.

[0372] By adopting a separator with a multi-layer structure, the safety of the secondary battery can be ensured even if the total thickness of the separator is small, and thus the capacity per unit volume of the secondary battery can be increased.

[0373] <Outer packaging> As the outer packaging body included in the secondary battery, for example, metal materials such as aluminum and / or resin materials can be used. In addition, a film-like outer packaging body can also be used. As the film, for example, the following three-layer structure film can be used: a metal film with excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is arranged on a film composed of materials such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as polyamide resin and polyester resin is also arranged on the metal film as the outer surface of the outer packaging body. Sometimes a three-layer structure film containing aluminum is called an aluminum laminated film.

[0374] (Implementation 4) In this embodiment, the appearance of the secondary battery is described. The appearance can also be said to be the shape.

[0375] <Coin-type secondary battery> An example of a coin-type secondary battery will be described. Fig. 20A This is an exploded perspective view of a coin-type (single-layer flat) secondary battery. Fig. 20B This is its appearance picture. Fig. 20C Coin-type secondary batteries are mainly used in small electronic devices.

[0376] In order to easily understand the overlapping relationship (upper and lower relationship and position relationship) of components, Fig. 20A A schematic diagram is used. Therefore, Fig. 20A Not with Fig. 20B Exactly the same picture.

[0377] exist Fig. 20A In the embodiment, the positive electrode 304, the separator 310, the negative electrode 307, the spacer 322, and the gasket 312 are stacked. Then, the negative electrode can 302, the positive electrode can 301, and the gasket are used to seal the above components. Fig. 20A The gasket used for sealing is not shown. The spacer 322 and the gasket 312 are used to protect the inside or fix the position in the tank when the positive electrode tank 301 and the negative electrode tank 302 are pressed together. The spacer 322 and the gasket 312 are made of stainless steel or insulating material.

[0378] A stacked structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is referred to as a positive electrode 304 .

[0379] Fig. 20B It is a perspective view of the manufactured coin-type secondary battery.

[0380] In the coin-type secondary battery 300, a positive electrode can 301 serving as a positive terminal and a negative electrode can 302 serving as a negative terminal are insulated and sealed by a gasket 303 formed of polypropylene or the like. A positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector 305. A negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector 308. The negative electrode 307 is not limited to a laminated structure, and a lithium metal foil or an alloy foil of lithium and aluminum may be used.

[0381] In the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 , the active material layer may be formed on one surface of the positive electrode and the negative electrode, respectively.

[0382] As the positive electrode can 301 and the negative electrode can 302, metals such as nickel, aluminum, and titanium, alloys thereof, and alloys of these and other metals (such as stainless steel, etc.) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, etc., the positive electrode can 301 and the negative electrode can 302 are preferably covered with nickel, aluminum, etc. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.

[0383] By immersing the negative electrode 307, the positive electrode 304 and the separator 310 in an electrolyte, Fig. 20C As shown, the positive electrode can 301 is placed at the bottom, the positive electrode 304, the separator 310, the negative electrode 307 and the negative electrode can 302 are stacked in this order, and the positive electrode can 301 and the negative electrode can 302 are pressed with the gasket 303 interposed therebetween to manufacture the coin-type secondary battery 300.

[0384] By using the positive electrode 12 and the like described above in the coin-type secondary battery 300 , the discharge capacity and safety can be improved.

[0385] <Cylindrical secondary battery> Next, refer to Fig.21A An example of a cylindrical secondary battery will be described. Fig.21A As shown, the top surface of the cylindrical secondary battery 616 includes a positive electrode cover (battery cover) 601, and the side and bottom surfaces thereof include a battery can (outer can) 602. The positive electrode cover 601 and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0386] Fig. 21B It is a diagram schematically showing a cross section of a cylindrical secondary battery. Fig. 21B The cylindrical secondary battery shown has a positive electrode cover (battery cover) 601 on the top surface and a battery can (outer can) 602 on the side and bottom surfaces. The positive electrode cover and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0387] A battery element is provided inside the hollow cylindrical battery can 602, in which a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are wound around a separator 605. Although not shown, the battery element is wound around the central axis. One end of the battery can 602 is closed and the other end is open. As the battery can 602, metals such as nickel, aluminum, titanium, their alloys, and alloys of them and other metals (such as stainless steel, etc.) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, the battery can 602 is preferably covered with nickel, aluminum, etc. On the inside of the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched by a pair of opposing insulating plates 608 and insulating plates 609. In addition, an electrolyte (not shown) is injected into the interior of the battery can 602 in which the battery element is provided. As the electrolyte, the same electrolyte as that of a coin-type secondary battery can be used.

[0388] Since the positive electrode and the negative electrode used for the cylindrical storage battery are wound, the active material is preferably formed on both surfaces of the current collector.

[0389] By using the above-mentioned positive electrode 12 and the like in the cylindrical secondary battery 616, the discharge capacity and safety can be improved.

[0390] The positive electrode 604 is connected to the positive terminal (positive electrode current collecting wire) 603, and the negative electrode 606 is connected to the negative terminal (negative electrode current collecting wire) 607. The positive terminal 603 can be made of a metal material such as aluminum. The negative terminal 607 can be made of a metal material such as copper. The positive terminal 603 is resistance welded to the safety valve mechanism 613, and the negative terminal 607 is resistance welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cover 601 through a PTC (Positive Temperature Coefficient) element 611. When the internal pressure of the battery rises to exceed a specified threshold, the safety valve mechanism 613 cuts off the electrical connection between the positive electrode cover 601 and the positive electrode 604. In addition, the PTC element 611 is a thermally sensitive resistor element whose resistance increases when the temperature rises, and limits the amount of current by increasing the resistance to prevent abnormal heating. As a PTC element, barium titanate (BaTiO 3 ) types of semiconductor ceramics, etc.

[0391] Fig. 21C An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616. The positive electrode of each secondary battery contacts a conductor 624 separated by an insulator 625, and the positive electrodes are electrically connected to each other. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. In addition, the negative electrode of each secondary battery is electrically connected to the control circuit 620 via a wiring 626. As the control circuit 620, a charge and discharge control circuit for performing charge and discharge, a protection circuit for preventing overcharge and / or overdischarge, etc. can be used.

[0392] Fig.21D An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616, and the plurality of secondary batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of secondary batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 through a wiring 627. The plurality of secondary batteries 616 may be connected in parallel or in series, or may be connected in parallel and then in series. By configuring the power storage system 615 including the plurality of secondary batteries 616, a large amount of electric power can be obtained.

[0393] Alternatively, a plurality of secondary batteries 616 may be connected in parallel and then connected in series.

[0394] In addition, a temperature control device may be included between the plurality of secondary batteries 616. When the secondary battery 616 is overheated, it can be cooled by the temperature control device, and when the secondary battery 616 is overcooled, it can be heated by the temperature control device. Therefore, the performance of the power storage system 615 is not easily affected by the external temperature.

[0395] In addition, Fig.21D In FIG. 6 , the power storage system 615 is electrically connected to the control circuit 620 via wiring 621 and wiring 622. The wiring 621 is electrically connected to the positive electrodes of the plurality of secondary batteries 616 via the conductive plate 628, and the wiring 622 is electrically connected to the negative electrodes of the plurality of secondary batteries 616 via the conductive plate 614.

[0396] <Other structural examples of secondary batteries> A structural example of a secondary battery will be described using FIG. 22 and FIG. 23 .

[0397] Fig.22A The secondary battery 913 shown includes a winding body 950 provided with a terminal 951 and a terminal 952 inside a housing 930. The winding body 950 is impregnated with an electrolyte inside the housing 930. The terminal 952 is in contact with the housing 930, and the terminal 951 is prevented from contacting the housing 930 by an insulating material. Note that for convenience, although Fig.22A Although the case 930 is shown separately in the figure, in reality, the winding body 950 is covered by the case 930, and the terminals 951 and 952 extend outside the case 930. As the case 930, a metal material (such as aluminum) or a laminate of a metal material and a resin material can be used.

[0398] In addition, if Fig. 22B As shown, multiple materials can also be used to form Fig.22A The housing 930 is shown. For example, Fig. 22B In the secondary battery 913 shown, a case 930a and a case 930b are attached to each other, and a wound body 950 is provided in a region surrounded by the case 930a and the case 930b.

[0399] As the housing 930a, a metal material (such as aluminum, etc.) or a laminate of a metal material and a resin material can be used. Since an insulating material such as an organic resin can be used as the above-mentioned resin material, in particular, by using a material such as an organic resin to form the surface of the antenna, the electric field shielding caused by the secondary battery 913 can be suppressed. In addition, if the electric field shielding caused by the housing 930a is small, an antenna can also be provided inside the housing 930a. As the housing 930b, a metal material (such as aluminum, etc.) or a laminate of a metal material and a resin material can be used.

[0400] Furthermore, Fig. 22C The structure of the wound body 950 is shown. The wound body 950 includes a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is formed by overlapping the negative electrode 931 and the positive electrode 932 with the separator 933 interposed therebetween to form a laminated sheet, and then winding the laminated sheet. In addition, a plurality of layers of the negative electrode 931, the positive electrode 932, and the separator 933 may be stacked.

[0401] By using the positive electrode 12 or the like as the wound body 950 , the discharge capacity and safety can be improved.

[0402] Alternatively, a secondary battery 913 including a wound body 950 a as shown in FIG. 23 may be used. Fig.23A The wound body 950a shown includes a negative electrode 931, a positive electrode 932, and a separator 933. The negative electrode 931 includes a negative electrode active material layer 931a. The positive electrode 932 includes a positive electrode active material layer 932a.

[0403] By using the above-mentioned positive electrode 12 and the like for the wound body 950 a , the discharge capacity and safety can be improved.

[0404] The separator 933 is wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. In addition, from the viewpoint of safety, it is preferable that the negative electrode active material layer 931a is wider than the positive electrode active material layer 932a. In addition, the winding body 950a of the above shape is preferable because of its good safety and productivity.

[0405] like Fig. 23B As shown, the negative electrode 931 is electrically connected to the terminal 951 by ultrasonic bonding, welding or pressing. The terminal 951 is electrically connected to the terminal 911a. In addition, the positive electrode 932 is electrically connected to the terminal 952 by ultrasonic bonding, welding or pressing. The terminal 952 is electrically connected to the terminal 911b.

[0406] like Fig.23C As shown, the wound body 950a and the electrolyte are covered with a case 930 to form a secondary battery 913. The case 930 is preferably provided with a safety valve, an overcurrent protection element, etc. The safety valve is a valve that opens the inside of the case 930 at a specified internal pressure to prevent battery rupture.

[0407] like Fig. 23B As shown, the secondary battery 913 may also include a plurality of winding bodies 950a. By using a plurality of winding bodies 950a, a secondary battery 913 with a larger discharge capacity can be realized. Fig.23A and Fig. 23B For other components of the secondary battery 913 shown in FIG. FIG. 22A to FIG. 22C The secondary battery 913 is shown.

[0408] <Laminated secondary battery> then, Fig.24A and Fig. 24B 1 is an external view showing an example of a laminated secondary battery 500 . Fig.24A and Fig. 24B A positive electrode 503 , a negative electrode 506 , a separator 507 , an outer package 509 , a positive electrode lead electrode 510 , and a negative electrode lead electrode 516 are all shown.

[0409] Fig.24A It is an appearance diagram of a positive electrode 503 and a negative electrode 506. The positive electrode 503 includes a positive electrode current collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. In addition, the positive electrode 503 has an area where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab area). The negative electrode 506 includes a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. In addition, the negative electrode 506 has an area where the negative electrode current collector 504 is partially exposed, namely, the tab area. The area or shape of the tab area of ​​the positive electrode and the negative electrode is not limited to Fig.24A Example shown.

[0410] By using the positive electrode 12 and the like described above in the laminated secondary battery 500 , the discharge capacity and safety can be improved.

[0411] <Method for manufacturing laminated secondary battery> Reference FIG. 25A to FIG. 25C illustrate Fig.24A An example of a method for manufacturing a laminated secondary battery is shown in FIG.

[0412] First, if Fig.25A Prepare the negative electrode 506 and the positive electrode 503 as shown. Fig.25B As shown, a negative electrode 506 and a positive electrode 503 are stacked with a separator 507 sandwiched therebetween. Here, an example using 5 sets of negative electrodes and 4 sets of positive electrodes is shown. In addition, it can also be said that it is a stacked body composed of negative electrodes, separators, and positive electrodes. Next, the tab regions of the positive electrode 503 are joined to each other, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. As the joining method, ultrasonic welding or the like can be used, for example. Similarly, the tab regions of the negative electrode 506 are joined to each other, and the negative electrode lead electrode 516 is joined to the tab region of the outermost negative electrode.

[0413] Next, the negative electrode 506 , the separator 507 , and the positive electrode 503 are arranged on the outer package 509 .

[0414] Below, as Fig.25C As shown, the outer package 509 is folded along the portion indicated by the dotted line. Then, the outer periphery of the outer package 509 is joined. As the joining method, for example, heat pressing or the like can be used. At this time, in order to inject the electrolyte later, a non-joined area (hereinafter referred to as the introduction port) is provided on a part (or one side) of the outer package 509.

[0415] Next, the electrolyte is introduced into the inner side of the outer packaging body 509 from the introduction port provided in the outer packaging body 509. The electrolyte is preferably introduced under a reduced pressure atmosphere or an inert gas atmosphere. Finally, the introduction port is joined. In this way, the laminated secondary battery 500 can be manufactured.

[0416] By using the positive electrode active material 100 for the positive electrode 503 , a secondary battery 500 having high capacity, high discharge capacity, and excellent cycle characteristics can be manufactured.

[0417] <Secondary battery pack> An example of a secondary battery pack 532 that can be wirelessly charged using an antenna will be described with reference to Fig. 26. The secondary battery pack is preferably used as a mobile battery.

[0418] Fig.26A 1 is a diagram showing the appearance of a secondary battery pack 532 , which has a thin rectangular parallelepiped shape (or a relatively thick flat plate shape). Fig.26B 51 is a diagram for explaining the structure of a secondary battery pack 532. The secondary battery pack 532 includes a circuit board 540 and a secondary battery 513. A label 529 is attached to the secondary battery 513. The circuit board 540 is fixed by a sealing tape 515. The secondary battery pack 532 also includes an antenna 517.

[0419] The interior of the secondary battery 513 may have a structure including a wound body or a structure including a stacked body.

[0420] like Fig.26B As shown, in the secondary battery pack 532, for example, a control circuit 590 is provided on a circuit board 540. In addition, the circuit board 540 is electrically connected to the terminal 514. In addition, the circuit board 540 is electrically connected to the antenna 517, one of the positive and negative wires 551 of the secondary battery 513, and the other of the positive and negative wires 552.

[0421] The secondary battery pack 532 includes a layer 519 between the antenna 517 and the secondary battery 513. The layer 519 has a function of shielding the electromagnetic field from the secondary battery 513, for example. As the layer 519, a magnetic body can be used, for example.

[0422] In addition, the shape of antenna 517 is not limited to a coil shape, for example, it can be a linear or plate shape. In addition, antennas such as a planar antenna, an aperture antenna, a traveling wave antenna, an EH antenna, a magnetic field antenna, or a dielectric antenna can also be used. Alternatively, antenna 517 can also be a flat conductor. The flat conductor can also be used as one of the conductors for electric field coupling. In other words, antenna 517 can also be used as one of the two conductors possessed by a capacitor. Thus, not only electromagnetic and magnetic fields are utilized, but also electric fields can be utilized to exchange electric power.

[0423] In addition, if Fig.26C As shown, it may also include a circuit system 590 a disposed on the circuit board 540 and a circuit system 590 b electrically connected to the circuit board 540 through the terminal 514 .

[0424] By using the positive electrode 12 and the like described above for the secondary battery 513 applied to the secondary battery pack 532 , the discharge capacity and safety can be improved.

[0425] (Implementation method 5) In this embodiment, an example of a vehicle equipped with a secondary battery according to one embodiment of the present invention is described.

[0426] As a vehicle, a secondary battery can typically be used in a car. As a car, a new generation of clean energy vehicles such as a hybrid electric vehicle (HV), an electric vehicle (EV) or a plug-in hybrid electric vehicle (also referred to as PHEV or PHV) can be cited, and a secondary battery can be used as one of the power sources installed in the car. Vehicles are not limited to cars. For example, as a vehicle, a tram, a monorail, a ship, a submarine (submersible, unmanned submarine), a flying object (helicopter, unmanned aircraft (drone), airplane, rocket, satellite), an electric bicycle, an electric motorcycle, etc. can be cited, and a secondary battery including one embodiment of the present invention can be applied to these vehicles.

[0427] like Fig.27C As shown, in an electric vehicle, as secondary batteries for main driving, first batteries 1301a and 1301b and a second battery 1311 for supplying power to an inverter 1312 for starting an engine 1304 are provided. The second battery 1311 is also called a cranking battery (also called a starter battery). The second battery 1311 only needs to have a high output and does not need to have a high capacity. In addition, the capacity of the second battery 1311 is smaller than that of the first batteries 1301a and 1301b.

[0428] The internal structure of the first battery 1301a can be a winding type or a stacked type. In addition, the first battery 1301a can also use a solid-state battery. By using a solid-state battery as the first battery 1301a, a high capacity can be achieved, safety is improved, and miniaturization and lightness can be achieved.

[0429] In this embodiment, an example of connecting the first battery 1301a and 1301b in parallel is shown, but more than three batteries may be connected in parallel. In addition, as long as sufficient power can be stored in the first battery 1301a, the first battery 1301b may not be provided. By forming a battery pack with multiple secondary batteries, a larger amount of power can be taken out. Multiple secondary batteries may be connected in parallel, in series, or in series after being connected in parallel. Sometimes multiple secondary batteries are referred to as battery packs.

[0430] In order to cut off the power from the plurality of secondary batteries, the vehicle-mounted secondary battery includes a charging plug or a circuit breaker that can cut off the high voltage without using a tool, which is provided in the first battery 1301a.

[0431] In addition, the power of the first battery 1301a, 1301b is mainly used to rotate the engine 1304, and the power is also supplied to the 42V series vehicle-mounted components (electric power steering system 1307, heater 1308, defogger 1309, etc.) through the DCDC circuit 1306. In the case where the rear wheel includes a rear engine 1317, the first battery 1301a is used to rotate the rear engine 1317.

[0432] Furthermore, the second battery 1311 supplies power to 14V series vehicle-mounted components (audio 1313 , power windows 1314 , lights 1315 , etc.) via the DCDC circuit 1310 .

[0433] Next, refer to Fig.27A The first battery 1301a is described.

[0434] Fig.27A An example of using nine rectangular secondary batteries 1300 as a battery pack 1415 is shown. In addition, the nine rectangular secondary batteries 1300 are connected in series and one electrode is fixed using a fixing portion 1413 formed of an insulator and the other electrode is fixed using a fixing portion 1414 formed of an insulator. In this embodiment, an example of fixing using fixing portions 1413 and 1414 is shown, but it can also be stored in a battery storage box (also referred to as a housing). Assuming that the vehicle is subjected to vibration or shaking from the outside (road surface, etc.), it is preferable to fix multiple secondary batteries using fixing portions 1413, 1414, a battery storage box, etc. In addition, one electrode is electrically connected to the control circuit unit 1320 via wiring 1421. In addition, the other electrode is electrically connected to the control circuit unit 1320 via wiring 1422.

[0435] Alternatively, a memory circuit including a transistor using an oxide semiconductor may be used as the control circuit portion 1320. A charge control circuit or a battery control system including a memory circuit including a transistor using an oxide semiconductor is sometimes referred to as a BTOS (Battery operating system or Battery oxide semiconductor).

[0436] It is preferred to use a metal oxide used as an oxide semiconductor. For example, as a metal oxide, it is preferred to use an In-M-Zn oxide (the element M is selected from one or more of aluminum, gallium, yttrium, copper, vanadium, beryllium, boron, titanium, iron, nickel, germanium, zirconium, molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten and magnesium). In particular, the In-M-Zn oxide that can be applied to the metal oxide is preferably CAAC-OS (C-Axis Aligned Crystal Oxide Semiconductor) or CAC-OS (Cloud-Aligned Composite Oxide Semiconductor). In addition, In-Ga oxide and In-Zn oxide can also be used as metal oxides. CAAC-OS is an oxide semiconductor including a plurality of crystalline regions, and the c-axis of the plurality of crystalline regions is oriented in a specific direction. In addition, the specific direction refers to the thickness direction of the CAAC-OS film, the normal direction of the formed surface of the CAAC-OS film, or the normal direction of the surface of the CAAC-OS film. In addition, the crystalline region is a region having a periodicity of atomic arrangement. Note that when the atomic arrangement is viewed as a lattice arrangement, the crystalline region is also a region where the lattice arrangement is consistent.

[0437] In addition, "CAC-OS" refers to a structure in which the material is separated into a first region and a second region to form a mosaic shape, and the first region is distributed in the film (hereinafter also referred to as a cloud shape). That is, CAC-OS refers to a composite metal oxide having a structure in which the first region and the second region are mixed. Note that it is sometimes difficult to observe a clear boundary between the first region and the second region.

[0438] For example, in the CAC-OS of In-Ga-Zn oxide, based on the EDX mapping image obtained by energy dispersive X-ray spectroscopy (EDX), it can be confirmed that the structure has a region with In as the main component (first region) and a region with Ga as the main component (second region) that are unevenly distributed and mixed.

[0439] When CAC-OS is used for transistors, the complementary effect of the conductivity of the first region and the insulation of the second region can give CAC-OS a switch function (a function of controlling on / off). In other words, a portion of the CAC-OS material has a conductive function and another portion has an insulating function, and the entire material has a semiconductor function. By separating the conductive function and the insulating function, each function can be maximized. Therefore, by using CAC-OS for transistors, a large on-state current (I on ), high field effect mobility (μ) and good switching performance.

[0440] Oxide semiconductors have various structures and various characteristics. The oxide semiconductor of one embodiment of the present invention may include two or more of an amorphous oxide semiconductor, a polycrystalline oxide semiconductor, a-like OS, CAC-OS, nc-OS, and CAAC-OS.

[0441] In addition, the control circuit unit 1320 preferably uses a transistor containing an oxide semiconductor because the transistor can be used in a high temperature environment. In order to simplify the process, the control circuit unit 1320 can also be formed using a unipolar transistor. The operating ambient temperature range of the transistor containing an oxide semiconductor in the semiconductor layer is larger than that of the single-crystalline Si transistor, that is, above -40°C and below 150°C, and the characteristic change when the secondary battery is heated is smaller than that of the single-crystalline transistor. The off-state current of the transistor containing an oxide semiconductor is also below the lower limit of the measurement at 150°C, but the temperature dependence of the off-state current characteristics of the single-crystalline Si transistor is large. For example, at 150°C, the off-state current of the single-crystalline Si transistor increases, and the switching ratio of the current does not become sufficiently large. The control circuit unit 1320 can improve safety. In addition, by combining with a secondary battery in which the positive electrode active material 100 obtained in embodiments 1, 2, etc. is used for the positive electrode, a synergistic effect of safety can be obtained. The use of the positive electrode active material 100 obtained in Embodiments 1 and 2 for a positive electrode secondary battery and a control circuit unit 1320 greatly contributes to reducing accidents such as fires caused by secondary batteries.

[0442] The control circuit unit 1320 using a storage circuit including a transistor using an oxide semiconductor can also be used as an automatic control device for a secondary battery for the causes of instability caused by ten conditions such as micro short circuits. As functions for solving the causes of instability caused by the ten conditions, there can be cited prevention of overcharging, prevention of overcurrent, control of overheating during charging, cell balancing in a battery pack, prevention of overdischarge, a capacity meter, automatic control of charging voltage and current according to temperature, control of charging current according to the degree of degradation, detection of abnormal behavior of micro short circuits, prediction of abnormalities regarding micro short circuits, etc. The control circuit unit 1320 has at least one of the above functions. In addition, ultra-miniaturization of the automatic control device for the secondary battery can be achieved.

[0443] In addition, "micro short circuit" refers to a very small short circuit inside the secondary battery. It is not a state where the positive and negative electrodes of the secondary battery cannot be charged or discharged due to a short circuit, but a phenomenon in which a short circuit current flows slightly in a very small short circuit portion. Since a large voltage change occurs even in a short and very small portion, this abnormal voltage value will affect subsequent speculation.

[0444] One of the reasons for micro short circuits is believed to be that due to repeated charging and discharging, uneven distribution of positive electrode active materials occurs, local current concentration occurs in part of the positive electrode and part of the negative electrode, and part of the separator becomes inoperative, or side reactions produce side reactants, leading to micro short circuits.

[0445] In addition to micro short circuits, the control circuit unit 1320 detects the terminal voltage of the secondary battery and manages the charge and discharge state of the secondary battery. For example, to prevent overcharging, both the output transistor of the charging circuit and the blocking switch can be turned off at almost the same time.

[0446] then, Fig.27B Show Fig.27A An example of a block diagram of a battery pack 1415 is shown.

[0447] The control circuit unit 1320 includes: a switch unit 1324 including at least a switch for preventing overcharging and a switch for preventing overdischarging; a control circuit 1322 for controlling the switch unit 1324; and a voltage measuring unit for the first battery 1301a. In the control circuit unit 1320, the upper limit voltage and the lower limit voltage of the secondary battery used are set to control the upper limit of the current flowing from the outside, the upper limit of the output current flowing to the outside, etc. The range above the lower limit voltage and below the upper limit voltage of the secondary battery is the recommended voltage range. When the voltage is outside this range, the switch unit 1324 functions and serves as a protection circuit. In addition, the control circuit unit 1320 controls the switch unit 1324 to prevent overdischarge and / or overcharge, so it can also be called a protection circuit. For example, when the control circuit 1322 detects a voltage that will become overcharge, the current is shielded by making the switch of the switch unit 1324 in a closed state. In addition, the function of shielding the current according to the increase in temperature can also be set by setting a PTC element in the charge and discharge path. In addition, the control circuit unit 1320 includes an external terminal 1325 (+IN) and an external terminal 1326 (−IN).

[0448] The switch portion 1324 may be formed by combining n-channel transistors and p-channel transistors. In addition to switches including Si transistors using single crystal silicon, for example, Ge (germanium), SiGe (silicon germanium), GaAs (gallium arsenide), GaAlAs (gallium aluminum arsenide), InP (indium phosphide), SiC (silicon carbide), ZnSe (zinc selenide), GaN (gallium nitride), GaO x (gallium oxide; x is a real number greater than 0) constitute the switch section 1324. In addition, the storage element using the OS transistor can be freely configured by stacking it on a circuit using the Si transistor, so it is easy to achieve integration. In addition, the OS transistor can be manufactured by using the same manufacturing equipment as the Si transistor, thereby enabling low-cost manufacturing. That is, by stacking the control circuit section 1320 using the OS transistor on the switch section 1324 for integration, the switch section 1324 and the control circuit section 1320 can be integrated into one chip. The volume occupied by the control circuit section 1320 can be reduced, so miniaturization can be achieved.

[0449] The first battery 1301a and 1301b mainly supply power to 42V series (high voltage series) vehicle-mounted equipment, while the second battery 1311 supplies power to 14V series (low voltage series) vehicle-mounted equipment. In many cases, the second battery 1311 adopts a lead-acid battery because of cost advantages. However, lead-acid batteries have the disadvantages of large self-discharge compared with lithium-ion batteries and easy deterioration due to a phenomenon called sulfation. Although there is an advantage of no need for maintenance when using a lithium-ion battery as the second battery 1311, an abnormality that is difficult to distinguish during manufacturing may occur when it is used for a long time, such as more than three years. In particular, in order to prevent the situation that the second battery 1311 of the starter inverter cannot work, even if the first battery 1301a and 1301b have residual capacity, the second battery 1311 is charged in a manner that is always kept fully charged by supplying power from the first battery.

[0450] This embodiment shows an example in which lithium ion secondary batteries are used for both the first battery 1301a and the second battery 1311. A lead acid battery, an all-solid battery, or an electric double layer capacitor may also be used for the second battery 1311. For example, an all-solid battery of embodiment 6 may also be used. By using an all-solid battery of embodiment 6 as the second battery 1311, a high capacity can be achieved, thereby achieving miniaturization and lightness.

[0451] In addition, the regenerative energy caused by the rotation of the tire 1316 is transmitted to the engine 1304 through the transmission 1305, and is charged to the second battery 1311 from the engine controller 1303 and the battery controller 1302 through the control circuit unit 1321. In addition, the first battery 1301a is charged from the battery controller 1302 through the control circuit unit 1320. In addition, the first battery 1301b is charged from the battery controller 1302 through the control circuit unit 1320. In order to efficiently charge the regenerative energy, it is preferred that the first batteries 1301a and 1301b can be charged at a high speed.

[0452] The battery controller 1302 can set the charging voltage and charging current of the first batteries 1301a and 1301b, etc. The battery controller 1302 sets the charging conditions according to the charging characteristics of the secondary battery to be used and performs high-speed charging.

[0453] In addition, although not shown in the figure, when connected to an external charger, the charger socket or the charger connection cable is electrically connected to the battery controller 1302. The power supplied from the external charger is charged to the first battery 1301a, 1301b through the battery controller 1302. In addition, some chargers are provided with a control circuit without using the function of the battery controller 1302, but in order to prevent overcharging, it is preferred to charge the first battery 1301a, 1301b through the control circuit unit 1320. In addition, sometimes the connection cable or the charger connection cable is provided with a control circuit. The control circuit unit 1320 is sometimes referred to as an ECU (Electronic Control Unit). The ECU is connected to a CAN (Controller Area Network) provided in the electric vehicle. CAN is one of the serial communication standards used as an in-vehicle LAN. In addition, the ECU includes a microcomputer. In addition, the ECU uses a CPU or a GPU.

[0454] As an external charger installed in a charging station, there are 100V outlet-200V outlet or three-phase 200V and 50kW outlet, etc. In addition, it is also possible to charge by supplying power from an external charging device through a contactless power supply method.

[0455] In order to charge the battery in a short time during high-speed charging, a secondary battery that can withstand charging at a high voltage is desired.

[0456] In addition, when graphene is used as a conductive material and the capacity can be suppressed from decreasing and maintained at a high capacity even if the thickness of the electrode layer is increased and the load is increased, a synergistic effect can be achieved to realize a secondary battery with greatly improved electrical characteristics. In particular, it is very effective for secondary batteries used in vehicles, and a longer driving distance can be achieved without increasing the weight ratio of the secondary battery relative to the total weight of the vehicle, specifically, a vehicle that can travel a distance of more than 500 km per charge.

[0457] Next, an example in which a secondary battery as one embodiment of the present invention is mounted on a vehicle, typically a transportation vehicle, will be described.

[0458] When the secondary battery is installed in a vehicle, a new generation of clean energy vehicles such as hybrid electric vehicles (HV), electric vehicles (EV) or plug-in hybrid electric vehicles (PHV) can be realized. In addition, the secondary battery can also be installed in agricultural machinery, electric bicycles including electric-assisted bicycles, motorcycles, electric wheelchairs, electric karts, ships, submarines, airplanes, rockets, artificial satellites, space probes, planetary probes or spacecraft. By using the above-mentioned positive electrode 12 and the like for the secondary battery, the discharge capacity and safety can be improved. Therefore, the secondary battery of one embodiment of the present invention is suitable for miniaturization and lightweight, and can be suitable for use in transportation vehicles.

[0459] FIG. 28A to FIG. 28D A transport vehicle using one embodiment of the present invention is shown. Fig.28A The car 2001 shown is an electric car using an electric motor as a power source for running. Alternatively, the car 2001 is a hybrid car that can use an electric motor and an engine as a power source for running. When the secondary battery is installed in the vehicle, the example of the secondary battery shown in the embodiment 4 can be set in one or more parts. Fig.28A The illustrated automobile 2001 includes a battery pack 2200 including a secondary battery module in which a plurality of secondary batteries are connected, and preferably also includes a charge control device electrically connected to the secondary battery module.

[0460] In addition, in the automobile 2001, the secondary battery of the automobile 2001 can be charged by supplying power from an external charging device using a plug-in method or a contactless power supply method. When charging, the charging method or the specifications of the connector can be appropriately performed according to the methods specified by CHAdeMO (a registered trademark in Japan) or the combined charging system "Combined Charging System". As a charging device, a charging station set up in a commercial facility or a home power supply can also be used. For example, by supplying power from the outside using plug-in technology, the power storage device installed in the automobile 2001 can be charged. Charging can be performed by converting AC power into DC power using a conversion device such as an AC / DC converter.

[0461] In addition, although not shown in the figure, the power receiving device can also be installed in the vehicle and the power can be supplied non-contactly from the power transmission device on the ground for charging. When the non-contact power supply method is used, by assembling the power transmission device in the road or the outer wall, charging can be performed not only when the vehicle is parked but also when it is driving. In addition, the non-contact power supply method can also be used to send and receive power between two vehicles. Furthermore, a solar cell can be set on the outside of the vehicle to charge the secondary battery when it is parked or driving. Such non-contact power supply can be achieved using electromagnetic induction and magnetic field resonance.

[0462] Fig.28B In the diagram, a large transport vehicle 2002 including an electrically controlled engine is shown as an example of a transport vehicle. The secondary battery module of the transport vehicle 2002 is, for example, a secondary battery module having a maximum voltage of 170V, in which four secondary batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series and 48 cells are connected. The battery pack 2201 has the same characteristics as the battery pack 2201 except for the number of secondary batteries constituting the secondary battery module. Fig.28A The functions are the same, so the description is omitted.

[0463] exist Fig.28C In the figure, a large transport vehicle 2003 including an engine controlled by electricity is shown as an example. The secondary battery module of the transport vehicle 2003 is, for example, a battery as follows: a secondary battery module with a maximum voltage of 600V in which more than 100 secondary batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series. Therefore, a secondary battery with less uneven characteristics is required. By using a secondary battery in which the positive electrode active material 100 described in embodiments 1, 2, etc. is used for the positive electrode, a secondary battery with stable battery characteristics can be manufactured, and mass production can be carried out at low cost from the perspective of yield.

[0464] exist Fig.28D , an aircraft 2004 equipped with an engine burning fuel is shown as an example. Fig.28D The aircraft 2004 shown includes wheels for taking off and landing, so it can be said that the aircraft 2004 is a type of transportation vehicle. In the aircraft 2004, multiple secondary batteries are connected to form a secondary battery module and include a battery pack 2203 having a secondary battery module and a charging control device.

[0465] The secondary battery module of the aircraft 2004 has, for example, eight 4V secondary batteries connected in series and a maximum voltage of 32V. In addition to the number of secondary batteries constituting the secondary battery module of the battery pack 2203, the Fig.28A The functions are the same, so the description is omitted.

[0466] Fig.28E As an example, an artificial satellite 2005 using a secondary battery 2204 is shown. Since the artificial satellite 2005 is used in the extremely low temperature space, it is preferable to include a secondary battery 2204 of one embodiment of the present invention. In addition, the secondary battery 2204 is preferably installed inside the artificial satellite 2005 in a state covered with a heat-insulating member.

[0467] (Implementation 6) In this embodiment, using Fig.29A and Fig.29B An example in which the secondary battery of one embodiment of the present invention is installed in a building will be described.

[0468] Fig.29A The house shown includes a storage device 2612 having a secondary battery module of one embodiment of the present invention and a solar panel 2610. By using the above-mentioned positive electrode 12 and the like for the secondary battery, the discharge capacity and safety can be improved. The storage device 2612 is electrically connected to the solar panel 2610 through wiring 2611 and the like. In addition, the storage device 2612 can be electrically connected to a ground-mounted charging device 2604. The power obtained by the solar panel 2610 can be charged into the storage device 2612. In addition, the power stored in the storage device 2612 can be charged into the secondary battery included in the vehicle 2603 through the charging device 2604. The storage device 2612 is preferably arranged in the underfloor space portion. By being arranged in the underfloor space portion, the space on the floor can be effectively utilized. Alternatively, the storage device 2612 can also be arranged on the floor.

[0469] The power stored in the power storage device 2612 can also be supplied to other electronic devices in the house. Therefore, even when power cannot be supplied from a commercial power source due to a power outage or the like, the electronic devices can be used by using the power storage device 2612 of one embodiment of the present invention as an uninterruptible power supply.

[0470] Fig.29B An example of a power storage device according to one embodiment of the present invention is shown. Fig.29B As shown, a power storage device 791 according to one embodiment of the present invention is provided in an underfloor space 796 of a building 799. In addition, the control circuit described in Embodiment 4 may be provided in the power storage device 791, and a secondary battery using the positive electrode active material 100 obtained in Embodiments 1 and 2, etc., for the positive electrode may be used in the power storage device 791, thereby obtaining a synergistic effect of safety. The control circuit described in Embodiment 7 and the secondary battery using the positive electrode active material 100 described in Embodiments 1 and 2, etc., for the positive electrode greatly contribute to reducing accidents such as fires caused by the power storage device 791 including the secondary battery.

[0471] The power storage device 791 is provided with a control device 790 , and the control device 790 is electrically connected to the switchboard 703 , the power storage controller 705 (also referred to as a control device), the display 706 , and the router 709 through wiring.

[0472] Electric power is supplied from the commercial power supply 701 to the switchboard 703 through the lead-in installation portion 710. In addition, both the electric power from the power storage device 791 and the electric power from the commercial power supply 701 are supplied to the switchboard 703, and the switchboard 703 supplies the supplied electric power to the general load 707 and the storage load 708 through the socket (not shown).

[0473] Examples of the general load 707 include electronic devices such as a television and a personal computer, and examples of the power storage load 708 include electronic devices such as a microwave oven, a refrigerator, and an air conditioner.

[0474] The power storage controller 705 has a measuring unit 711, a predicting unit 712, and a planning unit 713. The measuring unit 711 has a function of measuring the power consumption of the general load 707 and the power storage load 708 in a day (e.g., from 0:00 to 24:00). In addition, the measuring unit 711 may also have a function of measuring the power of the power storage device 791 and the power supplied from the commercial power supply 701. In addition, the predicting unit 712 has a function of predicting the required power consumed by the general load 707 and the power storage load 708 in the next day based on the power consumption of the general load 707 and the power storage load 708 in a day. In addition, the planning unit 713 has a function of determining the charging and discharging plan of the power storage device 791 based on the required power predicted by the predicting unit 712.

[0475] The amount of power consumed by the general load 707 and the power storage load 708 measured by the measuring unit 711 can be confirmed using the display 706. Alternatively, it can be confirmed using an electronic device such as a television or a personal computer through the router 709. Furthermore, it can be confirmed using a portable electronic terminal such as a smart phone or a tablet terminal through the router 709. In addition, the required power for each time period (or each hour) predicted by the prediction unit 712 can be confirmed using the display 706, an electronic device, or a portable electronic terminal.

[0476] (Implementation 7) In this embodiment, a two-wheeled vehicle or a bicycle is shown as an example of a vehicle in which a secondary battery is mounted. By using the positive electrode 12 and the like as described above for a secondary battery, the discharge capacity and safety can be improved.

[0477] Fig. 30A An example of an electric bicycle equipped with a secondary battery according to one embodiment of the present invention is shown. Fig.26A The electric bicycle 8700 shown can use the power storage device of one embodiment of the present invention. For example, the power storage device of one embodiment of the present invention includes a plurality of storage batteries and a protection circuit.

[0478] The electric bicycle 8700 includes a power storage device 8702. The power storage device 8702 supplies power to a motor that assists the rider. In addition, the power storage device 8702 is portable. Fig. 30B The power storage device 8702 taken out of the bicycle is shown. The power storage device 8702 has a plurality of secondary batteries 8701 included in the power storage device of one embodiment of the present invention built in, and the remaining power, etc. can be displayed by the display unit 8703. In addition, the power storage device 8702 includes a control circuit 8704 that can perform charging control or abnormality detection of the secondary battery. The control circuit 8704 is electrically connected to the positive electrode and the negative electrode of the secondary battery 8701. In addition, by combining with a secondary battery using the positive electrode active material 100 for the positive electrode, a synergistic effect of safety can be obtained.

[0479] Fig. 30C This is an example of a two-wheeled vehicle using the power storage device of one embodiment of the present invention. Fig. 30C The illustrated scooter 8600 includes a power storage device 8602, a side mirror 8601, and a turn signal lamp 8603. The power storage device 8602 can supply power to the turn signal lamp 8603.

[0480] In addition, Fig. 30C In the illustrated scooter 8600, the power storage device 8602 can be stored in the under-seat storage section 8604. Even if the under-seat storage section 8604 is small, the power storage device 8602 can be stored in the under-seat storage section 8604.

[0481] (Implementation 8) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is incorporated into an electronic device is described. By using the above-mentioned positive electrode active material and the like in the secondary battery, the discharge capacity and safety can be improved.

[0482] As electronic devices equipped with secondary batteries, for example, television devices (also called televisions or television receivers), displays for computers, etc., digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones, mobile phone devices), portable game consoles, portable information terminals, sound reproduction devices, large game consoles such as pinball machines, etc. As portable information terminals, notebook personal computers, tablet terminals, electronic book terminals, mobile phones, etc. can be cited.

[0483] Fig.31A An example of a mobile phone is shown. The mobile phone 2100 includes an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, etc. in addition to a display unit 2102 mounted on a housing 2101. In addition, the mobile phone 2100 includes a secondary battery 2107. By including the secondary battery 2107 using the positive electrode active material 100 described in the above embodiment as the positive electrode, a high capacity can be achieved, and a structure that can cope with the space saving required for miniaturization of the housing can be achieved.

[0484] The mobile phone 2100 can execute various application programs such as mobile phone, e-mail, article reading and writing, music playing, Internet communication, computer games, etc.

[0485] The operation button 2103 may have various functions in addition to time setting, such as power switch, wireless communication switch, silent mode setting and cancellation, power saving mode setting and cancellation, etc. For example, by using the operating system incorporated in the mobile phone 2100, the function of the operation button 2103 can be freely set.

[0486] In addition, the mobile phone 2100 can perform short-range wireless communication standardized by the communication. For example, by communicating with a headset capable of wireless communication, a hands-free call can be made.

[0487] In addition, the mobile phone 2100 has an external connection port 2104, and data can be directly sent to or received from other information terminals through a connector. In addition, charging can also be performed through the external connection port 2104. In addition, the charging operation can also be performed using wireless power supply without using the external connection port 2104.

[0488] The mobile phone 2100 preferably includes a sensor. For example, a fingerprint sensor, a pulse sensor, a human body sensor such as a temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, etc. are preferably installed as the sensor.

[0489] In addition, the mobile phone 2100 may also include an external battery 2150. The external battery 2150 includes a secondary battery and a plurality of terminals 2151. The external battery 2150 can charge the mobile phone 2100 and the like through a cable 2152 and the like. By using the positive electrode active material of one embodiment of the present invention for the secondary battery included in the external battery 2150, a high-performance external battery 2150 can be realized. In addition, even if the capacity of the secondary battery 2107 included in the main body of the mobile phone 2100 is small, it can be used for a long time by charging from the external battery 2150. Therefore, the main body of the mobile phone 2100 can be miniaturized and / or lightweight, and safety can be improved.

[0490] Fig.31B An unmanned aerial vehicle 2300 including a plurality of rotors 2302 is shown. The unmanned aerial vehicle 2300 is also called a drone. The unmanned aerial vehicle 2300 includes a secondary battery 2301 of one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely operated via the antenna.

[0491] Fig. 31C An example of a robot is shown. Fig. 31C The robot 6400 shown includes a secondary battery 6409, an illumination sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0492] The microphone 6402 has a function of sensing the user's voice and surrounding sounds, etc. In addition, the speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user through the microphone 6402 and the speaker 6404.

[0493] The display unit 6405 has the function of displaying various information. The robot 6400 can display the information required by the user on the display unit 6405. The display unit 6405 can also be equipped with a touch panel. In addition, the display unit 6405 can be a detachable information terminal, and by setting it at a fixed position of the robot 6400, it can be charged and send and receive data.

[0494] The upper camera 6403 and the lower camera 6406 have the function of photographing the surrounding environment of the robot 6400. In addition, the obstacle sensor 6407 can detect whether there is an obstacle in the direction of the robot 6400 when it moves forward using the moving mechanism 6408. The robot 6400 can confirm the surrounding environment using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407 and move safely.

[0495] The robot 6400 is provided with a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component therein.

[0496] Fig.31D An example of a sweeping robot is shown. The sweeping robot 6300 includes a display unit 6302 disposed on the surface of a housing 6301, a plurality of cameras 6303 disposed on the side, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, etc. Although not shown in the figure, the sweeping robot 6300 also has wheels, a suction port, etc. The sweeping robot 6300 can walk automatically, detect garbage 6310, and can suck up garbage from the suction port set below.

[0497] The cleaning robot 6300 can determine whether there are obstacles such as walls, furniture, or steps by analyzing the image captured by the camera 6303. In addition, when an object such as a wire that may be entangled with the brush 6304 is found through image analysis, the rotation of the brush 6304 can be stopped. The internal area of ​​the cleaning robot 6300 is equipped with a secondary battery 6306 and a semiconductor device or an electronic component according to one embodiment of the present invention.

[0498] Fig.32A An example of a wearable device is shown. A secondary battery is used as a power source of the wearable device. In addition, in order to improve the splash-proof, waterproof or dust-proof performance when the user uses the wearable device in daily life or outdoors, the user not only wants the wearable device to be able to be charged by wire with the connector part exposed for connection, but also wants to be able to be charged wirelessly.

[0499] For example, the secondary battery of one embodiment of the present invention can be installed in Fig.32A The spectacles-type device 4000 shown in FIG. 4 includes a frame 4000a and a display unit 4000b. By installing a secondary battery in the temple of the curved frame 4000a, the spectacles-type device 4000 can be lightweight, well-balanced, and used continuously for a long time.

[0500] The secondary battery of one embodiment of the present invention may be mounted on the earphone type device 4001. The earphone type device 4001 includes at least a microphone unit 4001a, a flexible tube 4001b, and an earphone unit 4001c. The secondary battery may be provided in the flexible tube 4001b or in the earphone unit 4001c.

[0501] In addition, the secondary battery of one embodiment of the present invention may be mounted on the device 4002 that can be directly mounted on the body. In addition, the secondary battery 4002b may be provided in the thin casing 4002a of the device 4002.

[0502] In addition, the secondary battery of one embodiment of the present invention may be mounted on the device 4003 that can be mounted on clothing. In addition, the secondary battery 4003b may be provided in the thin casing 4003a of the device 4003.

[0503] In addition, the secondary battery of one embodiment of the present invention may be mounted on a waistband device 4006. The waistband device 4006 includes a waistband portion 4006a and a wireless power supply and reception portion 4006b, and the secondary battery may be mounted in an inner region of the waistband portion 4006a.

[0504] Furthermore, the secondary battery of one embodiment of the present invention may be mounted on a wristwatch-type device 4005. The wristwatch-type device 4005 includes a display portion 4005a and a strap portion 4005b, and the secondary battery may be provided on the display portion 4005a or the strap portion 4005b.

[0505] The display unit 4005a can display various information such as e-mails and incoming phone calls in addition to the time.

[0506] In addition, since the wristwatch type device 4005 is a wearable device that is directly wrapped around the wrist, it can also be equipped with sensors for measuring the user's pulse, blood pressure, etc. Thus, the user's exercise volume and health-related data can be stored for health management.

[0507] Fig.32B is a perspective view showing the watch-type device 4005 taken off from the wrist.

[0508] in addition, Fig.32C It is a side view. Fig.32C The internal region includes a secondary battery 913. The secondary battery 913 is provided at a position overlapping with the display portion 4005a. [Example]

[0509] <Method for producing sample 1> In this embodiment, according to Fig.17 18 and the like, a positive electrode active material 100 having a median particle size of 12 μm or less was manufactured and used as a sample 1. A method for manufacturing the positive electrode active material 100 will be described.

[0510] exist Fig.17 The starting material of step S10 is lithium cobalt oxide (LiCoO 2 ), commercially available lithium cobalt oxide (manufactured by Nippon Chemical Industry Co., Ltd., CELLSEED C-5H) containing no additive elements was prepared. The median particle size of C-5H was about 7.0 μm, which satisfied the condition that the median particle size was 12 μm or less.

[0511] Then, in Fig.17 In the heating of step S15, C-5H is placed in a sagger (container), covered with a lid, and then heated in a muffle furnace at 850° C. for 2 hours. After the atmosphere in the muffle furnace is made an oxygen atmosphere, oxygen gas is prevented from entering and leaving the processing chamber.

[0512] Next, according to Fig.18A In step S20a shown in the figure, a source of the additive element A1 is prepared. First, lithium fluoride (LiF) is prepared as a F source, and magnesium fluoride (MgF) is prepared as a Mg source. 2 ). LiF:MgF 2 Weigh LiF and MgF in a ratio of 1:3 (molar ratio) 2 Next, LiF and MgF were mixed in dehydrated acetone. 2 The mixture was stirred at a rotation speed of 500 rpm for 20 hours. A ball mill was used for pulverization and mixing, and zirconia balls were used as pulverization media. After mixing, the mixture was sieved using a sieve with a mesh size of 300 μm, thereby obtaining the added element A1.

[0513] Next, according to Fig.17 The step S31 shown is to mix the lithium cobalt oxide obtained by heating in step S15 (lithium cobalt oxide after initial heating) and the additive element Al source obtained in step S20a. Specifically, MgF 2 The mixture was weighed to a ratio of 1 mol% to the lithium cobalt oxide after the initial heating, and mixed by a dry method. At this time, the mixture was stirred at a rotation speed of 150 rpm for 1 hour. Then, the mixture was screened using a sieve with a mesh size of 300 μm, thereby obtaining a mixture 903 (step S32).

[0514] Then, in Fig.17 In step S33, the mixture 903 is heated. The heating conditions are 900° C. and 5 hours. During heating, the sagger containing the mixture 903 is covered with a lid. The atmosphere in the sagger is made to contain oxygen to prevent oxygen gas from entering and leaving the processing chamber. Lithium cobalt oxide containing Mg and F (composite oxide of step S34a) is obtained by heating.

[0515] Next, according to Fig.18C Step S40 is to prepare a source of the additive element A2. First, nickel hydroxide (Ni(OH) 2 ), prepare aluminum hydroxide (Al(OH) 3 ). Next, nickel hydroxide and aluminum hydroxide were stirred in dehydrated acetone at a rotation speed of 500 rpm for 20 hours. A ball mill was used for pulverization, and zirconium oxide balls were used as pulverizing media. Then, a sieve with a mesh size of 300 μm was used for screening, thereby obtaining the additive element A2 source of step S43.

[0516] Then, in Fig.17 In step S51, lithium cobalt oxide containing Mg and F and an additive element A2 source are mixed by dry method. Specifically, the mixture is stirred at a rotation speed of 150 rpm for 1 hour. As a mixing ratio, relative to LICoO 2 The nickel hydroxide and aluminum hydroxide are both 0.5 mol % and mixed using a ball mill, using zirconium oxide balls as a grinding medium. Finally, the mixture is sieved using a 300 μm sieve to obtain a mixture 904 (step S52).

[0517] Then, in Fig.17 In step S53, the mixture 904 is heated. The heating conditions are 850°C and 2 hours. During heating, the sagger containing the mixture 904 is covered with a lid and heated in a muffle furnace. After the atmosphere in the muffle furnace is made an oxygen atmosphere, oxygen gas is prevented from entering and exiting the treatment chamber. By heating, lithium cobalt oxide (positive electrode active material 100 of step S54) containing Mg, F, Ni and Al is obtained. In this way, the positive electrode active material of sample 1 is obtained.

[0518] <Particle size distribution measurement> The particle size distribution of Sample 1 was measured.

[0519] The particle size distribution was measured using a laser diffraction particle size distribution measuring instrument SALD-2200 manufactured by Shimadzu Corporation. First, about 0.4 g of sample 1, a surfactant, and 1 mL to 2 mL of distilled water were mixed in a beaker, and ultrasonic treatment was performed to fully stir to obtain a dispersion. Then, the dispersion was injected into a stirring water tank, and the photometric distribution was measured 64 times every 2 seconds to analyze the particle size distribution data.

[0520] Fig.33 The results of the particle size distribution measurement of Sample 1 are shown as a solid line. Fig.33 is a graph showing the frequency (%) relative to the particle diameter (μm). Fig.33 In FIG. 1 , as Reference Example 1, the particle size distribution of commercially available lithium cobalt oxide (C-5H manufactured by Nippon Chemical Industry Co., Ltd.) containing no additive element used as a starting material in this example is shown by a dotted line.

[0521] The median particle size of sample 1 was about 9.7 μm. The D90 of sample 1 was 15.5 μm. As a result, it was confirmed that the median particle size of sample 1 satisfied 12 μm or less. In addition, the median particle size of C-5H as reference example 1 was about 7.0 μm.

[0522] It is believed that the added element in Sample 1 is appropriately distributed in the surface layer, so the particle size distribution is larger than that of C-5H. When such Sample 1 is used in a secondary battery, it is less likely to catch fire during a needle penetration test, and a highly safe secondary battery can be provided.

[0523] <Powder resistance measurement> The powder volume resistivity of Sample 1 was measured.

[0524] As a method for measuring the powder volume resistivity, the method described in <<Measurement of Powder Resistance>> of Implementation Example 1 was used. As a measuring device, MCP-PD51 manufactured by Mitsubishi Chemical Analytical Technology Co., Ltd. was used. Among the resistors, Hiresta-UP was selected based on the resistivity. In addition, the measurement was performed in a dry room environment (i.e., a temperature environment of 15°C or more and 30°C or less).

[0525] The powder of Sample 1 was placed in the measuring section, and the powder resistance and powder thickness were measured under pressure conditions of 13 MPa, 25 MPa, 38 MPa, 51 MPa, and 64 MPa, thereby obtaining the powder volume resistivity. Note that the volume resistivity is obtained by multiplying the resistance by the area and dividing by the thickness. Note that the volume resistivity of C-5H as Reference Example 1 is shown in the following table. Based on the resistivity of Reference Example 1, Loresta-GP was selected as the resistor. The following table shows the results of the volume resistivity and conductivity.

[0526] [Table 1]

[0527] As shown in Table 1, it can be seen that the volume resistivity of Sample 1 is higher than that of Reference Example 1. Specifically, it can be seen that the powder volume resistivity of Sample 1 is 2.67×10 9 Ω· cm at a pressure of 64 Mpa. This value is higher than that of Reference Example 1. That is, it can be seen that Sample 1 shows a powder volume resistivity of 1.0×10 3 Ω·cm or more, preferably 4.0×10 3 Ω·cm or more at a pressure of 64 Mpa. It is considered that magnesium etc. are located in the first region in Sample 1, so the powder resistance of the positive electrode active material is increased. When such Sample 1 is used in a secondary battery, it is not easy to catch fire during the nail penetration test, and a secondary battery with high safety can be provided. When such Sample 1 is used in a secondary battery, even if an internal short circuit occurs, the speed of the current flowing into the positive electrode can be made gentle, and a secondary battery with high safety can be provided.

[0528] Under low pressure conditions, there is a tendency for the volume resistivity to be higher than that under high pressure conditions. From this, it can be seen that the powder volume resistivity of Sample 1 is 1.5×10 8 Ω·cm or more at a pressure of 64 Mpa, and 2.1×10 9 Ω·cm or more at a pressure of 13 Mpa. Thus, the values in the above table can be combined regarding the volume resistivity.

[0529] <XPS Analysis> XPS analysis was performed on Sample 1 and Reference Example 1. The measurement conditions of XPS are as follows. Measuring device: QuanteraII manufactured by PHI X-ray source: Monochromatic Al Kα (1486.6 eV) Detection area: Detection depth: About 4 nm to 5 nm (extraction angle is 45°) Measurement spectrum: Wide scan, narrow scan of each detected element

[0530] By analyzing the above XPS measurement results, the XPS analysis results shown in the following table were obtained.

[0531] [Table 2]

[0532] As can be seen from Table 2, the atomic number ratio (atomic %) of each element when the total atomic number of Li, Co, Ni, Al, O, Mg, F, C, Ca, Na, S, Cl and Ti is 100% is shown. Note that the numerical values ​​are rounded off to show in the table, and although the total amount recorded in Table 2 is sometimes 99.9%, the XPS analysis adopts the calculation based on the total atomic number of 100.0%.

[0533] When comparing Sample 1 and Reference Example 1, more Ni, Mg, and F were detected in Sample 1, and less Li and Co were detected. This result is considered to indicate that the first region described in Embodiment 1 was formed in Sample 1.

[0534] Based on the XPS analysis results shown in Table 2, the ratio of the number of atoms of Ni to the number of atoms of Co (A Ni / A Co ), the ratio of the number of atoms of Mg to the number of atoms of Co (A Mg / A Co ) and the ratio of the number of atoms of F to the number of atoms of Co (A F / A Co ), and the following table shows the calculation results.

[0535] [Table 3]

[0536] In the XPS analysis of sample 1, the ratio of the number of atoms of Ni to the number of atoms of Co (A Ni / A Co ) is 0.09 or more, and the ratio of the atomic number ratio of Mg to the atomic number ratio of Co (A Mg / A Co ) is 1.00 or more, and the ratio of the number of atoms of F to the number of atoms of Co (A F / A Co ) is greater than 0.70.

[0537] From the above results, it can be seen that the ratio of the number of atoms of Ni to the number of atoms of Co (A Ni / A Co ) is preferably 0.07 or more, more preferably 0.08 or more, and still more preferably 0.09 or more. Ni / A Co Preferably 0.15 or less, preferably 0.13 or less, preferably 0.11 or less.

[0538] In addition, it can be said that the ratio of the atomic number ratio of Mg to the atomic number ratio of Co (A Mg / A Co ) is preferably 0.8 or more, more preferably 0.9 or more, and further preferably 1.0 or more. In addition, it can be said that A Mg / A Co is preferably 1.4 or less, more preferably 1.3 or less, and further preferably 1.2 or less.

[0539] In addition, it can be said that the ratio of the atomic number ratio of F to the atomic number ratio of Co (A F / A Co ) is preferably 0.5 or more, more preferably 0.6 or more, and further preferably 0.7 or more. In addition, it can be said that A F / A Co is preferably 1.0 or less, preferably 0.9 or less, preferably 0.8 or less.

[0540] When using this kind of Sample 1 in a secondary battery, it is not easy to catch fire during the needle puncture test, and a secondary battery with high safety can be provided.

[0541] <STEM-EDX Analysis> Perform STEM-EDX line analysis on Sample 1. Use HD-2700 manufactured by Hitachi High-Technologies Corporation as the STEM device, and the acceleration voltage is 200 kV. As the EDX detector, use Octane T Ultra W manufactured by Amtec Corporation (the detection element area is 100 mm 2 × 2). Use TEAM manufactured by Amtec Corporation as the EDX software. The EDX analysis measurement conditions are as follows: the beam diameter is The beam residence time is 50 msec, the number of frames is 20 frames, the step size is 0.2 nm, and the number of data steps is 850 steps (width 42 nm).

[0542] As a pretreatment before analysis, a protective film is evaporated on the surface of sample 1. Next, a cross-sectional observation sample is manufactured using a FIB-SEM device. Specifically, carbon as a protective film is evaporated in the observation part of the sample using a carbon coating unit of an ion sputtering device (MC1000 manufactured by Hitachi High-Technologies Corporation), and the periphery of the observation part is removed using a FIB-SEM device (XVision200TBS manufactured by Hitachi High-Technologies Corporation), and then the bottom of the observation part is cut off to reduce the thickness of the observation part to about 60nm. At this time, MPS (microprobe system) is used to pick it up, and the final processing conditions are, for example, an acceleration voltage of 10kV. Through this thinning method, two samples are prepared as cross-sectional observation samples of sample 1: sample 1Basal having an area including a surface parallel to the base surface; and sample 1Edge having an area including a surface (end face) parallel to a surface intersecting the base surface.

[0543] Fig.34A The distribution (counts) of the STEM-EDX line analysis of the region of Sample 1 including the surface parallel to the basal plane is shown. Fig.34B Quantitative values ​​(atomic %) of the STEM-EDX line analysis of the region of Sample 1 including the surface parallel to the basal plane are shown. Fig.35A , Fig.35B and Fig.35C Shown respectively from the above Fig.34A The distribution (count) of STEM-EDX line analysis extracts the distribution of Co and Mg, the distribution of Co and Al, and the distribution of Co and Ni. Fig.36A , Fig.36B and Fig.36C Shown respectively from the above Fig.34B The quantitative values ​​(atomic %) of the STEM-EDX line analysis are the quantitative values ​​of only Mg, only Al and only Ni. Fig.37A The STEM-EDX point analysis of the region including the surface parallel to the base surface of the sample 1 is shown, and the STEM image of the region 1 including the object is also shown. The region 1 corresponds to the surface layer part of the sample 1. Fig.37B This is a graph of a part of the energy spectrum of the enlarged region 1. The horizontal axis of the energy spectrum represents the energy of the characteristic X-ray, and the vertical axis represents the X-ray intensity. The unit of the X-ray intensity is cps (Counts Per Second). Fig.38A The STEM-EDX point analysis of a region including a surface parallel to the base plane of the sample 1 is shown, and the STEM image of the region 2 including the object is also shown. The region 2 corresponds to the interior of the sample 1. Fig.38B This is a graph showing a part of the energy spectrum of region 2 magnified.

[0544] from Fig.34A The average value M of the detection intensity inside cobalt is obtained by AVE The average value of the background M BG 50% of the sum of the points so that they overlap Fig.34A The reference point in each graph is set at a distance of 20 nm to facilitate comparison.

[0545] exist Fig.35A , Fig.35B and Fig.35C In the figure, the direction from the position at a distance of 20 nm (Co half value) to the inside of the particle is the positive direction. The position indicating the maximum value of the detected intensity is called the peak position of the added element, and the peak position of Al is 3.4 nm (the position at a distance of 23.4 nm). In addition, the peak positions of Mg and Ni cannot be specified. The distribution of Al is wide.

[0546] exist Fig.36A In the graph, the direction from the position at a distance of 20nm (Co half value) to the inside of the particle is the positive direction. The quantitative value of magnesium is the maximum at -0.2nm (distance 19.8nm). 1.32 atomic%, 0.35 atomic% at 10 nm (distance 30 nm), 0.42 atomic% at 20 nm (distance 40 nm), and 0.71 atomic% at 50 nm (distance 70 nm). In other words, in the region including the surface parallel to the basal plane of sample 1, magnesium has the maximum quantitative value in the surface layer, and is distributed in the concentration range of 0.3 atomic% or more and 1.4 atomic% or less from the surface layer to the inside. However, as Fig.37A and Fig.38B As shown, in the energy spectrum, no peak of characteristic X-ray derived from magnesium is confirmed in Region 1 and Region 2. Therefore, the magnesium concentration range in the region including the surface parallel to the basal plane of Sample 1 exceeds 0 and is 1.4 atomic % or less.

[0547] exist Fig.36B In the graph, the direction from the position at a distance of 20nm (Co half value) to the inside of the particle is the positive direction. The quantitative value of aluminum is the maximum at 3.4nm (distance 23.4nm). 1.09 atomic%, 0.89 atomic% at 10 nm (distance 30 nm), 0.45 atomic% at 20 nm (distance 40 nm), and 0.10 atomic% at 50 nm (distance 70 nm). In other words, in the region including the surface parallel to the base surface of sample 1, aluminum has the maximum quantitative value in the surface layer, and is distributed in the concentration range of 0.1 atomic% or more and 1.1 atomic% or less from the surface layer to the inside. Fig.37A and Fig.38B As shown, in the energy spectrum, peaks of characteristic X-rays derived from aluminum are confirmed in regions 1 and 2.

[0548] exist Fig.36C , the direction inside the particle is the positive direction from the position at a distan...

Claims

1. A battery comprising: A positive electrode comprising a positive electrode active material and a conductive material, The positive electrode active material comprises cobalt, oxygen, magnesium and nickel. The median particle size of the positive electrode active material is 1 μm or more and 12 μm or less. In EDX line analysis in the depth direction of a region of the positive electrode active material having a plane other than the (001) plane, the distribution of the magnesium has a portion overlapping with the distribution of the nickel. Furthermore, the conductive material is attached to a portion of the surface other than the (001) surface of the positive electrode active material.

2. A battery comprising: A positive electrode comprising a positive electrode active material and a conductive material, The positive electrode active material comprises cobalt, oxygen, magnesium and nickel. The median particle size of the positive electrode active material is 1 μm or more and 12 μm or less. In EDX line analysis in the depth direction of a region of the positive electrode active material having a plane other than the (001) plane, the concentration of the magnesium is 0.3 atomic % or more and 7 atomic % or less, Furthermore, the conductive material is attached to a portion of the surface other than the (001) surface of the positive electrode active material.

3. A battery comprising: A positive electrode comprising a positive electrode active material and a conductive material, The positive electrode active material comprises cobalt, oxygen, magnesium, nickel and aluminum. The median particle size of the positive electrode active material is 1 μm or more and 12 μm or less. In an EDX line analysis in the depth direction of a region of the positive electrode active material having a surface other than the (001) surface, the distribution of magnesium has a portion overlapping with the distribution of nickel and the peak of the magnesium concentration is closer to the surface side of the positive electrode active material than the peak of the aluminum concentration. Furthermore, the conductive material is attached to a portion of the surface other than the (001) surface of the positive electrode active material.

4. A battery comprising: A positive electrode comprising a positive electrode active material and a conductive material, The positive electrode active material comprises cobalt, oxygen, magnesium, nickel and aluminum. The median particle size of the positive electrode active material is 1 μm or more and 12 μm or less. In EDX line analysis in the depth direction of a region of the positive electrode active material having a surface other than the (001) surface, the concentration of magnesium is greater than or equal to 0.3 atomic % and less than or equal to 7 atomic %, and the concentration of aluminum is greater than or equal to 0.1 atomic % and less than or equal to 3 atomic %, Furthermore, the conductive material is attached to a portion of the surface other than the (001) surface of the positive electrode active material.

5. The battery according to any one of claims 1 to 4, The powder volume resistivity of the positive electrode active material is 1.5×10 8 Ω·cm or more.

6. The battery according to any one of claims 1 to 4, The conductive material comprises carbon fiber, graphene or a graphene compound.

7. The battery according to claim 6, The carbon fibers include carbon nanotubes.

8. The battery according to claim 7, The carbon nanotubes are in a tangled shape.

9. An electronic device comprising the battery according to any one of claims 1 to 4.

10. A vehicle comprising the battery according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Positive electrode active material and method for producing positive electrode active material

    WO2020026078A1